Genotype-dependent Food Competition Behaviors in Male Fruit Flies Under Distinct Thermal Conditions - Rui Han; Jun Zhang; Jia-Xin Wang; Yu-Xin Wang; An-Qi Wen; Hao-Wei Wang; Xu Liang; Xiang-Haoran Lin; Lin-Xiang Liu; Ke-Jing Feng (Journal of Insect Behavior, 2026)

A reproducible endothelial-state contrast with limited bulk prognostic robustness in hepatocellular carcinoma - Si-yuan Tan; Lan-hui Qin; Wenqing Liang; Rui Song; Pei-yin Chen; Weihui Xu; Guanzhen Zeng; Yu Zhang; Liling Long (Functional & Integrative Genomics, 2026)

An integrated computational-experimental approach identifies Malate Synthase G as therapeutic target to disrupt carbon metabolism in chronic Pseudomonas aeruginosa infection - Geping Chen; Qiutong Tan; Haochuan Zhou; Rui Wang; Jingyi Mo; Jun Xu; Wenying Chen (Functional & Integrative Genomics, 2026)

Circadian Rhythm Disorders: Focusing on Environmental Risk Factors, Interrelationship with Diseases, and Developing Chronotherapy - Shiya Li; Xia Li; Nan Nan; Yaru Zhang; Zhipeng Yan; Mengzhen Xu; Yuanbao Zhang; Rui Chen; Guohua Qin (Reviews of Environmental Contamination and Toxicology, 2026)

Regulation of Escherichia coli fermentation processes: from molecular mechanisms to smart industrial practice - Haoni Luan; Wenhan Qiu; Rui Yang; Kaiyue Feng; Wei Xu; Fei Wang; Wei Feng; Peng Song (Archives of Microbiology, 2026)

Optimized co-application of biochar and organic fertilizer enhances soil quality and leaf yield in a Cyclocarya paliurus–Camellia sinensis agroforestry system on acidic soils - Rui Deng; Jian Xu; Shanshan Wang; Jianren Wang; Shengzuo Fang (Agroforestry Systems, 2026)

Synthesis of Template-polymerized β-cyclodextrin-based Cationic Microblock Flocculants for the Efficient Removal of Emulsified Oil - Kun Li; Wei Song; Erming Ouyang; Hongwei Yang; Yuxin Yuan; Songbiao Xu; Rui Zhao (Water, Air, & Soil Pollution, 2026)

Intrusion dynamics of descending particle-laden plumes in stratified ambient: the roles of fluid buoyancy fraction and source momentum - Li Zhang; Yan Zhang; Xu-Hui Zhang; Ji-Yan Qiao; Yin-Rui Zhang; Xiao-Bing Lu (Environmental Fluid Mechanics, 2026)

Effects of Compound Yeast Culture on the Intestinal Morphology, Intestinal Function, and Microorganisms of Weaned Lambs - Shixiong Liu; Puguo Hao; Hui Chen; Xueqiang Li; Xiaohui Xu; Rui Du; Chen Xue; Lan Yang; Dacheng Liu (Probiotics and Antimicrobial Proteins, 2026)

An integrated InSAR and SPF-constrained workflow for 3D landslide displacement reconstruction - Dezhi Zai; Rui Pang; Bin Xu; Jun Liu (Bulletin of Engineering Geology and the Environment, 2026)

Extracellular Vesicles Derived from Resveratrol-Treated BMSCs Promote the Repair of Bone Defects in Osteoporotic Rats - Yan Lv; Yongjun Du; Zhi Peng; Chengjie Ma; Zhenggang Li; Rui Xu; Jianhong Hou; Sheng Lu (Stem Cell Reviews and Reports, 2026)

A practical guide to investigating biomolecular condensates: a comment from the plant community - Jiaxuan Peng; Jaime Agudo-Canalejo; Monika Chodasiewicz; Daniël Van Damme; Vangelis Daskalakis; Manuel González-Fuente; Rui Gao; Emmanouela Filippidi; Hongwei Guo; Shengbo He; Kai Huang; Shuai Huang; et al. (Science China Life Sciences, 2026)
Biomolecular condensates formed through phase separation have emerged as a central principle of cellular organization, enabling the dynamic regulation of gene expression, signaling, metabolism, and stress responses. While early conceptual advances in condensate biology have largely originated from animal and in vitro systems, plant cells present a unique set of biological and technical challenges, including rigid cell walls, turgor pressure, plastid autofluorescence, complex endomembrane organization, and acute environmental responsiveness. These distinctive features impede the direct transfer of existing methodologies and drive the development of heterogeneous experimental practices. In this community comment, we present a comprehensive methodological framework for studying biomolecular condensates in plants, spanning in silico prediction, in vitro reconstitution, molecular dynamics simulations, live-cell and super-resolution imaging, material property measurements, membrane-associated condensates, and synthetic condensate engineering. We highlight best practices, common pitfalls, and plant-specific considerations, emphasizing the need for orthogonal validation, quantitative interpretation, and physiological relevance. By consolidating current methodologies and articulating shared principles, this review aims to establish a foundation for rigorous, reproducible, and conceptually coherent research in condensate biology of plants and beyond, with emerging implications for crop genetic improvement and synthetic biology applications.

Rapid assembly of structurally diverse 3,4-dihydroquinazolines with anticancer activity via SDS-promoted aqueous synthesis - Fu-Qiang Yu; Pei-Lu Song; Yan-Rui Fan; Jun-Wei Wang; Xu-Jie Wang; Jin-Fei Yang (Molecular Diversity, 2026)

A 3D finite element limit equilibrium framework for reliability analysis of complex slopes: Demonstrating the superiority of horn-shaped failure mechanisms - Yuliang Chen; Rui Pang; Bin Xu (Journal of Mountain Science, 2026)

Zn-MOF-C Catalyzed Ozonation of Ibuprofen: Performance and Catalytic Mechanism - Xu Wang; Shaopo Wang; Zhe Wang; Yeye Li; Rui Zhang; Rongguang Li; Jing Chang (Water, Air, & Soil Pollution, 2026)

Structure-based classification for differential tyrosine kinase inhibitors efficacy of EGFR exon 19 deletions in non-small cell lung cancer - Wei Zhuang; Hua Bai; Jie Zhao; Weihua Li; Jiaojiao Yu; Zhijie Wang; Jianchun Duan; Xuezhi Hao; Yan Wang; Yutao Liu; Lin Wang; Lin Lin; et al. (Science China Life Sciences, 2026)

Diverse plants recruit functional microbes as engines to drive ecosystem multifunctionality in post-fire forests - Hong-Rui Wang; Yu-Yang Liu; Yang Xu; Kai-Li Wang; Rui Deng; Fu-Juan Feng (Plant and Soil, 2026)

ATP6AP2 ameliorates inflammation and pyroptosis in heart failure by promoting lysosome-dependent STING degradation - Xuan Zhao; Hui Zhang; Xinyue Ding; Huimin Wu; Min Li; Nengpin Yin; Junqing Gao; Youlong Xu; Rui Wang; Zhen Qi; Lina Xing; Zongjun Liu (Apoptosis, 2026)

A novel LSTM-Kriging model for spatiotemporal interpolation of air pollution - Rui Xu; Jiaming Zou; Yuanfeng Sun; Jian Li; Liyi Guo; Shiming Shen; Hang Wan (Air Quality, Atmosphere & Health, 2026)

Additive effects of heat and volatile organic compounds co-exposure on metabolic syndrome: evidence from petrochemical workers in China - Minhua Li; Rui Xu; Yilin Zhang; Shanshan Du; Rong Xu; Qing Zu; Zihu Lv; Wei Zheng; Weimin Ye; Jianjun Xiang (International Archives of Occupational and Environmental Health, 2026)

Fragmentation Performance and Mechanisms of Different Drilling Pattern in Multi-hole Blasting - Yuanquan Xu; Ming Tao; Zhixian Hong; Rui Zhao; Haibo Li; Xibing Li (Rock Mechanics and Rock Engineering, 2026)

Triaxial Creep Behavior and Meso-structural Characteristics of Rock-Concrete Composites with Different Interface Roughness - Weijing Yao; Hanbing Xu; Shengqi Yang; Yongjiang Luo; Shaoge Rui; Jianyong Pang (Rock Mechanics and Rock Engineering, 2026)

Superposition Effects of Fire Exposure and Water Extinguishing on Fracturing Mechanisms and Mechanical Behavior of Granitic Building Stone - Fei Wang; Zhuang Xu; Heinz Konietzky; Liqiang Ma; Yu Pan; Qingyou Zhu; Rui Pang; Benguo He (Rock Mechanics and Rock Engineering, 2026)

A Multimodal Strategy for Enhancing Minimally Invasive Ablation of Lung Tumor - Rui Zhang; Kangwei Zhang; Yue Lou; Guangzhi Wang; Lisa X. Xu (Annals of Biomedical Engineering, 2026)

PD-1⁺ CD8⁺ T cells: roles of PD-1 beyond an exhaustion marker - Jingyi Chen; Zixiang Chen; Liangjie Xu; Jieting Jia; Ke Rui; Jie Tian (Seminars in Immunopathology, 2026)

An improved DT-BiLSTM framework to eliminate seasonal interference in DO prediction of Chengdu, China - Mei Li; Kexing Chen; Zengyao Li; Yilin He; Rui Xu; Zhaoli Wang (Environment, Development and Sustainability, 2026)

Improved Adaptive Variational Mode Decomposition for Denoising Teleseismic P-Wave Data - Rui Ma; Jianye Chen; Erik Westman; Miao Zhang; Xu Ma (Rock Mechanics and Rock Engineering, 2026)

N-myristoyl Transferase Maintains Type II Neuroblasts through Notch Signaling in Drosophila - Sifan Gong; Shuliu Zhang; Xu Yan; Wenting Gong; Qingxia Zhou; Xiaojing Yang; Kun Yang; Menglong Rui; Su Wang (Neuroscience Bulletin, 2026)

Short-term organic fertilizer substitution: effects on crop yield and soil phosphorus dynamics in a rice-rapeseed rotation system - Hui Wang; Wenlong Cheng; Shang Han; Shan Tang; Fahui Jiang; Rongyan Bu; Min Li; Rui Zhu; Mengmeng Tang; Zhenghua Xu; Ji Wu (Journal of Soils and Sediments, 2026)

Sappanone A exerted promising therapeutic effects in vitiligo through Wnt5a-mediated noncanonical Wnt signaling - Mingming Xu; Meilin Ding; Rui Li; Hejuan Zhang; Feifei Ren; Hongyang Li; Wei Zhang (Journal of Natural Medicines, 2026)

Differential analysis of lipid profiles in natural Calculus Bovis and Bovis Calculus Sativus by UHPLC-MS/MS - Qiang Mao; Huan Zhong; Wan-Li Liang; Jin Dai; Rui-Ting Huang; Yi-Di Wang; Di-Yang Sun; Kai Tang; Long-Fei Xia; Hai-Biao Gong; Yi-Fang Li; Wan-Yang Sun; et al. (Journal of Natural Medicines, 2026)

Short-term hot spring balneotherapy ameliorates sleep disorders: wrist-worn wearable-assessed sleep improvement associated with neuroimmune, tryptophan metabolic and gut microbiome alterations - Xiao Zhang; Yue Zou; Xiao-qin He; Yi-hang Xu; Hong-xia Li; Fen Yang; Bao-chao Zhang; Lin-xuan Liao; Meng-xi Cao; Rui-xue Wang; Si-fan Hao; Meng-meng Wang; et al. (International Journal of Biometeorology, 2026)

Apatite-doped cyanobacterial biochar for treating smelting site pollution: A “win–win” strategy for cyanobacteria resource recovery and heavy metal mitigation - Rui Deng; Haoyang Deng; Wanning Ye; Qingsheng Xu; Long Du; Shu Wang; Zhengbo Yue; Wentao Wu (Environmental Geochemistry and Health, 2026)

Potential of Bacillus amyloliquefaciens XSZ-1 as a bio-inoculant for enhancing cotton productivity and health in saline-alkali cotton field soil - Jiayue Yuan; Jiali Lu; Zekun Ma; Yanlei Zhu; Xu Geng; Bei Zheng; Rui Zhang (World Journal of Microbiology and Biotechnology, 2026)

The development of bioinspired copper complexes for CO2 activation and hydration - Ramamoorthy Ramasubramanian; Jyun-Chi Lee; Rui-Ze Xu; Xylon Weng; Tiow-Gan Ong; Sodio C. N. Hsu; Glenn P. A. Yap; Vincent C.-C. Wang (JBIC Journal of Biological Inorganic Chemistry, 2026)

ERK1/2 activation in anti-inflammatory effects and underlying signaling mechanisms - Kaiwen Tao; Lin Xu; Chao Cheng; Fukang Yuan; Yicheng Yu; Lidan Zhang; Runmin Li; Rui Xia; Haibei Dong; Xingqi Wang (Inflammation Research, 2026)

Correction to: Puerarin alleviates myocardial ischemia-reperfusion injury by enhancing FUNDC1-mediated mitophagy - Na Feng; Anhua Zhang; Lingling Yao; Jie Tang; Min Lu; Dandan Shi; Zhuoran Zhu; Rui Liu; Jun Chen; Xinwen Min; Handong Yang; Hao Xu; et al. (Molecular and Cellular Biochemistry, 2026)

Heterogeneity of REE distribution revealed by rare-earth phosphate minerals in Chang’e-6 lunar soil - Zhenhao Hu; Rui Li; Jingwen Liu; Yang Li; Tao Chen; Qinglong Yu; Xi Wang; Baochen Yang; Jingyan Xu; Xiongyao Li; Jianzhong Liu; Ziyuan Ouyang (Acta Geochimica, 2026)

An Attention-Enhanced Temporal Convolutional Network for Surrounding Rock Deformation Prediction in Mountain Tunnels - Rui Su; Yitao Yang; Guowen Xu; Ziqian Yang; Jie Yu; Ruohui Wang; Dong Zhou; Zhuolin Wu (Rock Mechanics and Rock Engineering, 2026)

Establishment and comprehensive performance evaluation of auto- and allo-tetraploids derived from Crassostrea gigas and C. angulata - Xianchao Bai; Yuanxin Liang; Geng Cheng; Jianmin Zhou; Rui Xu; Qi Li (Aquaculture International, 2026)

SYVN1-provoked RASA1 ubiquitination promotes pulmonary inflammation in chronic obstructive pulmonary disease - Ju-Hong Wu; Yi-Cheng Ma; Yu-Qi Wang; Hai-Long Miao; Meng-Xue Liu; Dong-Xu Hua; Min-Min Tang; Tian-Rui Sui; Zhi-Yong Wu; Yu Wang; Jin Yang; Hui Zhao; et al. (Inflammation Research, 2026)

Theta-aurora dynamics: Ionospheric mapping of evolving magnetospheric plasma boundaries - Xin-Ming Chen; Zan-Yang Xing; Qing-He Zhang; Yong-Liang Zhang; Hui-Gen Yang; L. R. Lyons; K. Oksavik; S. E. Milan; Rui-Long Guo; Tong Xu; Bin-Bin Tang; Xiang-Yu Wang; et al. (Science China Earth Sciences, 2026)
The theta-aurora, an auroral feature bridging the nightside and dayside auroral oval under a northward interplanetary magnetic field (IMF), is closely linked to the energetic plasma evolving within the magnetosphere. While existing views emphasize that energetic plasma resides on closed field lines, the mechanism by which it is accelerated and precipitates on open field lines to form the theta aurora remains poorly understood. Here, we introduce a mechanism derived from multi-instrument observations of theta-aurora evolution in the Northern Hemisphere and simulations conducted using a global magnetohydrodynamics (MHD) model. The observations and simulations exhibit excellent agreement, revealing that the theta-aurora represents ionospheric projections of boundaries between distinct magnetospheric plasma. These different magnetospheric plasma, an energetic structure originating from the plasma sheet and the preexisting cold lobe plasma, develop a boundary with contrasting physical properties that drive localized plasma instabilities. Particle precipitation occurs at plasma boundary, and controls both the formation and temporal evolution of theta-aurora. Our findings provide critical insights into the coupling between the ionosphere and magnetosphere under northward IMF.

A comprehensive review on the main alkamides in Piper nigrum and anti-inflammatory properties of piperine - Rui Guo; Yiming Fang; Junyao Li; Haoyang Gao; Zhiqiang Niu; Yadong Lv; Long You; Ji Zhang; Xu Wang; Guiping Wu; Taoyun Wang; Weicheng Hu; et al. (Phytochemistry Reviews, 2026)

Dual Low-b-value-driven U-shaped fusion GAN for synthesizing high-b-value prostate DWI - Rui Feng; Qun Huang; Aiping Chen; Chuanbing Wang; Leilei Zhou; Jingjing Xu; Xiaodong Wang; Da Cao; Xiuhan Li; Wei Wang (Physical and Engineering Sciences in Medicine, 2026)

Does a positive culture correlate with the volume of synovial fluid inoculated into blood culture bottles for the diagnosis of periprosthetic joint infection? - Jia-Zheng Xu; Zhi-Sen Gao; Zhen Zhang; Ping Song; Wei Chai; Rui Li (European Journal of Clinical Microbiology & Infectious Diseases, 2026)

Decoupling pollution sources from health risks of soil metal(loid)s in a mining-impacted agro-ecosystem: Integrating geochemical baselines with bioavailability - Jun Li; Xu-Bin Zhou; Xin-Ying Tuo; Chao Wang; Rui-Qi Yang; Fei Zang (Environmental Geochemistry and Health, 2026)

Archaeal and Bacterial Communities and Their Relations with Hydrochemistry in Gongzhu Co, a Carbon-Poor, Nutrient-Rich Basin Lake of the Qinghai–Xizang Plateau - Minhaoxue Zou; Yujie Tao; Bohan Shi; Rong Xu; Rong Wang; Yongzhen Li; Rui Han; Derui Zhu (Current Microbiology, 2026)

A Novel ML–NWP Coupled Optimization Approach on a Reconstructed WRF Model - Hai Chu; Yuan Cao; Rui Wang; Jianming Xu; Lei Chen; Xuliang Fan; Shiqi Chen; Jianhai Guo; Junjing Wu (Journal of Meteorological Research, 2026)

Pore Connectivity and Its Pattern in Gas Shale Reservoirs - Rui Yang; Sijun Cheng; Zhiliang He; Qinhong Hu; Baojian Shen; Pengwei Wang; Jianting Xu (Journal of Earth Science, 2026)

Exposure to per- and polyfluoroalkyl substances and risk of reproductive system cancers: A systematic review and meta-analysis - Xin Liu; Zhihong Lv; Zixiang Huang; Rui Sun; Dingyu Zhu; Pengcheng Xu; Yiquan Xiong; Xiaowei Guo; Yaxuan Ren; Junhua Zhou (Journal of Environmental Health Science and Engineering, 2026)

Insights to Geometrical and Mechanical Representative Elementary Volume (REV) from a DFN Approach: A Case Study of the Lanping Lead–Zinc Mine - Yan Gu; Rui Yong; Nick Barton; Wen-Jie Xu; Ze Li; Changshuo Wang; Jibo Qin (Rock Mechanics and Rock Engineering, 2026)

Muscone Exerts Rapid Antidepressant Effects Through Modulating Glutamatergic Neural Transmission in the Anterior Cingulate Cortex Against Peripheral Inflammation-induced Depression - Xiaoyun Qiu; Xiaojie Zhang; Yuanzhi Yang; Minjuan Sun; Xiaoli Da; Jiaying Liu; Rui Wang; Jingjia Liang; Xuhong Jiang; Gang Tian; Qiyuan Shan; Yu Du; et al. (Neuroscience Bulletin, 2026)

Impact Mechanical Behavior and Energy Dissipation Analysis of Rock-Concrete Composites with different Interface Roughness - Wei-jing Yao; Han-bing Xu; Sheng-qi Yang; Shao-ge Rui; Jian-yong Pang (Applied Geophysics, 2026)

Efficient combined use of electroacupuncture with ordered collagen scaffolds enhances the therapeutic efficacy of human spinal cord-derived neural progenitor cells therapy in spinal cord injury rats - Yunlong Zou; Weiwei Xue; Bo Guo; Lu Li; Yannan Zhao; Xianming Wu; Zhifeng Xiao; Qi Zhang; Dezun Ma; Xinhao Zhao; Bing Chen; He Shen; et al. (Science China Life Sciences, 2026)

Puerarin alleviates myocardial ischemia-reperfusion injury by enhancing FUNDC1-mediated mitophagy - Na Feng; Anhua Zhang; Lingling Yao; Jie Tang; Min Lu; Dandan Shi; Zhuoran Zhu; Rui Liu; Jun Chen; Xinwen Min; Handong Yang; Hao Xu; et al. (Molecular and Cellular Biochemistry, 2026)

Multifaceted roles of CcGpi7, a phosphoethanolamine transferase, in physiology and virulence of Corynespora cassiicola - Chao Xu; Mengyuan Hou; Qingzhou Ma; Yue-hua Geng; Rui Zang; Taibo Liang; Yashuang Guo; Mengmeng Yang; Meng Zhang (World Journal of Microbiology and Biotechnology, 2026)

Sinomenine ameliorates experimental autoimmune neuritis by suppressing pro-inflammatory immune components and restoring immune balance - Yan-Mei Gong; Zhen-Lin Liu; Si-Miao Li; Yi-Fan Wei; Guo-Hui Gao; Rui-Qi Xu; Xue-Min Li; Yu-Dong Liu; Rui-Sheng Duan; Ying Liu (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Adverse drug events and toxicological mechanisms of esketamine: a study based on US Food and Drug Administration Adverse Event Reporting System and network toxicology analysis - Lu Wang; Rui Xiong; Hengxu Liu; Shipeng Zhang; Ling Xu; Xiaodan Lai (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Image restoration of sediment particles in turbid environments based on a multi-scale fusion algorithm - Xiaolong Ma; Ming Bai; Yiteng Wang; Rui Xu; Sheng Li; Houzhen Wei (Journal of Soils and Sediments, 2026)

The hidden cost of urban noise: spatiotemporal heterogeneity, environmental burden, and economic valuation across major Chinese cities - Zeyu Xu; Rui Hu; Haoran Su; Zhexi Wang (Environmental Monitoring and Assessment, 2026)

BsSYT1 is required for growth, conidiogenesis, stress response and virulence of Bipolaris sorokiniana - Yuehua Geng; Feiyu Yan; Yu Zhang; Mengyao Yang; Changshui Li; Ruilin Shi; Chao Xu; Rui Zang; Qin Guo; Yashuang Guo; Qingzhou Ma; Meng Zhang (World Journal of Microbiology and Biotechnology, 2026)

Correction: Vitamin D receptor suppresses pulmonary fibroblast activation by downregulating the TGF-β1/Smad signaling pathway - Jialai Yang; Tangbing Xu; Rui Xu (Histochemistry and Cell Biology, 2026)

Unveiling the “Glycolysis-Lactate-Lactylation” Axis: A Novel Target in Ischemic Cerebrovascular Disease - Yi Xie; Mengmeng Dai; Rui Liu; Ying Li; Hao Yan; Jiacheng Li; Xuantong Liu; Zhiyuan Yu; Shabei Xu; Wei Wang; Xiang Luo (Neuroscience Bulletin, 2026)
Ischemic cerebrovascular disease involves complex interactions between metabolic reprogramming and epigenetic regulation. Recent studies indicate that enhanced glycolysis and lactate accumulation under hypoxic conditions not only maintain cell viability by supplying energy but also participate in disease regulation through lactylation. Lactylation regulates gene expression, immune polarization, metabolic enzyme activity, and angiogenesis through epigenetic remodeling. In ischemic cerebrovascular disease, lactylation exerts dual roles: on one hand, it can induce neuronal death, exacerbate neuroinflammation, and form a vicious metabolic cycle; on the other hand, it can influence immune cell function and gene expression, thereby exerting neuroprotective effects. Accordingly, targeting lactate metabolism or lactylation-modifying enzymes holds considerable therapeutic potential. Nevertheless, the spatiotemporal regulation, synergistic effects, and broader physiopathological implications of lactylation warrant further in-depth investigation. This review systematically summarizes the role of the “glycolysis-lactate-lactylation” axis in the pathogenesis of ischemic cerebrovascular disease, and discusses its potential as a therapeutic target.

Hybrid crested porcupine optimizer decomposition method and deep neural network to predict long-term rainfall - Man-Hong Fan; Xiao-Ying Ma; Shi-Qi Xu; Rui-Lin Fu (Theoretical and Applied Climatology, 2026)

Variogram-distance graph attention Kriging: an innovative hybrid approach for improving soil heavy metals interpolation - Ling Zeng; Daichi Xu; Rui Sun; Meng Yuan; Bin Hu (Stochastic Environmental Research and Risk Assessment, 2026)

The biphasic regulatory effect of adenosine A2B receptor in ischemic brain injury and its therapeutic potential - Xu Rui; Wang Xi; Li Mengzhu; Su Peiwei; Liu Mudong; Zhu Chao; Luo Wanyu; Zhao Haijun (Purinergic Signalling, 2026)

Twelve-year organic substitution fertilization mitigates microbial nutrient limitation and enhances soil carbon pool stability in a rubber plantation - Wenxian Xu; Yingying Zhang; Wenjie Liu; Congju Zhao; Ashar Tahir; Chuan Yang; Xinwei Guo; Rui Sun; Xiangshuai Yan; Huifang Yuan; Qiu Yang; Zhixiang Wu (Plant and Soil, 2026)

Relationship between expression of derived factor-1CXC chemokine receptor 4 in tumor tissues of patients with non-small cell lung cancer and postoperative lymph node metastasis - Zhanwu Zhang; Xiaoming Wang; Rui Tian; Kunpeng Duan; Xu Zhang (Journal of Molecular Histology, 2026)

Technological evolution and industrial scaling of Spirulina in China: a four-decade review - Kexin Xu; Ronglian Xing; Kang Wang; Song Qin; Zhili Yu; Hongxia Zhang; Rui Li; Zhen Yu; Lihong Chen (Journal of Applied Phycology, 2026)

A deep learning multi-branch network method for landslide susceptibility mapping in the Sichuan-Tibet transportation corridor - Jichao Lv; Ruikai Hong; Xin Bao; Renzhe Wu; Xu He; Guoxiang Liu; Rui Zhang (Bulletin of Engineering Geology and the Environment, 2026)

From SPP to RTK: promoting the satellite navigation potential of acoustically excited antenna - Shangyang Wang; Yifan Fu; Rui Hu; Du Li; Bing Xu; Ruofan Liu; Yinuo Song; Junru Li; Bin Fang; Wenkui Lin; Zhongming Zeng; Xiangwei Zhu (GPS Solutions, 2026)

Quantitative analyzing method for floor acceleration amplification factor based on instrumented buildings - Tao Wang; Rui Pan; Guoshan Xu; Liyan Meng; Jisheng Liu (Earthquake Engineering and Engineering Vibration, 2026)

ChIP-seq and RNA-seq Reveal the Involvement of Histone Lactylation Modification in Early Pregnancy with Subclinical Hypothyroidism - Chaofei Cheng; Lizhen Guo; Yinjuan Xu; Rongzhu Xiong; Leirong Zheng; Yanmei Peng; Rui Hua (Biochemical Genetics, 2026)

Spatial Distribution Characteristics of Secondary PM2.5 in Beijing-Tianjin-Hebei Region Based on Time Series Decomposition - Qing Yao; Jing Ding; Zi-rui Liu; Xu Yang; Ying-xiao Tang; Zi-yin Cai; Su-qin Han (Aerosol Science and Engineering, 2026)

Construction and Simulation of Global Land Surface Microwave Emissivity Atlas Using FY-3D Satellite Data - Yonghong Liu; Fuzhong Weng; Fei Tang; Yang Han; Qingyang Liu; Rui Li; Yongming Xu; Jun Yang (Advances in Atmospheric Sciences, 2026)

Effect of 6-Month High-Impact and Resistance Exercise on Regional Strength and BMD of Spine: A Clinical Trial Combined with a Finite-Element Study - Pu Duan; Yinxia Nie; Shizhong Liu; Xiaoyu Xia; Rui Xu; Simin Li; Vadim V. Silberschmidt; Lin Meng; Juan Du; Dong Ming (Annals of Biomedical Engineering, 2026)

Rectal nanoparticulate-hydrogel delivering budesonide to reduce enterohepatic drug metabolism and clearance - Rui Xue Zhang; Weijia Lu; Xu Yan; Xudong Deng; Runrun Wan; Zhejun Song; Jiayan Liang; Xue-Ting Wang; Tingting Cao; Yan Chen; Paul K. H. Tam (Drug Delivery and Translational Research, 2026)

Vitamin D receptor suppresses pulmonary fibroblast activation by downregulating the TGF-β1/Smad signaling pathway - Jialai Yang; Tangbing Xu; Rui Xu (Histochemistry and Cell Biology, 2026)

Multi-Feature and Multi-Step Monthly Rainfall Forecasting with the Hybrid VMD-LSTM-CATNet Model in Diverse Climatic Regions - Man-Hong Fan; Xiao-Ying Ma; Shi-Qi Xu; Rui-Lin Fu; Zhong-Xing Tao (Water Resources Management, 2026)

Integrating Machine Learning and Petrophysical Data for 3D Ore Body Modeling: A Case Study of the Bayan Obo Deposit - Shupeng Lu; Ya Xu; Rui Guo; Song Huang; Qianwen Zhang; Yonggang Zhao; Yun Liu; Jian Wang; Liang Zhao (Pure and Applied Geophysics, 2026)

Clostridium dalinum: A Novel Lactic Acid Bacterium with Excellent Antioxidant and Anti-inflammatory Functions Through NF-κB, Keap1-Nrf2-ARE Signaling Pathways - Zheng-Qiang Li; Rui Li; Wei Deng; Rui An; Ping Ma; Jun Li; Rong She; Xiao-Yan Yang; Xu Yang; Wen Xiao (Probiotics and Antimicrobial Proteins, 2026)

Research progress on quorum-quenching strategies for membrane biofouling control - Hongwei Wu; Kuo Yang; Yifan Gao; Rui Xu; Yuzhang Feng; Yinning Wang; Huimin Lin; Siqi Hu; Gege Tian; Jiaying Li; Pingfeng Yu; Bing Zhang (ENGINEERING Environment, 2026)

Tracking the eyes to track decline: Global eye movement similarity as a novel neuropsychological marker of mild cognitive impairment - Zhan Wang; Hong-Zhou Xu; Fang Fang; Xue-Rui Peng; Ying-Chen Liu; Zhi-Jun Zhan; Jing Yu (GeroScience, 2026)

Fungal diversity associated with Ulva pertusa and its response to cAMP and light - Rui Guo; Yinping Song; Weicheng Xu; Naiyun Ji (Journal of Oceanology and Limnology, 2026)

Fe/CeMnOX Catalysts with Mechanistically Decoupled Redox Promotion and Sulfation Resistance for Low-Temperature NH3-SCR - Shuya Rui; Yaliang Ren; Zhen Ye; Binghui Wu; Zhehao Xu; Anton Nikiforov; Zhiping Ye (Water, Air, & Soil Pollution, 2026)

Tree of life and conservation of gymnosperms in China - Chang-Wang Ma; Dan Xie; Hong Du; Kai-Yuan Huang; Yuan-Yuan Feng; Zhou-Rui Wei; Xin-Quan Liu; Cheng-Ru Li; Jing-Jing Sun; Xiao-Xin Wei; Zhi-Heng Wang; Wei-Hua Xu; et al. (Science China Life Sciences, 2026)

Stable soil aggregates and complex microbial networks enhances soil quality in saline-alkali agroecosystem - Bangyan Zhang; Jinmin Wu; Rui Bu; Xiaoli Zhang; Xiaolong Bai; Lei Li; Meilin Lin; Yifei Zhang; Xing Xu; Bin Wang (Plant and Soil, 2026)

Phosphorus fertilization shapes rhizosphere beneficial microbial communities and soil–plant relations in arid cotton fields of Xinjiang, China - Bin Peng; Shuai Zhao; Cong-Rui Liu; Wen-Xuan Mai; Na Zhou; Ping Zhang; Shu-Ying Wang; Xu Liu; Bao-Zhan Wang; Chang-Yan Tian (Plant and Soil, 2026)

Hidden potential of rare root endophytes in native plants for phytoremediation in antimony mine tailings - Hanbing Gao; Zhaohui Guo; Shikai Li; Chi Zhang; Min Shen; Xiao He; Rui Xu (Plant and Soil, 2026)

Assessing the disease burden of opioid use disorder in western europe: trends, gender differences, and future directions - Dingwen Xu; Rui Zhang; Jingjing Li; Jijun Wu; Zhe Yang (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Diagnostic Value of Fast Stroke Imaging for Salvageable Brain Tissue and Collateral Circulation in Stroke Patients - Dongxue Wang; Shuang Liang; Zhongzhen Yue; Ye Tian; Jing Zhang; Liyu Qiao; Rui Li; Junqiang Xu; Rui Chen; Fanxiang Meng; Yichao Wang (Journal of Medical and Biological Engineering, 2026)

Rural Community Resilience to Drought and Sustainable Development in Inner Mongolian Plateau, China - Wenlong Li; Rui Xu; Haiying Lin; Fujia Li (Chinese Geographical Science, 2026)

Molecular characterization of a novel partitivirus from quinoa (Chenopodium quinoa) in China - Wenqi Mao; Jiajia Lin; Zhongtian Xu; Penghuan Rui; Xinxin Fang; Hongying Zheng; Yuwen Lu; Jianping Chen; Fei Yan; Guanwei Wu (Archives of Virology, 2026)

Identification of disease-associated gene expression signatures for mechanistic insights and drug prediction in dilated cardiomyopathy-induced heart failure - Wei Yu; Shuai Xu; Xin Tan; Hangyao Zhang; Ruohan Ma; Yiyao Zeng; Anchen Xu; Honghui Tang; Qin Rui; Yahui Song; Yafeng Zhou (Molecular and Cellular Biochemistry, 2026)

Distinct ecophysiological characteristics of two genetically similar vibriophages - Wenqing Li; Runqi Zhu; Keming Shi; Huiyu Ding; Shiying Ren; Song Xu; Jing Zhao; Nianzhi Jiao; Yunlan Yang; Rui Zhang (Marine Life Science & Technology, 2026)

Chebulagic acid targets FBXO38 to enhance natural killer cell-mediated anti-tumor immunity in lung adenocarcinoma - Xiwen Hu; Rui Sha; Feiran Yang; Jinwen Chai; Bin Liu; Xiaoqing Xu (Human Cell, 2026)

Joint Characterization and Stability Analysis: Measurement Techniques and Engineering Implications - Rui-yang Bi; Chao-shui Xu; Zu-pu Xuan; Jian Zhou; Kun Du (Rock Mechanics and Rock Engineering, 2026)

ADAM17 Supports Disinhibition of Pre-sympathetic Glutamatergic Neurons Through Microglial Chemotaxis - Jiawei Wang; Zihan Qiu; Yue Han; Hanxue Wu; Miao Yuan; Yan Liu; Huichao Wang; Shenglan Yuan; Dengfeng Gao; Lina Sun; Xingjuan Chen; Eric Lazartigues; et al. (Neuroscience Bulletin, 2026)

Mechanistic Investigation of TSPO-Mediated Dysregulation of Mitochondrial Copper Homeostasis in Microglia and its Role in Perioperative Neurocognitive Disorders - Youli Fu; Jiahe Lian; Yinglong Liu; Yongxin Liu; Zihan Xu; Haoran Fan; Yongliang Zhu; Yingxia Liang; Lina Sun; Rui Zhang (Molecular Neurobiology, 2026)

Curcumin Ameliorates Depressive-like Behaviors by Modulating mGluR2/PGC-1α-Mediated Glutamatergic Homeostasis and Mitochondrial Function - Liping Xu; Deyun Jiang; Lujing Yang; Conghua Ji; Rong Bai; Yirun Xu; Tian-Rui Xu (Molecular Neurobiology, 2026)

Xinshuaining preparation ameliorates doxorubicin-induced cardiac injury in heart failure rats by regulating gut microbiota - Qian Nie; Jue Zhao; Sattar Haseeb; Siwei Deng; Xin Zhang; Rui Wang; Xu Luo; Wen Xie (Drug Delivery and Translational Research, 2026)

Automatic Image Co-registration of Carotid Angiography and Intravascular Optical Coherence Tomography Based on Machine Learning Method: A Pilot Feasibility Study - Hui Xu; Jia-Nan Li; Yan Xu; Jun-Ren Ma; Kang Zong; Rui Zhu; Yi-Hui Cao; Peng-Fei Yang; Rui Zhao; Jian-Min Liu (Annals of Biomedical Engineering, 2026)

Computational Investigation of Dicyanoisophorone-Based Fluorophores: Substituent and Site Effects - Yating Ding; Zhengze Zhang; Rui Wu; Ying Xu; Qu Zhang; Zhao Liu; Junqiang Lei (Journal of Fluorescence, 2025)

Integration of transcriptome and metabolome analysis reveals that alternative splicing of TT8 modulates anthocyanin biosynthesis in postharvest blood orange stored at moderate temperature - Wang Jianhui; Xu Rui; Guo Weiqing; Li Zhihong; Liu dayu; Li Jingjing; Li Dagang; Chen Ying (Plant Molecular Biology, 2025)

Interplay between Nrf2 and ROS in regulating epithelial-mesenchymal transition: implications for cancer metastasis and therapy - Yi Xu; Shuning Hu; Rui Chen; Sheng Xu; Guangyang Yu; Lili Ji (Molecular Biology Reports, 2025)
Epithelial-mesenchymal transition (EMT), including developmental (Type I), wound healing (Type II), and pathological (Type III) subtypes, constitutes a critical driver of cancer metastasis. This review analyzes the redox interplay between nuclear factor erythroid 2-related factor 2 (Nrf2) and reactive oxygen species (ROS) in EMT regulation and cancer progression. Nrf2 maintains redox homeostasis through antioxidant gene activation while paradoxically promoting tumor survival and drug resistance via Keap1-dependent degradation and phosphorylation-mediated stabilization. ROS generated through mitochondrial and NADPH oxidase pathways exhibit dual functionality: moderate levels activate EMT transcription factors to drive metastasis and cancer stem cells (CSCs) plasticity, whereas excessive ROS induce apoptosis and ferroptosis. While Nrf2 typically suppresses EMT through ROS neutralization and epithelial integrity preservation, chronic Nrf2 activation in CSCs paradoxically sustains metastatic potential through redox buffering. This synthesis delineates the spatiotemporal regulation of Nrf2-ROS-EMT networks across tumor microenvironments, emphasizing therapeutic opportunities through redox balance modulation and pathway-specific Nrf2 inhibition in advanced malignancies.

Time trend of urine metal levels in preschool children in the electronic waste recycling area and its association with hemoglobin levels - Rongyi Kang; Jieting Chen; Kaihui Li; Rui Sun; Jian Zhang; Chenxu Dai; Xijin Xu; Bo Xie; William W. Au; Lei Tan; Xia Huo (International Archives of Occupational and Environmental Health, 2025)

CFD–DEM and Experimental Investigation of Seepage Behavior at Soil–Structure Interfaces - Xue-min Yang; Zeng-guang Xu; Jun-rui Chai; Cheng Cao; Chao-wei Sun; Gang Li (Geotechnical and Geological Engineering, 2025)

Multi-omics based consensus subtypes, development of prognostic signature, and identification of INHBB as a potential therapeutic target in colorectal cancer - Xu Wang; Yuanmin Xu; Rui Sun; Sheng Wang; Xiang Wei (Functional & Integrative Genomics, 2025)

Comparative pan-genome analysis of Huperzia and Phlegmariurus and transcriptomics reveals thermal adaptation in Huperzia - Muzi Li; Yazhu Wu; Haibo Li; Zhongnian Zhang; Rui Qin; Jiahao Wen; Yeqin Xu; Chengcheng Bao; Dekai Wang (Functional & Integrative Genomics, 2025)

CRP and HNF1A collaborate to regulate the progression of laryngeal cancer through the Wnt signaling pathway - Zhigang Zhao; Xiaojing Zhu; Jinyuan Xu; Penglong Song; Yanan Sun; Zhenming Yang; Li Wang; Jiarui Zhang; Rui Zhao; Xiaoxue Chen; Wenjing Li; Linli Tian; et al. (Functional & Integrative Genomics, 2025)

Integrated multi-omics analysis of UL16-binding protein 2 as a prognostic and immunotherapy biomarker for colorectal cancer - Xin-Yang Qu; Yong Xu; Rui-Min Wu; Gao-Chun Xiao; Ping-Feng Wang; Jin Xie; Xu-Sheng Liu (Functional & Integrative Genomics, 2025)

Immobilization of arsenic and antimony by silica-Fe (hydr)oxides composite: investigation of potential ecological effects on the soil microbial environment - Rui Xu; Yaxin Tian; Qian Li; Guangfei Qu; Lang Liao; Zhe Yin; Zhenguo Wu; Yuqi Han; Yan Zhang; Yongbin Yang; Dongbin Liu; Haiyan Yan; et al. (Environmental Geochemistry and Health, 2025)

GSANet: research on EEG decoding based on graph attention and self attention in auditory attention detection - Yuanlin Dong; Rui Dai; Tiancheng Xie; Ke Xu; Liya Huang (Cognitive Neurodynamics, 2025)

Enhancing performance of SSVEP-based visual acuity via exploiting subject-specific information - Xiaowei Zheng; Boyu Wen; Xin Yan; Guanghua Xu; Rui Zhang (Cognitive Neurodynamics, 2025)

Emotion recognition of CNN bidirectional long short-term memory with center and Softmax loss function (CNN-BiLSTM-CS) EEG -based - Xiaodan Zhang; Shuyi Wang; Yige Li; Kemeng Xu; Rui Zhao; Wei Wei (Cognitive Neurodynamics, 2025)

Classification for Alzheimer's disease and frontotemporal dementia via resting-state electroencephalography-based coherence and convolutional neural network - Rundong Jiang; Xiaowei Zheng; Jiamin Sun; Lei Chen; Guanghua Xu; Rui Zhang (Cognitive Neurodynamics, 2025)

A review of the low-field NMR technique for analyzing the state of water in clayey soils - Yingyao Qin; Liang Wang; Xiaolong Ma; Yong Wan; Rui Xu; Houzhen Wei (Bulletin of Engineering Geology and the Environment, 2025)

The protective role of HINT2 in hypoxia injury of neuroblastoma cells and its regulatory mechanism on MCU-MICU1 pathway - Shao Rui; Zhang Lilong; Geng Yannan; Xu Tiantong (Neurophysiology, 2025)

Heavy Magnesium Isotope Evidence for a Key Role of Serpentinite-Derived Fluids in Arc Magmatism - Rui An; Yongsheng He; Shan Ke; Guochun Zhao; Aiying Sun; Yang Wang; Hongsheng Xu (Journal of Earth Science, 2025)

Critical processes controlling the formation of visible gold in the giant Jiaodong gold province: Constraints from microtextural and geochemical analyses by SEM, TOF–SIMS, and LA-(MC)-ICP-MS - Hong Wang; Ting-Guang Lan; Lang-Ye Zhao; Hong-Rui Fan; Zhan-Ping Li; Huan-Long Hu; Zi-Qi Xu; Hong-Wei Peng; Lei Shu (Acta Geochimica, 2025)

Deep structure of the middle segment of the Bangong-Nujiang Suture Zone based on aerogravity and aeromagnetic anomalies, Qinghai-Tibet Plateau - Bao-bao Cao; Dao-qing Zhou; Yan-yan Wei; Rui Zhao; Qiao-juan Yan; Lei Xu; Di-shuo Zhang (Applied Geophysics, 2025)

Research on Acoustic-Electrical Integrated Technology in Geothermal Resource Exploration, Development and Monitoring - Feng Chu; Rui Xu; Rong-hua Zhang; Yi-guo Xue; Deng-rui Wu; Lin-zhi Lang; Shu-ge Liu; Jing-kai Qu (Applied Geophysics, 2025)

Arabidopsis Dynamin-Related Protein 1a is important for cell plate fusion with parent cell plasma membrane in cytokinesis during pollen mitosis I - Nan Wang; Qingchen Rui; Haoyue Xu; Xiaoyun Tan (Planta, 2025)

Investigation of the mechanism of Dan Zhi Qing’e Formula for treating menopausal hot flashes using UHPLC-Q-TOF MS and network pharmacology - Xinyu Li; Xinyu Liu; Minghui Cai; Shuang Wei; Rui Wang; Nanjian Xu; Jingtian Qu; Yuming Wang (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

The m6 A modification of CDKN2 A inhibites ferroptosis and affects the resistance of cervical squamous cell carcinoma to cisplatin - Xiang Yong; Xifeng Xu; Xiaoping Zhang; Rui Song; Huaiyuan Hu; Zhen Li; Yanzi Qin (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

The Impact of the Combined Application of Zinc and Selenium on the Physiological Mechanisms and Mercury Accumulation in Rice Under Mercury Stress - Qiu Huang; Jing Liu; Wanyu Li; Anqi Xu; Rui Wu; Fanxin Qin (Bulletin of Environmental Contamination and Toxicology, 2025)

S-Ketamine Alleviates Anxiety-Induced Chronic Postoperative Pain by Affecting Glucose Metabolism of Striatal Microglia in a Rat Model - Rui Xu; Wei Zhu; Xuan Xu; Yue Yao; Qi Liu; Yan Yang; Yulin Huang; Zhengliang Ma (Journal of Neuroimmune Pharmacology, 2025)

A novel method for predicting debris flow hazard: a multi-strategy fusion approach based on the light gradient boosting machine framework - Tianlong Wang; Qi Ge; Tianxing Ma; Hao Chen; Rui Luo; Xu Wang; Keying Zhang; Zhaowei Chu; Xiaohui Ni; Hongyue Sun (Stochastic Environmental Research and Risk Assessment, 2025)

Zinc and manganese impact on cabbage (Brassica rapa) cadmium tolerance: comparative transcriptomic and metabolomic study - Wanyu Li; Fanxin Qin; Banglin Luo; Qiu Huang; Anqi Xu; Rui Wu (Plant and Soil, 2025)

Ratiometric core/shell Nanosensors for Simultaneously Measuring Mitochondrial ATP Production and Oxygen Consumption in Living Cells - Rui Jiang; Ying Lian; Enlai Yang; Ying Xu; Jiahao Liang; Yang Yang; Nianhong Wang; Xu-dong Wang (Phenomics, 2025)

Application of platelet-rich plasma lysate combined with hyaluronic acid microneedles for the treatment of alopecia - Zhengxin Suo; Yingcan Xu; Along Zhang; Ye Cao; Jiaxin Liu; Hong Wang; Rui Zhong (Drug Delivery and Translational Research, 2025)

Flavonoids as Signals Mediate Plant-nematode Communication Through Regulating Nematode Perceptual Ability - Xiang-Yu Zhang; Rui Yuan; Yaseen Ullah; Xu-Dong Li; Hao-Ran Li; Wei Zhang (Journal of Chemical Ecology, 2025)

Jingfang granule extends lifespan and healthspan in Caenorhabditis elegans: insights from RNA-seq analysis of genetic mechanisms - Taili Zhao; Yunhua Hou; Chuanjiao Feng; Rui Zhao; Honghua Li; Peipei Zhao; Mengmeng Wang; Jingli Ren; Yiwei Meng; Kuidong Xu; Jia Liu; Xin Yin; et al. (Biogerontology, 2025)

Acute high-altitude hypoxia induced NLRP3 inflammasome activation in pulmonary artery smooth muscle cells by BMAL1 targeting mitochondrial VDAC1-mediated MtDNA leakage - Si-Yuan He; Ying-Rui Bu; Jin Xu; Yu-Meng Wang; Tian-Xi Feng; Pei-Jie Li; Yi-Xiao Zhao; Yi-Ling Ge; Man-Jiang Xie (Apoptosis, 2025)

Oral bioavailability property prediction based on task similarity transfer learning - Chen Zeng; Chengcheng Xu; Yingxu Liu; Yunya Jiang; Lidan Zheng; Yang Liu; Yanmin Zhang; Yadong Chen; Haichun Liu; Rui Gu (Molecular Diversity, 2025)

Customized microbial inoculants enhance rhizosheath functionality and drive ecosystem restoration in desertified grasslands - Qiqi Han; Weimeng Liu; Yingjie Jiang; Pengyuan Yang; Zixuan Wang; Ziyuan Yan; Zhuo Zhang; Rui Xu; Hui Tang; Guixia Liu (Plant and Soil, 2025)

Structural changes and Cd immobilization mechanism of Solanum nigrum pectin in root and leaf cell walls under Cd stress - Yue Teng; Huibo Sun; Yi Xiao; Jiawei Hu; Rui Xu; Longteng Zhi; Hongyan Yu (Plant and Soil, 2025)

Effect of fulvic acid on aggregate characteristics and humus composition in saline-alkali soil - Rui Cai; Yaru Guo; Yanjie Li; Ling Li; Susu Xu; Ping Gong; Pengfei Li; Hongguang Liu (Plant and Soil, 2025)

The degradation of lignin and cellulose in typhoon-induced unsenescent leaf litter depends greatly on functional strategies among tree species - Rui Cao; Huaibin Wang; Lifeng Wang; Zhuang Wang; Zhihui Wang; Qin Wang; Naiyue Lv; Xu Wang; Wanqin Yang (Plant and Soil, 2025)

Endothelial Cell Integrin α6 Regulates Vascular Remodeling Through the PI3K/Akt-eNOS-VEGFA Axis After Stroke - Bing-Qiao Wang; Yang-Ying Duan; Mao Chen; Yu-Fan Ma; Ru Chen; Cheng Huang; Fei Gao; Rui Xu; Chun-Mei Duan (Neuroscience Bulletin, 2025)

Dynamic Transcriptome Analysis Uncovers Key Regulatory Genes During Stem Elongation Stages in Wheat - Rui Cao; Yaoyu Chen; Hongyong Dai; Zhencheng Xie; Lifen Wu; Zhan Li; Yuxin Yang; Lichao Zhang; Xu Liu; Xiuying Kong; Chuan Xia (Journal of Plant Growth Regulation, 2025)

Phylogenetic and toxicogenomic profiling of CYPomes to elucidate convergent and divergent insecticide resistance profiles in three rice planthopper species - Kai Lin; Hongxin Wu; Zhongsheng Li; Zichun Zhong; Liuyan He; Yujing Guo; Jie Zhang; Xiaoxia Xu; Wenqing Zhang; Fengliang Jin; Rui Pang (Journal of Pest Science, 2025)

MLWNNR: LncRNA-Disease Association Prediction with Multi-Kernel Learning-Driven Weighted Nuclear Norm Regularization - Guo-Bo Xie; Hao-Jie Xu; Guo-Sheng Gu; Zhi-Yi Lin; Jun-Rui Yu; Rui-Bin Chen (Interdisciplinary Sciences: Computational Life Sciences, 2025)

Using Interactive Multi-Media Panorama Virtual Reality to Balance Heritage Science, Education and Conservation At Zhoukoudian, Fangshan UNESCO Global Geopark - Jun-Ting Qiu; Tong-Yu Zhang; Lixian Tian; Xin-Min Rui; Hong-Xu Mu; Liang Qiu; Long-Xin Xu (Geoheritage, 2025)

Sequence of middle-lower Ordovician in Shunbei area of Tarim Basin, China, and its geological significance - Rui Xiong; Heng Fu; Yong Li; Caizhu Xie; Ronggang Wang; Shaoze Zhao; Chuan Xu; Chongyang Xiao (Carbonates and Evaporites, 2025)

Experimental and numerical investigation of gas preferential flow through geosynthetic clay liner overlap joint in landfill final cover system - Lin Qin; Fusheng Zha; Rui Xu; Songyu Liu; Abdelmalek Bouazza; He Huang; Qiao Wang (Bulletin of Engineering Geology and the Environment, 2025)

Nested MPI-CWRF dynamical downscaling and future projections of summer extreme precipitation changes in China - Huan Li; Fengxue Qiao; Nan Wei; Haoran Xu; Rui Wang; Fulin Jiang; Guimin Lou; Jia Zhao; Qingyu Yang (Frontiers of Earth Science, 2025)

Mesenchymal Stromal Cells and Graft-versus-Host Disease: Preclinical and Clinical Studies - Rui Wang; Jingkang Xiong; Qing Xu; Ya Zhou; Shijie Yang; Qingxiao Song; Xiaoqi Wang; Xi Zhang (Stem Cell Reviews and Reports, 2025)

Nicotianamine facilitates zinc translocation from roots to shoots in the nickel hyperaccumulator Odontarrhena chalcidica - Teng-Hao-Bo Deng; Ya-Zhou Wang; Bing-Lan Mo; Ting Liu; Lei Li; Ye-Tao Tang; Dian Wen; Yong-Dong Huang; Sheng-Sheng Sun; Xu Wang; Rui-Ying Du; Jean-Louis Morel; et al. (Plant and Soil, 2025)

Droplet-vitrification for cassava shoot tip cryopreservation: protocol optimization and histological observation for rapid shoot tip recovery - Min-Rui Wang; Xiu-Qing Miao; Yun-Liu Fu; Lang-Xin Chen; Xiao-Bing Wang; Qing-Quan Yang; Li Xu; Zhiying Li (Plant Cell, Tissue and Organ Culture (PCTOC), 2025)

Numerical Modeling of Permeability Sensitivities Based on Characteristics of Heterogeneous Coal Structure Reservoirs - Rui Wang; Kun Zhang; Guofu Li; Liangwei Xu (Natural Resources Research, 2025)

Geochemical Characteristics of Natural Gas in the Upper Permian Reservoir of the Eastern Sichuan Basin, China: Implication of Multiple Sources Mixing - Lu Xu; Rui Liu; Yufeng Tang; Kangbin Zhang; Liang Feng; Xiucheng Tan; Fei Liu; Dingchuan Jiang (Journal of Earth Science, 2025)

Elucidating the anti-aging bioactive compounds and mechanisms of Jingfang Granules formula based on network pharmacology and Caenorhabditis elegans - Rui Zhao; Taili Zhao; Tingting Shi; Chuanjiao Feng; Honghua Li; Ying Xu; Qingqing Zhang; Xin Yin; Jingchun Yao; Guimin Zhang; Xuekui Xia (Biogerontology, 2025)

Retraction Note to: miR-365b-3p adsorbed by HCG18 inhibits the proliferation and angiogenesis of stomach adenocarcinoma by downregulating STC1 - Hui Li; Jian Song; Rui Hou; Yingdong Cao; Huaili Xu (Molecular & Cellular Toxicology, 2025)

Rapeseed transcription factor BnaC9bHLH35 promotes root growth and improves nitrogen use efficiency under low nitrate conditions - Qin-Xin Fang; Haokun Cheng; Zhongni Ma; Qiuyan Xu; Huanpeng Wang; Yunru Yan; Mengting Sun; Rui Wang; Wenlong Liu; Saeed Ullah; Yuhang Fan; Chunchun Huang; et al. (Theoretical and Applied Genetics, 2025)

Inversion of Stress Redistribution Based on Focal Mechanism Solutions: A Case Study of the Dongtan Coal Mine - Kai Zhan; Hao Luo; Rui Xu; Xiaotao Wen; Cong Wang (Rock Mechanics and Rock Engineering, 2025)

Enhanced Microseismic Event Localization in Coal Mines Using the EDDI-Based Cross-Correlation Stacking Method - Kai Zhan; Xuben Wang; Xiaotao Wen; Rui Xu; Chao Kong; Chao Wang (Rock Mechanics and Rock Engineering, 2025)

Variations in lunar regolith mineralogy along the Chang’e-4, Yutu-2 traverse: Combined effects of ejecta sedimentation and subsequent modification - Zhenxing Zhao; Yazhou Yang; Dijun Guo; Yang Liu; Feng Zhang; Xing Wu; Rui Xu; Zhiping He; Yongliao Zou (Science China Earth Sciences, 2025)

Human dental follicle cell-derived conditioned media enhance periodontal regeneration by regulating the osteogenic differentiation and inflammation of periodontal ligament stem cells and macrophage polarization - Yichen Gao; Xianyi He; Yuyao Deng; Xia Wang; Jie Shen; Wei Xu; Rui Cai; Xiaorong Lan; Junliang Chen; Yun He (Molecular and Cellular Biochemistry, 2025)

Functional shift in soil microbiome with decline in photosynthetic carbon input signifies rapid decrease of soil organic carbon during alpine grassland degradation - Minghua Song; Rui Pang; Yuqiang Tian; Yikang Li; Guiqiang Wang; Xingliang Xu (Biology and Fertility of Soils, 2025)

Molecular characterization of a novel non-segmented double stranded RNA mycovirus infecting the phytopathogenic fungus Botryosphaeria dothidea - Shunpei Xie; Yanan Zhang; Guoqing Xing; Qinzhou Ma; Yashuang Guo; Rui Zang; Chao Xu; Haiyan Wu; Haiqiang Li; Meng Zhang (Archives of Virology, 2025)

Ferroptosis: Disease Associations and Therapeutic Target Exploration - Hailing Wang; Liwei Jia; Rui Yin; Shujun Xu; Xin Meng (Journal of Molecular Neuroscience, 2025)

Epigenetics in the modern era of crop improvements - Yan Xue; Xiaofeng Cao; Xiangsong Chen; Xian Deng; Xing Wang Deng; Yong Ding; Aiwu Dong; Cheng-Guo Duan; Xiaofeng Fang; Lei Gong; Zhizhong Gong; Xiaofeng Gu; et al. (Science China Life Sciences, 2025)
Epigenetic mechanisms are integral to plant growth, development, and adaptation to environmental stimuli. Over the past two decades, our comprehension of these complex regulatory processes has expanded remarkably, producing a substantial body of knowledge on both locus-specific mechanisms and genome-wide regulatory patterns. Studies initially grounded in the model plant Arabidopsis have been broadened to encompass a diverse array of crop species, revealing the multifaceted roles of epigenetics in physiological and agronomic traits. With recent technological advancements, epigenetic regulations at the single-cell level and at the large-scale population level are emerging as new focuses. This review offers an in-depth synthesis of the diverse epigenetic regulations, detailing the catalytic machinery and regulatory functions. It delves into the intricate interplay among various epigenetic elements and their collective influence on the modulation of crop traits. Furthermore, it examines recent breakthroughs in technologies for epigenetic modifications and their integration into strategies for crop improvement. The review underscores the transformative potential of epigenetic strategies in bolstering crop performance, advocating for the development of efficient tools to fully exploit the agricultural benefits of epigenetic insights.

The nickel hyperaccumulator Odontarrhena chalcidica (Brassicaceae) preferentially takes up zinc over nickel - Ya-Zhou Wang; Ke-Rui Geng; Bing-Lan Mo; Ting Liu; Ye-Tao Tang; Dian Wen; Fu-Rong Li; Xu Wang; Lei Li; Rui-Ying Du; Antony van der Ent; Teng-Hao-Bo Deng; et al. (Plant and Soil, 2025)

Deep Learning-Based Surrogate-Assisted Intelligent Optimization Framework for Reservoir Production Schemes - Lian Wang; Hehua Wang; Liehui Zhang; Liang Zhang; Rui Deng; Bing Xu; Xing Zhao; Chunxiang Zhou; Li Fan; Xindong Lv; Junda Wu (Natural Resources Research, 2025)

Olaparib reverses prostate cancer resistance to Rapamycin by promoting macrophage polarization towards the M1 phenotype - Kai Ye; Gang Shi; Jian Xu; Kunyan Qiao; Qinghai Dai; Zhixiao Huo; Yu Cao; Wei Liu; Yue Hu; Lihua Yan; Yu Zhu; Ping Li; et al. (Molecular and Cellular Biochemistry, 2025)

Development of novel caffeic acid derivatives as multifunctional agents for the treatment of AD - Kerong Hu; Jing Yang; Qiyao Zhang; Xinxin Wang; Yujie Xu; Yuxin Zhang; Zhenghuai Tan; Wenmin Liu; Rui Chen; Zhipei Sang (Medicinal Chemistry Research, 2025)

Helicobacter pylori VacA-induced gastric mucosal atrophy: a comparative analysis with other forms of atrophic gastritis - Yang-Kun Wang; Wen-Rui Chen; Ling-Yan Lu; Ying-Ying Li; Rui-Kun Qiu; Chao-Ya Zhu; Fa-Shun Zhang; Su-Nan Wang; Si-Liang Xu (Journal of Molecular Histology, 2025)

Investigation of scale effect on shear behaviors of natural rock joints using the overlapping sampling method - Qinkuan Hou; Shuhong Wang; Rui Yong; Minna Xu; Wenpan Sun; Furui Dong (Bulletin of Engineering Geology and the Environment, 2025)

Integrative transcriptomic and physiological analyses uncover mechanisms by which arbuscular mycorrhizal fungi mitigate salt stress in sugar beet - Zeyuan Cui; Xiaodong Li; Pingan Han; Rui Chen; Yinzhuang Dong; Gui Geng; Lihua Yu; Jiahui Liu; Yao Xu; Yuguang Wang (Mycorrhiza, 2025)

The sedimentological heterogeneities and responses to controlling factors in Toutunhe Formation of Xiayan Rise, Junggar Basin - Nai-xiang He; Xiang Li; Ya-jie Ding; Rui Qi; Gang Xu; Zi-jian Han; Chao Hou; Lei Xie (Applied Geophysics, 2025)

Ecological security and structural optimization of land space in the Pearl River Delta Urban Agglomeration: an approach based on the footprint family - Cong Huang; Jun Liu; Hanyu Yin; Zhonghao Zhang; Wei Cao; Wenfang Tan; Xufeng Fei; Chen Xu; Lumeng Liu; Jiali Chen; Kai Li; Rui Xiao (Environment, Development and Sustainability, 2025)

Prevalence of malnutrition among adult inpatients in China: a nationwide cross-sectional study - Yan Liu; Chunhua Song; Xue Wang; Xianghua Ma; Pianhong Zhang; Gaiyun Chen; Zhenqian Cheng; Juying Liu; Ying Yao; Wenjun Ma; Zengning Li; Ping Sun; et al. (Science China Life Sciences, 2025)

Nitrogen addition and plant functional type mediate the mesofauna-driven litter element release of subtropical forest - Jihong Li; Qun Liu; Rui Yin; Chengming You; Li Zhang; Han Li; Lixia Wang; Hongwei Xu; Lin Xu; Sining Liu; Bo Tan; Zhenfeng Xu (Plant and Soil, 2025)

Dynamic transcriptomics and physiological insights reveal multi-tissue salt adaptation mechanisms in Amaranthus hypochondriacus across stress gradients - Qian Xu; Jinxin Gan; Zhikang Zhou; Tao Zhou; Rui Lu; Ningfang Liu; Longxing Hu (Plant Cell Reports, 2025)

The tumor suppressor SALL2 opposes chemotherapeutic resistance in breast cancer - Qiji Li; Chenxin Li; Yuhao Zhang; Zihan Zheng; Yun Wang; Yingqian Yang; Qingqing Zhu; Rui Wang; Wanhui Xu; Chengming Zhu; Qin Tian; Meng Wang; et al. (Molecular and Cellular Biochemistry, 2025)

Source identification of polycyclic aromatic hydrocarbons (PAHs) in river sediments within a hilly agricultural watershed of Southwestern China: an integrated study based on Pb isotopes and PMF method - Fen Xu; Chunmei Jiang; Qiang Liu; Rui Yang; Weiwei Li; Yao Wei; Linlin Bao; Hongjin Tong (Environmental Geochemistry and Health, 2025)

Monthly variations of the spring greenness response across boreal Eurasia to the preceding wintertime northern annular mode during 1982–2022 - Jing Li; Weiming Zeng; Ruichen Lin; Zhiqing Xu; Xilin Xie; Feng Su; Rui Zhao; Anmin Duan (Climate Dynamics, 2025)

Grazing and Enclosure Alter the Vertical Distribution of Bacterial Communities in Different Microhabitats of Wetlands Along the Xilin River - Xiaoai Cao; Yating Tian; Huamin Liu; Hongbo Yu; Feng Niu; Rui Zhang; Zhichao Xu; Yi Zhuo; Lu Wen; Dongwei Liu; Lixin Wang (Wetlands, 2025)

Driving analysis and prediction of COD based on frequency division - Mei Li; Kexing Chen; Deke Wang; Yilin He; Rui Xu (Stochastic Environmental Research and Risk Assessment, 2025)

Unraveling Neurotoxicity Discrepancies: Comparative In vitro and In vivo Analysis of Colistin and Polymyxin B and the Underlying Mechanisms - Rui Yang; Debiao Xiang; Fang Yuan; Yuan Yang; Pengkai Wang; Bing Xu; Xin Li (Molecular Neurobiology, 2025)

Fatty acid binding protein 4 knockdown improves fetal development in rats with gestational diabetes mellitus through modulating autophagy mediated by the PTEN/Akt/mTOR signaling pathway - Fanglei Yang; Yifan Mao; Bin Tang; Rui Xu; Feiyun Jiang (Journal of Molecular Histology, 2025)

Association between sleep quality and serum biomarkers among long-term hot spring bathers: a cross-sectional study - Fen Yang; Yue Zou; Ying-ying Zhang; Hong-xia Li; Yi-hang Xu; Bao-chao Zhang; Lin-xuan Liao; Meng-xi Cao; Rui-xue Wang; Yuan Yuan; Yun Zhou; Da-yong Zeng; et al. (International Journal of Biometeorology, 2025)

Pharmacological Inhibition of TXNRD1 by a Small Molecule Flavonoid Butein Overcomes Cisplatin Resistance in Lung Cancer Cells - Rui Yang; Shibo Sun; Qiuyu Zhang; Haowen Liu; Ling Wang; Yao Meng; Na Chen; Zihan Wang; Haiyan Liu; Fengyun Ji; Yan Dai; Gaohong He; et al. (Biological Trace Element Research, 2025)

Knockdown of SETD5 Inhibits Colorectal Cancer Cell Growth and Stemness by Regulating PI3K/AKT/mTOR Pathway - Xiaohua Zhou; Wenqiang Chen; Duanming Zhuang; Guangqi Xu; Yongqiang Puyang; Hongqing Rui (Biochemical Genetics, 2025)

Nuclear receptor coactive 4-mediated ferritinophagy: a key role of heavy metals toxicity - Wan-Xue Xu; Xue Wen; Yi-Tong Fu; Jie Yang; Han Cui; Rui-Feng Fan (Archives of Toxicology, 2025)

Reconstruction of well-logging data using unsupervised machine learning-based outlier detection techniques (UML-ODTs) under adverse drilling conditions - Jing-Rui Chen; Rui-Zhao Yang; Ting-Ting Li; Yun-Di Xu; Zhi-Peng Sun (Applied Geophysics, 2025)

GFFMNet: Prediction Method for Coal Mine Seismic Focal Mechanisms Based on GCN - Kai Zhan; Xigui Zheng; Rui Xu; Cong Wang; Ping Song (Rock Mechanics and Rock Engineering, 2025)

Bayesian Microseismic Localization Method Based on the Maximum Entropy Hamiltonian Monte Carlo Markov Chain Approach - Kai Zhan; Xuben Wang; Xiaotao Wen; Rui Xu; Chao Kong; Chao Wang (Rock Mechanics and Rock Engineering, 2025)

Functional characterization and site-directed mutagenesis of a novel UDP-glycosyltransferase from Panax japonicus var. major - Lu Mou; Yang Zhang; Yu-Xin Zhuang; Rui-Fang Ren; Ran Xu; Ling Yang; Shao-Peng Zhang; Deng-Xiang Du (Planta, 2025)

PKS1 involved in anthocyanin accumulation in red-skinned pear fruit - Lei Guo; Yuting Hao; Ying Tang; Mengjia Wu; Rui Zhai; Chengquan Yang; Lingfei Xu; Zhigang Wang (Plant Cell Reports, 2025)

Changes in Type 1 Diabetes-Associated Gut Microbiota Aggravate Brain Ischemia Injury by Affecting Microglial Polarization Via the Butyrate–MyD88 Pathway in Mice - Xianzhang Zeng; Can Ma; Wenchao Fu; Yongmei Xu; Rui Wang; Dan Liu; Lijuan Zhang; Narisu Hu; Dongmei Li; Wenzhi Li (Molecular Neurobiology, 2025)

The Impact of Different Mating Systems on Locomotion in Drosophila melanogaster - Rui Han; Jun Zhang; Ruo-Xi Wang; Jia-Xin Xu; Kai-Chen Weng; An-Xin Wang; Hao Huang; Yu-Yuan Lu; Yi-Jie Chen; Yu-Chen Wang (Journal of Insect Behavior, 2025)

Geosites Associated with Paleovolcanic Landscapes and Paleontology in Hoboksar Mongol Autonomous County, Xinjiang Uygur Autonomous Region, NW China - Hong-Xu Mu; Qing-Wei Song; Jun-Ting Qiu; Long-Xin Xu; Xin-Min Rui (Geoheritage, 2025)

Sodium-glucose cotransporter 2 inhibitors and contrast-induced nephropathy risk: a meta-analysis - Gang Fan; Lin Lin; Hong Zuo; Rui Yan; Chao Xu (European Journal of Clinical Pharmacology, 2025)

Nicotinamide riboside restores nicotinamide adenine dinucleotide levels and alleviates brain injury by inhibiting oxidative stress and neuroinflammation in a mouse model of intracerebral hemorrhage - Jing She; Hua Zhang; Hui Xu; Yan-Yan Li; Jun-Chao Wu; Rong Han; Fang Lin; Yan Wang; Rui Sheng; Jin-hua Gu; Zheng-Hong Qin (Molecular Neurobiology, 2025)
Hemorrhagic stroke is a global health problem owing to its high morbidity and mortality rates. Nicotinamide riboside is an important precursor of nicotinamide adenine dinucleotide characterized by a high bioavailability, safety profile, and robust effects on many cellular signaling processes. This study aimed to investigate the protective effects of nicotinamide riboside against collagenase-induced hemorrhagic stroke and its underlying mechanisms of action. An intracerebral hemorrhage model was constructed by stereotactically injecting collagenase into the right striatum of adult male Institute for Cancer Research mice. After 30 minutes, nicotinamide riboside was administered via the tail vein. The mice were sacrificed at different time points for assessments. Nicotinamide riboside reduced collagenase-induced hemorrhagic area, significantly reduced cerebral water content and histopathological damage, promoted neurological function recovery, and suppressed reactive oxygen species production and neuroinflammation. Nicotinamide riboside exerts neuroprotective effects against collagenase-induced intracerebral hemorrhage by inhibiting neuroinflammation and oxidative stress.

Sleep deprivation stimulates adaptive thermogenesis by activating AMPK pathway in mice - Tian-Shu Zheng; Xin-Ran Gao; Rui-Ping Xu; Yi-Fei Zhao; Zhi-Teng Yang; De-Hua Wang (Journal of Comparative Physiology B, 2025)

Spatial single-cell maps reveal ST6GAL1 promoting ovarian cancer metastasis - Lan-hui Qin; Zijian Jiang; Chongze Yang; Rui Song; Pei-yin Chen; Weihui Xu; Guanzhen Zeng; Jin-yuan Liao; Liling Long (Glycoconjugate Journal, 2025)

The STING signaling pathways and bacterial infection - Jiayi You; Ailing Xu; Ye Wang; Guangmin Tu; Rui Huang; Shuyan Wu (Apoptosis, 2025)

Assessment of Peripheral Neuropathy Using Current Perception Threshold Measurement in Patients with Spinocerebellar Ataxia Type 3 - Xia-Hua Liu; Wei Lin; Hao-Ling Xu; Mao-Lin Cui; Zhuo-Ying Huang; Ying Li; Nan-Nan Zhang; Ning Wang; Zhi-Yong Wang; Shi-Rui Gan (The Cerebellum, 2025)

From Genes to Metabolites: HSP90B1’s Role in Alzheimer’s Disease and Potential for Therapeutic Intervention - Cheng Huang; Ying Liu; Shuxin Wang; Jinjun Xia; Di Hu; Rui Xu (NeuroMolecular Medicine, 2025)

A Method for Coal Mine Seismic Network Detection Capability Calculation Based on Energy - Kai Zhan; Xiaotao Wen; Cong Wang; Chao Kong; Chao Wang; Rui Xu (Rock Mechanics and Rock Engineering, 2025)

Protective effect of SERCA2a-SUMOylation by SUMO-1 on diabetes-induced atherosclerosis and aortic vascular injury - Jinlin Liu; Shifang Xu; Bin Gao; Meng Yuan; Li Zhong; Rui Guo (Molecular and Cellular Biochemistry, 2025)

Assessment of myelination development in neonatal rats using chemical exchange saturation transfer (CEST) 7-T MRI - Rui Wang; Shuxian Xu; Fenglin Jia; Yi Liao; Jiayi Li; Jing Liu; Fengyan Zhao; Haibo Qu (Experimental Brain Research, 2025)

A fidelity evaluation model for watermarked vector maps based on improved fuzzy comprehensive evaluation and random forest - Xu Xi; Huimin Tian; Jinglong Du; Mingkang Wu; Rui Huang (Earth Science Informatics, 2025)

Dietary Iron Overload Triggers Hepatic Metabolic Disorders and Inflammation in Laying Hen - Yue Li; Lan-Xin Li; Han Cui; Wan-Xue Xu; Hong-Yu Fu; Jiu-Zhi Li; Rui-Feng Fan (Biological Trace Element Research, 2025)

Identifying the Pathogenicity of a Novel NPRL3 Missense Mutation Using Personalized Cortical Organoid Model of Focal Cortical Dysplasia - Rongrong Lu; Ying Xu; Hao Li; Man Xiong; Wenhao Zhou; Weijun Feng; Rui Zhao (Journal of Molecular Neuroscience, 2024)

Molecular intersections of traumatic brain injury and Alzheimer’s disease: the role of ADMSC-derived exosomes and hub genes in microglial polarization - Pengtao Li; Liguo Ye; Sishuai Sun; Yue Wang; Yihao Chen; Jianbo Chang; Rui Yin; Xiaoyu Liu; Wei Zuo; Houshi Xu; Xiao Zhang; Robert Chunhua Zhao; et al. (Metabolic Brain Disease, 2024)

Community of Arbuscular Mycorrhizal Fungi in the Rhizosphere Soils with Different Generations of Hybridized Progeny of Wild Erianthus arundinaceus and Sugarcane - Jin-Lian Zhang; Yi-Hao Kang; Juan Song; Huan-Ying Xu; Wei Zhang; Ying-Jie Nong; Qian Wang; Qin-Nan Wang; Ting-Su Chen; Yang-Rui Li (Sugar Tech, 2024)

Deep Learning Approach for Hydraulic Support Anomaly Detection: Utilizing Convolutional Autoencoders and Dynamic Time Warping Technology - Xigui Zheng; Cong Wang; Chao Kong; Cancan Liu; Kai Zhan; Rui Xu (Rock Mechanics and Rock Engineering, 2024)

LGF SeismoLocator: A Deep Learning Model for Precision Microseismic Event Localization in Coal Mines - Kai Zhan; Xiaotao Wen; Rui Xu; Xuben Wang; Cong Wang; Ping Song; Chao Kong (Rock Mechanics and Rock Engineering, 2024)

CircCOX6A1 suppresses osteogenic differentiation and aggravates osteoporosis via miR-512-3p/DYRK2 axis - Dingwen He; Sikuan Zheng; Jian Cao; Jianjian Deng; Rui Ding; Yanjie Xu; Xigao Cheng (Molecular Biology Reports, 2024)

Study of the effect of keap1 on oxidative stress in human umbilical cord mesenchymal stem cells - Hongrong Deng; Yunxia Chen; Huiwen Liu; Li Wang; Hao Xu; Bin Tan; Qin Yi; Rui Wang; Bolin He; Jie Tian; Jing Zhu (Molecular Biology Reports, 2024)
Background HucMSCs had shown promising efficacy in treating childhood diseases, but oxidative stress induced by the poor microenvironment at the site of damage resulted in low cell survival after transplantation, thus preventing the cells from maximizing therapeutic efficacy. Therefore, this study aimed to investigate the role and mechanism of keap1 in oxidative stress injury of human umbilical cord mesenchymal stem cells (hucMSCs), and to provide theoretical support for improving the efficacy of stem cell therapy. Methods The hucMSCs were treated with hypoxic low-sugar-free serum (GSDH) to mimic the damaged site microenvironment after implantation. Adenoviral overexpression of keap1 gene of hucMSCs was performed in vitro, and cell proliferation ability was detected by CCK8 assay, crystal violet staining assay, and cell cycle assay. Cellular redox level was assessed by Amplex Red, MDA, and GSH/GSSG kit. Mitochondrial morphology was evaluated by mitotracker Red staining. ATP production was estimated by ATP detection kit. The mRNA and protein expression levels were tested by western blotting and RT-qPCR. Results GSDH treatment substantially upregulated keap1 expression. Subsequently, we found that overexpression of keap1 notably inhibited cell proliferation and caused cells to stagnate in G1 phase. At the same time, overexpression of keap1 induced the production of large amounts of H 2 O 2 and the accumulation of MDA, but suppressed the GSH/GSSG ratio and the expression of antioxidant proteins NQO1 and SOD1, which caused oxidative stress damage. Overexpression of keap1 induced cells to produce a large number of dysfunctional mitochondria resulting in reduced ATP production. Moreover, Overexpression of keap1 significantly decreased the IKKβ protein level, while upregulating IkB mRNA levels and downregulating P50 mRNA levels. Conclusions Overexpression of keap1 may induce oxidative stress injury in hucMSCs by down-regulating IKKβ expression and inhibiting NF-κB pathway activation. This implies the importance of keap1 in hucMSCs and it may be a potential gene for genetic modification of hucMSCs.

Muscone inhibits angiotensin II–induced cardiac hypertrophy through the STAT3, MAPK and TGF-β/SMAD signaling pathways - Yi-jiang Liu; Jia-jia Xu; Cui Yang; Yan-lin Li; Min-wei Chen; Shi-xiao Liu; Xiang-hui Zheng; Ping Luo; Rui Li; Di Xiao; Zhong-gui Shan (Molecular Biology Reports, 2024)
Background Muscone is a chemical monomer derived from musk. Although many studies have confirmed the cardioprotective effects of muscone, the effects of muscone on cardiac hypertrophy and its potential mechanisms are unclear.The aim of the present study was to investigate the effect of muscone on angiotensin (Ang) II-induced cardiac hypertrophy. Methods and results In the present study, we found for the first time that muscone exerted inhibitory effects on Ang II-induced cardiac hypertrophy and cardiac injury in mice. Cardiac function was analyzed by echocardiography measurement, and the degree of cardiac fibrosis was determined by the quantitative real-time polymerase chain reaction (qRT-PCR), Masson trichrome staining and western blot assay. Secondly, qRT-PCR experiment showed that muscone attenuated cardiac injury by reducing the secretion of pro-inflammatory cytokines and promoting the secretion of anti-inflammatory cytokines. Moreover, western blot analysis found that muscone exerted cardio-protective effects by inhibiting phosphorylation of key proteins in the STAT3, MAPK and TGF-β/SMAD pathways. In addition, CCK-8 and determination of serum biochemical indexes showed that no significant toxicity or side effects of muscone on normal cells and organs. Conclusions Muscone could attenuate Ang II-induced cardiac hypertrophy, in part, by inhibiting the STAT3, MAPK, and TGF-β/SMAD signaling pathways.

Adventitious shoot organogenesis from immature leaves of sugarcane (Saccharum spp. hybrid) cultivar Yuetang 03-373 improving shoot proliferation and industrial scale-up of plants - Shuangyan Chen; Yinglin Lu; Qingwen Luo; Jiana Tan; Jinyan Guan; Jianpiao Luo; Yuchan Xu; Mengyi Chen; Rui Zhao; Jaime A. Teixeira da Silva; Yifei Zhang; Guohua Ma (Journal of Crop Science and Biotechnology, 2024)

CD90’s role in vascularization and healing of rib fractures: insights from Dll4/notch regulation - Lei Wang; Rui Hu; Pei Xu; Pengkai Gao; Bin Mo; Liya Dong; Fengqing Hu (Inflammation Research, 2024)

A novel data-driven hybrid intelligent prediction model for reservoir landslide displacement - Dezhi Zai; Rui Pang; Bin Xu; Jun Liu (Bulletin of Engineering Geology and the Environment, 2024)

Exploring the role of YBX3 in PEDV infection through the utilization of YBX3 knockout and overexpression cell lines - Jiayun Wu; Huizhen Gao; Haoyu Rui; Pan Xu; Ligang Ni; Junsheng Zhang; Ligang Wang (Virus Genes, 2024)

Metals are overlooked in the evolution of antibiotic resistance - Yi Zhao; Rui Xu; Siobhan F. Cox; Min Qiao; Huaming Guo (Soil Ecology Letters, 2024)

Dynamics of Haptophytes (Eukaryota, Hacrobia) Revealed via Short-Term Sampling in the South China Sea - Haoyue Zhang; Ran Li; Bowei Gu; Hejun Kong; Jie Xu; Rui Zhang; Xiaolin Li; Nianzhi Jiao; Dapeng Xu (Journal of Ocean University of China, 2024)

Chang’E-7 Lunar Soil Water Molecule Analyzer (LSWMA) Prototype for High-Precision Measurement of Water Content and Hydrogen Isotope Ratio - Rui Chen; Wenzhen Lu; Xiang Li; Xingping Wang; Kan Chen; Chi Zhang; Nailiang Cao; Zhenyu Xu; Yi Xu; Ruifeng Kan; Renrui Liu; Qiquan Yang; et al. (Journal of Earth Science, 2024)

Association between particulate matter exposure and acute ischemic stroke admissions in less-polluted areas: a time-series study using a distributed lag nonlinear model - Xiaoxiao Song; Xiaolan Huang; Jinling Li; Liming Lu; Rui Qin; Miaomiao Xu; Li Su; Lian Gu (Journal of Environmental Health Science and Engineering, 2024)

Relative importance of altitude shifts with plant and microbial diversity to soil multifunctionality in grasslands of north-western China - Ning Wang; Junhui Cheng; Yunhua Liu; Qicheng Xu; Chen Zhu; Ning Ling; Junjie Guo; Rui Li; Wei Huang; Shiwei Guo; Baorong Wang; Shaoshan An; et al. (Plant and Soil, 2024)

Probiotic nucleotides increase IL-10 expression in airway macrophages to mitigate airway allergy - Jinmei Xue; Zhizhen Liu; Bailing Xie; Rui Dong; Juan Wu; Yisha Wu; Zhihan Xu; Yuhe Tian; Yao Wei; Zhigang Geng; Lei Lu; Yu Liu; et al. (Inflammation Research, 2024)

Analysis of factors affecting microbial degradation of cyanobacterial toxins based on theoretical calculations - Jianglong Ling; Ye Ruan; Congchao Xu; Di Liu; Bowen Shi; Yihong Yang; Zihao Jia; Tianyu Zhang; Mingxuan Guo; Rui Li; Xixi Li (Environmental Geochemistry and Health, 2024)

A novel hollow flower shaped Cu9S8 antibacterial agent for removing sulfonamide in water environment: effects of composite with magnetic biochar, differential adsorption, and mechanism study - Rui-peng Li; Zheng-rong Hu; Xing Wang; Jun Chen; Qing-qing Liu; Ying Zhao; Zhong-bao Zhao; Xu-lin Lu; Zhi-wei Zhang (Environmental Science and Pollution Research, 2024)

Arbuscular Mycorrhizal Fungi Enhance Tolerance to Drought Stress by Altering the Physiological and Biochemical Characteristics of Sugar Beet - Zeyuan Cui; Rui Chen; Tai Li; Bingchen Zou; Gui Geng; Yao Xu; Piergiorgio Stevanato; Lihua Yu; Vadim N. Nurminsky; Jiahui Liu; Yuguang Wang (Sugar Tech, 2024)

Effects of Different Concentrations of Weak Acid Fracturing Fluid on the Microstructure of Coal - Gan Rui; Zuo Shaojie; Si Junting; Liu Chengwei; Tian Feng; Jiang Zhizhong; Wang Changwei; Peng Shouqing; Xu Zhiyuan (Natural Resources Research, 2024)

RETRACTED ARTICLE: miR-365b-3p adsorbed by HCG18 inhibits the proliferation and angiogenesis of stomach adenocarcinoma by downregulating STC1 - Hui Li; Jian Song; Rui Hou; Yingdong Cao; Huaili Xu (Molecular & Cellular Toxicology, 2024)

Chemical constituents from the aerial parts of Rhododendron thymifolium and its bioactivities against Tribolium castaneum, Lasioderma serricorne, and Ditylenchus destructor - Jun-Yu Liang; Ying-Ying Yang; Rui Feng; Xiao-Han Zhang; Xu-Dong Wang; Jun-Long Wang; Wei-Bao Kong; Ji Zhang (Journal of Plant Diseases and Protection, 2024)

Bentonite/Sesbania Gum Hydrogel for Effective Removal of Cationic Dyes: Network Structure Construction and the Role of Multiple Hydroxyl and Carboxyl Adsorption Sites - Luying Jiang; Sishan Yu; Jingwei Zhang; Zisong Xu; Rui Tang; Yinlong Wang; Ke Liang; Chen Zhai; Zhangfa Tong; Hanbing Zhang (International Journal of Environmental Research, 2024)

RIP3 regulates doxorubicin-induced intestinal mucositis via FUT2-mediated α-1,2-fucosylation - Wei Wen; Xiaomin Hu; Jialin Liu; Fanxin Zeng; Yihua Xu; Ye Yuan; Chunyan Gao; Xueting Sun; Bo Cheng; Jue Wang; Xinli Hu; Rui-Ping Xiao; et al. (Inflammation Research, 2024)

Microbial Community Structure and Metabolism of Xinjiang Fine-Wool Sheep based on High-Throughput Sequencing Technology - Rui Yao; Fulin Li; Xuyang Dong; Yueren Xu; Ruirui Hu; Limin Wang; Kuojun Cai; Xiaogang Liu; Wei Ni; Ping Zhou; Shengwei Hu (Current Microbiology, 2024)

Long-Chain Alkenones in the South Yellow Sea Sediments and Their Indicative Significance for Haptophytes Species - Yakun Xu; Xinxin Yang; Rui Xiao; Lei Xing (Journal of Ocean University of China, 2024)

Undifferenced array PPP: a model for GNSS integrated positioning and attitude determination - Xiangdong An; Rui Shang; Xiaolin Meng; Weiping Jiang; Zhenhao Xu; Ruijie Xi; Qusen Chen (GPS Solutions, 2024)

Lightweight seamless lane-level positioning with the integration of BDS-3 PPP-B2b and VINS: a case study using smartphone - Rui Shang; Chengfa Gao; Xiaolin Meng; Zhenhao Xu; Qi Liu; Qianqian Chen; Xiangdong An (GPS Solutions, 2024)

TNF-α and RPLP0 drive the apoptosis of endothelial cells and increase susceptibility to high-altitude pulmonary edema - Yi-Ling Ge; Pei-Jie Li; Ying-Rui Bu; Bin Zhang; Jin Xu; Si-Yuan He; Qing-Lin Cao; Yun-Gang Bai; Jin Ma; Lin Zhang; Jie Zhou; Man-Jiang Xie (Apoptosis, 2024)
High-altitude pulmonary edema (HAPE) is a fatal threat for sojourners who ascend rapidly without sufficient acclimatization. Acclimatized sojourners and adapted natives are both insensitive to HAPE but have different physiological traits and molecular bases. In this study, based on GSE52209, the gene expression profiles of HAPE patients were compared with those of acclimatized sojourners and adapted natives, with the common and divergent differentially expressed genes (DEGs) and their hub genes identified, respectively. Bioinformatic methodologies for functional enrichment analysis, immune infiltration, diagnostic model construction, competing endogenous RNA (ceRNA) analysis and drug prediction were performed to detect potential biological functions and molecular mechanisms. Next, an array of in vivo experiments in a HAPE rat model and in vitro experiments in HUVECs were conducted to verify the results of the bioinformatic analysis. The enriched pathways of DEGs and immune landscapes for HAPE were significantly different between sojourners and natives, and the common DEGs were enriched mainly in the pathways of development and immunity. Nomograms revealed that the upregulation of TNF-α and downregulation of RPLP0 exhibited high diagnostic efficiency for HAPE in both sojourners and natives, which was further validated in the HAPE rat model. The addition of TNF-α and RPLP0 knockdown activated apoptosis signaling in endothelial cells (ECs) and enhanced endothelial permeability. In conclusion, TNF-α and RPLP0 are shared biomarkers and molecular bases for HAPE susceptibility during the acclimatization/adaptation/maladaptation processes in sojourners and natives, inspiring new ideas for predicting and treating HAPE.

A multi-spatial scale analysis of anthropogenic nitrogen and phosphorus inputs in a large river basin: environmental effect and policy impact - Chenning Deng; Zeqian Zhang; Chaozheng Zhang; Rui Xu; Chong Nie; Qingjia Meng; Tiansen Zou; Hong Li; Jia Wu; Queping Yang (Regional Environmental Change, 2024)

An information quantity and machine learning integrated model for landslide susceptibility mapping in Jiuzhaigou, China - Yunjie Yang; Rui Zhang; Tianyu Wang; Anmengyun Liu; Yi He; Jichao Lv; Xu He; Wenfei Mao; Wei Xiang; Bo Zhang (Natural Hazards, 2024)

Farrerol Alleviates Cerebral Ischemia–Reperfusion Injury by Promoting Neuronal Survival and Reducing Neuroinflammation - Rui Zhao; Xin Zhou; Zhiyuan Zhao; Wenhao Liu; Mengfei Lv; Zhaolong Zhang; Changxin Wang; Tianli Li; Zixiong Yang; Qi Wan; Rui Xu; Yu Cui (Molecular Neurobiology, 2024)

Isolation and Characterization of a Novel Vibrio Phage vB_ValA_R15Z - Huifang Li; Wanxuan Zhong; Xinyu Zhang; Zhang Rui; Yunlan Yang; Juntian Xu; Jie Gao; Xing Zhou; Jie Wu; Jie Xu (Current Microbiology, 2024)

In vivo manufacture and manipulation of CAR-T cells for better druggability - Rui Hou; Xiaoxue Zhang; Xu Wang; Xuan Zhao; Sijin Li; Zhangchun Guan; Jiang Cao; Dan Liu; Junnian Zheng; Ming Shi (Cancer and Metastasis Reviews, 2024)

Engineering disease-resistant plants with alternative translation efficiency by switching uORF types through CRISPR - Jingjing Tian; Zhijuan Tang; Ruixia Niu; Yulu Zhou; Dan Yang; Dan Chen; Ming Luo; Rui Mou; Meng Yuan; Guoyong Xu (Science China Life Sciences, 2024)

Stefin B alleviates the gouty arthritis in mice by inducing the M2 polarization of macrophages - Shishui Lin; Xu Hu; Yang Li; Jiyue Huang; Rui Zhang; Xinxin Bai; Shaohuang Weng; Min Chen (Naunyn-Schmiedeberg's Archives of Pharmacology, 2024)
The present study aims to explore the therapeutic effect of Stefin B on gouty arthritis (GA) and the polarization of macrophages in mice. Stefin B-overexpressed or knockdown M0 macrophages were constructed. The GA model was established in mice by injecting 25 mg/mL MSU, followed by a single injecting of Stefin B-overexpressing adenovirus vector (GA model + Stefin B OE) or an empty vector (GA model + Stefin B OE NC). Stefin B was found lowly expressed in M1 macrophages. CD206 was markedly upregulated and IL-10 release was signally increased in Stefin B-overexpressed macrophages. In gouty arthritis mice, marked redness and swelling were observed in the ankle joint. Dramatical infiltration of inflammatory cells was observed in the GA model and GA model + Stefin B OE NC groups, which was suppressed in the Stefin B OE group. Increased proportion of F4/80 + CD86 + cells observed in GA mice was markedly repressed by Stefin B overexpression, accompanied by the declined level of Caspase-1 and IL-17. Collectively, Stefin B alleviated the GA in mice by inducing the M2 polarization of macrophages.

A Permeability Prediction Model of Single-Peak NMR T2 Distribution in Tight Sandstones: A Case Study on the Huangliu Formation, Yinggehai Basin, China - Jing Zhao; Zhilong Huang; Jin Dong; Jingyuan Zhang; Rui Wang; Chonglin Ma; Guangjun Deng; Maguang Xu (Mathematical Geosciences, 2024)

Ile-Pro-Pro attenuates sympathetic activity and hypertension - Jun-Liu Chen; Rui Ge; Xiu-Zhen Li; Yue Zhang; Wen-Yuan Hao; Na Li; Zhi-Qin Xu; Qi Chen; Yue-Hua Li; Guo-Qing Zhu; Xiao Tan (Journal of Physiology and Biochemistry, 2024)

Distribution, risk evaluation, and source allocation of cesium and strontium in surface soil in a mining city - Jia-li Li; Chun-dan Gan; Xin-yue Du; Xue-ying Yuan; Wen-lin Zhong; Meng-qi Yang; Rui Liu; Xiao-yu Li; Hao Wang; Yu-liang Liao; Zheng Wang; Mu-cheng Xu; et al. (Environmental Geochemistry and Health, 2024)

SSVEP-based visual acuity threshold estimation: linear extrapolation to noise level baseline with various noise definition criteria - Xiaowei Zheng; Xin Wei; Guanghua Xu; Rui Zhang (Cognitive Neurodynamics, 2024)

A novel AP2/ERF transcription factor, NtERF10, positively regulates plant height in tobacco - Li Xu; Yong Xu; Jia-rui Jiang; Chang-xin Cheng; Wen-wu Yang; Le-le Deng; Qi-li Mi; Wan-li Zeng; Jing Li; Qian Gao; Hai-ying Xiang; Xue-mei Li (Transgenic Research, 2024)
Ethylene response factors have been shown to be involved in the effects of plant developmental processes and to regulate stress tolerance. The aim of this study was to recognize the regulatory mechanisms of ethylene response factors on tobacco plant height. In this study, a gene-edited mutant (ERF10-KO) and wild type (WT) were utilized as experimental materials. Transcriptome and metabolome analyses were used to investigate the regulatory mechanism of NtERF10 gene editing on plant height in tobacco. Here, through the analysis of differentially expressed genes (DEGs), 2051 genes were upregulated and 1965 genes were downregulated. We characterized the different ERF10-KO and WT plant heights and identified key genes for photosynthesis, the plant hormone signal transduction pathway and the terpene biosynthesis pathway. NtERF10 was found to affect the growth and development of tobacco by regulating the expression levels of the PSAA , PSBA , GLY17 and GGP3 genes. Amino acid metabolism was analyzed by combining analyses of differentially expressed genes (DEGs) and differentially accumulated metabolites (DAMs). In addition, we found that members of the bHLH, NAC, MYB, and WRKY transcription factor families have vital roles in regulating plant height. This study not only provides important insights into the positive regulation of the ethylene response factor NtERF10 on plant height during plant growth and development but also provides new research ideas for tobacco molecular breeding.

Projected changes in wind erosion climatic erosivity over high mountain Asia: results from dynamical downscaling outputs - Rui Mao; Yuanyuan Xu; Jianze Zhu; Xuezhen Zhang; Shuaifeng Song; Dao-Yi Gong; Lianyou Liu; Peijun Shi (Asia-Pacific Journal of Atmospheric Sciences, 2024)

Astaxanthin Rescues Memory Impairments in Rats with Vascular Dementia by Protecting Against Neuronal Death in the Hippocampus - Na Wei; Luo-man Zhang; Jing-Jing Xu; Sheng-lei Li; Rui Xue; Sheng-li Ma; Cai Li; Miao-miao Sun; Kui-sheng Chen (NeuroMolecular Medicine, 2024)

Investigation of the Inhibitory Effects of Illicium verum Essential Oil Nanoemulsion on Fusarium proliferatum via Combined Transcriptomics and Metabolomics Analysis - Cui-Qiong Ling; Hong-Xin Liao; Jin-Rui Wen; Hong-Yan Nie; Li-Yan Zhang; Fu-Rong Xu; Yong-Xian Cheng; Xian Dong (Current Microbiology, 2024)

Metagenomic data highlight shifted nitrogen regime induced by wetland reclamation - Kexin Li; Nannan Wang; Fenghui Yuan; Xinhao Zhu; Yunjiang Zuo; Jianzhao Liu; Ziyu Guo; Ying Sun; Rui Su; Lihua Zhang; Sergei Lupakov; Yanyu Song; et al. (Biology and Fertility of Soils, 2024)

Preparation of bacterial fertilizer from biogas residue after anaerobic co-digestion of kitchen waste and residual sludge - Chuan Li; Chang Hua; Lingling Chen; Zimei Miao; Rui Xu; Sili Peng; Zhiwei Ge; Lingfeng Mao (Environmental Science and Pollution Research, 2024)

Whole exome sequencing analyses reveal novel genes in telomere length and their biomedical implications - Wei-Shi Liu; Bang-Sheng Wu; Liu Yang; Shi-Dong Chen; Ya-Ru Zhang; Yue-Ting Deng; Xin-Rui Wu; Xiao-Yu He; Jing Yang; Jian-Feng Feng; Wei Cheng; Yu-Ming Xu; et al. (GeroScience, 2024)

Climate and soil: Key Drivers of Plant Traits and Community Functional Differences in the Lakeshore Wetlands of Northern China - Rui Zhang; Zhichao Xu; Huamin Liu; Hongbo Yu; Feng Niu; Haitao Fang; Linqian Ma; Yunhao Wen; Lu Wen; Yi Zhuo; Lixin Wang (Wetlands, 2024)

Structure of a histone hexamer bound by the chaperone domains of SPT16 and MCM2 - Songlin Gan; Wen-Si Yang; Liting Wei; Zhiguo Zhang; Rui-Ming Xu (Science China Life Sciences, 2024)

Adaptive strategies of high and low nucleic acid prokaryotes in response to declining resource availability and selective grazing by protozoa - Chen Hu; Liuqian Yu; Xiaowei Chen; Jihua Liu; Yao Zhang; John Batt; Xilin Xiao; Qiang Shi; Rui Zhang; Tingwei Luo; Nianzhi Jiao; Dapeng Xu (Science China Earth Sciences, 2024)
Prokaryotes play a fundamental role in global ocean biogeochemical cycles. However, how the abundance and metabolic activity of ecologically distinct subgroups (i.e., high nucleic acid (HNA) and low nucleic acid (LNA) cells), and their regulating factors, change in response to changing marine environmental conditions remains poorly understood. Here, we delved into the time-evolving dynamic responses of the HNA and LNA prokaryotic subgroups to declining resource availability and selective grazing by protozoa by conducting a 73-day incubation experiment in a large-volume (117,000 L) macrocosm that facilitates community-level exploration. We found that the metabolic activity of the HNA subgroup was higher than that of the LNA subgroup when the macrocosm was resource replete but that the HNA subgroup declined more rapidly than the LNA subgroup as the resources became increasingly scarce, leading to a steadily increasing contribution of LNA cells to prokaryotic activity. Meanwhile, as resources in the macrocosm became limited, protozoan grazing preference shifted from the HNA to the LNA subgroup and the contributions of the LNA subgroup to the carbon flow within the macrocosm increased. The findings highlight the resilience of LNA cells in resource-limited environments, illuminate the critical role of selective grazing by protozoa in balancing distinct prokaryotic subgroups under changing resource conditions, and demonstrate the complex and adaptive interactions between protozoa and prokaryotes across diverse environmental contexts.

Vernalization promotes bolting in sugar beet by inhibiting the transcriptional repressors of BvGI - Chunxue Zhang; Shengnan Li; Yuguang Wang; Jiali Long; Xinru Li; Lixun Ke; Rui Xu; Zedong Wu; Zhi Pi (Plant Molecular Biology, 2024)

Primary Cutaneous Mucormycosis Caused by Mucor irregularis in a Chinese Man - Zhihua Li; Qing Jiang; Xiaohua Tao; Zhenhua Zhang; Luhuai Shi; Lifang Cheng; Pingxiu He; Xinyi Fan; Rui Xu; Yunpeng Luo; Yangmin Gao (Mycopathologia, 2024)

Clinical Characteristics and Pathogen Spectrum of Male Genital Fungal Infections in Nanchang Area, South China - Yun Jin; Yangmin Gao; Yunpeng Luo; XiaoHua Tao; Qing Jiang; Xinyi Fan; Rui Xu; Hua Qian; Xiaoguang Li; Zhijun Zhou (Mycopathologia, 2024)
The cutaneous fungal infections in male genitalia are relatively rare, and often present with various atypical clinical symptoms. It was mainly reported in a small number of case reports, while data with large number of patients were rarely reported. In this study, we reported 79 male patients with cutaneous fungal infections on scrotum or penis. The fungal infections were confirmed by microscopic examination directly and fungus culture. Clinical characteristics and predisposing factors were also collected. Of these 79 patients, 72 has lesions on scrotum, 5 on penis and 2 on both scrotum and penis. Trichophyton (T.) rubrum is the most common pathogen, found in 50 (67.6%) patients, which presented diverse clinical manifestation such as majorly erythematous, dry diffused scaly lesions without a clear border, slightly powdery and scutular scalings. Candida (C.) albicans is the secondly common pathogen, found in 21 (28.4%) patients, which also presented diverse lesions such as erythematous with dry whitish scaly lesions and erythematous erosion. The predisposing factors mainly included concomitant fungal infections on sites other than genitalia, especially inguinal region (tinea cruris), application of corticosteroid and high moisture. In conclusion, cutaneous fungal infections in male genitalia could be caused by different fungi, showed atypical or mild clinical appearances in most cases and might be a fungus reservoir, emphasizing the necessity to timely perform the fungi examinations and corresponding therapy.

Fractal characteristics of particle breakage on the coral sands–structure interface during ring shear tests - Houzhen Wei; Li Xin; Hang Ruan; Qi Yao; Xiaolong Ma; Rui Xu (Marine Geophysical Research, 2024)

Effects of an anti-WSSV transgenic cyanobacterial oral agent on the development, reproduction, and physiology of Daphnia magna - Yupei Tong; Yang Xu; Wen Peng; Dingji Shi; Yuqing Li; Rui Jia (Journal of Applied Phycology, 2024)

Curcumol: a review of its pharmacology, pharmacokinetics, drug delivery systems, structure–activity relationships, and potential applications - Sicheng Zhai; Rui Wang; Jingyuan Wang; Xiangdong Xu; Le Niu; Min Guo; Yongling Zhang; Yajun Shi; Xuexue Tang (Inflammopharmacology, 2024)

Recognition of autism spectrum disorder in children based on electroencephalogram network topology - Fali Li; Shu Zhang; Lin Jiang; Keyi Duan; Rui Feng; Yingli Zhang; Gao Zhang; Yangsong Zhang; Peiyang Li; Dezhong Yao; Jiang Xie; Wenming Xu; et al. (Cognitive Neurodynamics, 2024)

Air permeability variation of compacted loess: effects of soil basic properties and dry-wet cycles - Shi-Feng Lu; Xiao-Pei Guo; Xing-Rui Wang; Zi-Jing Han; Ling Xu; Xiao-Lin Huang; Lu Zuo (Bulletin of Engineering Geology and the Environment, 2024)

Co-occurrence of dominant bacteria and methanogenic archaea and their metabolic traits in a thermophilic anaerobic digester - Yanru Zhang; Yinping Xiang; Zhaohui Yang; Rui Xu (Environmental Science and Pollution Research, 2024)

Unlocking the potential of biochar: an iron-phosphorus-based composite modified adsorbent for adsorption of Pb(II) and Cd(II) in aqueous environments and response surface optimization of adsorption conditions - Xu Li; Yuan Chi; Feng Ma; Xiaoxin Wang; Rui Du; Zhipeng Wang; Xiaoyan Dang; Chaoyue Zhao; Yanping Zhang; Shumin He; Youzhao Wang; Tong Zhu (Environmental Science and Pollution Research, 2024)

A Senescence-Associated Secretory Phenotype of Bone Marrow Mesenchymal Stem Cells Inhibits the Viability of Breast Cancer Cells - Meng Li; Jie-Xi Liu; Bo Ma; Jin-Yu Liu; Ji Chen; Fang Jin; Cheng-Hu Hu; Hao-Kun Xu; Chen-Xi Zheng; Rui Hou (Stem Cell Reviews and Reports, 2024)

Heat shock protein HvHSP16.9 from wild barley enhances tolerance to salt stress - Haowen Chang; Tiantian Wu; Abdullah Shalmani; Le Xu; Chengdao Li; Wenying Zhang; Rui Pan (Physiology and Molecular Biology of Plants, 2024)

Analysis on the causes of massive stranding of Yellow Sea green tide on Lianyungang and Rizhao coasts in 2022 - Lingjuan Wu; Juan Huang; Yi Ding; Guiyan Liu; Shuai Huang; Song Gao; Chao Yuan; Jiangling Xu; Ping Wu; Rui Huang; Ruobing Wen; Jie Mei (Journal of Oceanology and Limnology, 2024)

The influence of complex terrain on cloud and precipitation on the foot and slope of the southeastern Tibetan Plateau - Junjun Li; Chunsong Lu; Jinghua Chen; Xu Zhou; Kun Yang; Jian Li; Xiaoqing Wu; Xiaoqi Xu; Shiying Wu; Rui Hu; Xin He; Zhuangzhuang Zhou; et al. (Climate Dynamics, 2024)

The simultaneous removal of methylene blue (MB) and Ca2+ by recyclable adsorbents based the scales derived from coal gasification system - Bai-Hong An; Da-Mao Xu; Run-Ting Wang; Ye-Xuan Wen; Rui Geng; Jia-Yun Wu; Xian-Chun Tang; Hong-Bin Chen (Environmental Science and Pollution Research, 2024)

Innovative recovery of matrix layered double hydroxide from simulated acid mine wastewater for the removal of copper and cadmium from wastewater - Rui Deng; Zhengbo Yue; Xinquan Wang; Qingsheng Xu; Jin Wang (Environmental Science and Pollution Research, 2024)

Effect of Regional Brain Activity Following Repeat Transcranial Magnetic Stimulation in SCA3: A Secondary Analysis of a Randomized Clinical Trial - Xia Liu; Lin Zhang; Hao-Lin Xu; Xia-Hua Liu; Arif Sikandar; Meng-Cheng Li; Xiao-Yue Xia; Zi-Qiang Huang; Na-Ping Chen; Yu-Qing Tu; Jian-Ping Hu; Shi-Rui Gan; et al. (The Cerebellum, 2024)

Analysis of landslide deformation in eastern Qinghai Province, Northwest China, using SBAS-InSAR - Haibo Tian; Pinglang Kou; Qiang Xu; Yuxiang Tao; Zhao Jin; Ying Xia; Jiangfan Feng; Rui Liu; Yongcheng Gou (Natural Hazards, 2024)

Multi-scale risk assessment method of rainstorm meteorological disaster for traffic in Wuhan 1 + 8 urban agglomeration - Rui Li; Xu Zhang; Chenghong Hu; Nengcheng Chen; Xiang Zhang (Natural Hazards, 2024)

Finite element modeling and analysis of effect of preexisting cervical degenerative disease on the spinal cord during flexion and extension - Meng-lei Xu; Yi-ting Yang; Hui-zi Zeng; Yu-ting Cao; Liang-dong Zheng; Chen Jin; Shi-jie Zhu; Rui Zhu (Medical & Biological Engineering & Computing, 2024)

Knockout of lws1 in zebrafish (Danio rerio) reveals its role in regulating feeding and vision-guided behavior - Di-Mei Xu; Fa-Rui Chai; Xu-Fang Liang; Ke Lu (Functional & Integrative Genomics, 2024)

Comprehensive evaluation of newly cultivated land sustainable utilization at project scale: A case study in Guangdong, China - Chang Guo; Xiaobin Jin; Xuhong Yang; Weiyi Xu; Rui Sun; Yinkang Zhou (Journal of Geographical Sciences, 2024)

Correction to: A new strategy for groundwater level prediction using a hybrid deep learning model under Ecological Water Replenishment - Zihao Jia; Qin Zhang; Bowen Shi; Congchao Xu; Di Liu; Yihong Yang; Beidou Xi; Rui Li (Environmental Science and Pollution Research, 2024)

Endothelial specific prolyl hydroxylase domain-containing protein 2 deficiency attenuates aging-related obesity and exercise intolerance - Lihong Pan; Xiaochen He; Rui Xu; Umesh Bhattarai; Ziru Niu; Jussara do Carmo; Yuxiang Sun; Heng Zeng; John S. Clemmer; Jian-Xiong Chen; Yingjie Chen (GeroScience, 2024)
Obesity and exercise intolerance greatly reduce the life quality of older people. Prolyl hydroxylase domain-containing protein 2 (PHD2) is an important enzyme in modulating hypoxia-inducible factor-alpha (HIF) protein. Using vascular endothelial cell-specific PHD2 gene knockout (PHD2 ECKO) mice, we investigated the role of endothelial PHD2 in aging-related obesity and exercise capacity. Briefly, PHD2 ECKO mice were obtained by crossing PHD2-floxed mice with VE-Cadherin (Cdh5)-Cre transgenic mice. The effect of PHD2 ECKO on obesity and exercise capacity in PHD2 ECKO mice and control PHD2 f/f mice were determined in young mice (6 to 7 months) and aged mice (16–18 months). We found that aged PHD2 ECKO mice, but not young mice, exhibited a lean phenotype, characterized by lower fat mass, and its ratio to lean weight, body weight, or tibial length, while their food uptake was not reduced compared with controls. Moreover, as compared with aged control mice, aged PHD2 ECKO mice exhibited increased oxygen consumption at rest and during exercise, and the maximum rate of oxygen consumption (VO 2 max) during exercise. Furthermore, as compared with corresponding control mice, both young and aged PHD2 ECKO mice demonstrated improved glucose tolerance and lower insulin resistance. Together, these data demonstrate that inhibition of vascular endothelial PHD2 signaling significantly attenuates aging-related obesity, exercise intolerance, and glucose intolerance.

A novel ZnCo2O4/BiOBr p-n/Z-scheme heterojunction photocatalyst for enhancing photocatalytic activity - Tao Xiong; Qi Feng; Cimei Fang; Rui Chen; Yanxi Wang; Longjun Xu; Chenglun Liu (Environmental Science and Pollution Research, 2024)

A new strategy for groundwater level prediction using a hybrid deep learning model under Ecological Water Replenishment - Zihao Jia; Qin Zhang; Bowen Shi; Congchao Xu; Di Liu; Yihong Yang; Beidou Xi; Rui Li (Environmental Science and Pollution Research, 2024)

Genetic lineage tracing identifies adaptive mechanisms of pancreatic islet β cells in various mouse models of diabetes with distinct age of initiation - Qi Fu; Yu Qian; Hemin Jiang; Yunqiang He; Hao Dai; Yang Chen; Zhiqing Xia; Yucheng Liang; Yuncai Zhou; Rui Gao; Shuai Zheng; Hui Lv; et al. (Science China Life Sciences, 2024)

The Relationships Between Danxia Geoheritages and Regional Tectonics in Southern Sichuan Basin: Implications for the Spatial Distribution of Danxia Landforms in China - Jun-Ting Qiu; Hong-Xu Mu; Xin-Min Rui; Yan-Jie Yang; Pengju Li; Liang Qiu; Chao-Bin Xu (Geoheritage, 2024)

Study and verification on an improved comprehensive prediction model of landslide displacement - Tianlong Wang; Rui Luo; Tianxing Ma; Hao Chen; Keying Zhang; Xu Wang; Zhaowei Chu; Hongyue Sun (Bulletin of Engineering Geology and the Environment, 2024)

The maturity, humus content, and microbial metabolic function of sheep manure compost on the Qinghai-Tibet Plateau can be significantly improved by reducing the moisture content - Rui Cai; Xiaohui Cao; Xin Jiang; Chuncheng Xu (Environmental Science and Pollution Research, 2024)

Bisphenol A affects microbial interactions and metabolic responses in sludge anaerobic digestion - Xiao He; Yinping Xiang; Rui Xu; Hanbing Gao; Zhaohui Guo; Weimin Sun (Environmental Science and Pollution Research, 2024)

Meteorological to Agricultural Drought Propagation Time Analysis and Driving Factors Recognition Considering Time-Variant Characteristics - Chengguo Wu; Yin Xu; Juliang Jin; Yuliang Zhou; Boyu Nie; Rui Li; Yi Cui; Fei Tong; Libing Zhang (Water Resources Management, 2024)

Effective Cellulase Production by Trichoderma reesei Using Solid and Liquid Inducers Mixture with Varying Ratios - Muhammad Jawad; Shuxin Pan; Youduo Wu; Omama Rehman; Ying Zhang; Rui Xu; Quan Zhang; Huipeng Gao; Chuang Xue (Sugar Tech, 2024)

Integrating bulk-RNA sequencing and single-cell sequencing analyses to characterize adenosine-enriched tumor microenvironment landscape and develop an adenosine-related prognostic signature predicting immunotherapy in lung adenocarcinoma - Tao Han; Jing Wu; Yafeng Liu; Jiawei Zhou; Rui Miao; Jianqiang Guo; Zhi Xu; Yingru Xing; Ying Bai; Dong Hu (Functional & Integrative Genomics, 2024)

GABRP Promotes the Metastasis of Pancreatic Cancer by Activation of the MEK/ERK Signaling Pathway - Yong Meng; Rui Li; Shuaiming Geng; Wenhao Chen; Weirong Jiang; Zhiwen Li; Ji Hao; Zhen Xu (Biochemical Genetics, 2024)

High-density lipoprotein cholesterol is associated with lowered cognitive recovery among acute ischemic stroke patients with mild cognitive impairment - Rui Wang; Zhuomin Jiao; Anxin Wang; Yijun Zhang; Xiangxiang Hong; Shan Huang; Jin Fu; Yinglian Zhou; Yifei Wang; Chunyang Li; Yue Liu; Ke Wei; et al. (Acta Neurologica Belgica, 2024)

Synergistic effects of adsorption and chemical reduction towards the effective Cr(VI) removal in the presence of the sulfur-doped biochar material - Rui Ma; Xiangning Xu; Yichu Zhang; Dandan Zhang; Guoping Xiang; Yongjun Chen; Jin Qian; Shouliang Yi (Environmental Science and Pollution Research, 2024)

Comparison of Seed Germination Characteristics Between Cultivated and Wild Barley - Le Xu; Haoran Gao; Jun Wu; Siyu Wang; Rui Pan; Wenying Zhang (Journal of Plant Growth Regulation, 2024)

Integrative transcriptomic and metabolomic analyses reveal the phenylpropanoid and flavonoid biosynthesis of Prunus mume - Rui Wu; Chengcheng Qian; Yatian Yang; Yi Liu; Liang Xu; Wei Zhang; Jinmei Ou (Journal of Plant Research, 2024)

Effect of vane angle on turbulence–chemistry interactions, temperature, flow field, burnout, and NOx emissions in swirling flames fueled by semicoke mixtures - Liutao Sun; Shengyu Kuang; Weilin Li; Jingjie Wang; Yanhui Xu; Lingkun Zhu; Hong Tian; Xinzhuo Li; Dengke Wang; Rui Sun (Environmental Science and Pollution Research, 2023)

Research Progress on TRPA1 in Diseases - Jiajing Li; Hongfei Zhang; Qian Du; Junyu Gu; Jiangbo Wu; Qi Liu; Zhuo Li; Ting Zhang; Jingyu Xu; Rui Xie (The Journal of Membrane Biology, 2023)
For a long time, the physiological activity of TRP ion channels and the response to various stimuli have been the focus of attention, and the physiological functions mediated by ion channels have subtle links with the occurrence of various diseases. Our group has been engaged in the study of ion channels. In recent years, the report rate of TRPA1 , the only member of the TRPA subfamily in the newly described TRP channel, has been very high. TRPA1 channels are not only abundantly expressed in peptidergic nociceptors but are also found in many nonneuronal cell types and tissues, and through the regulation of Ca 2+ influx, various neuropeptides and signaling pathways are involved in the regulation of nerves, respiration, circulation, and various diseases and inflammation throughout the body. In this review, we mainly summarize the effects of TRPA1 on various systems in the body, which not only allows us to have a more systematic and comprehensive understanding of TRPA1 but also facilitates more in-depth research on it in the future. Graphical Abstract

Shared and Distinct Topographic Alterations of Alpha-Range Resting EEG Activity in Schizophrenia, Bipolar Disorder, and Depression - Rui Xue; Xiaojing Li; Jianning Chen; Sugai Liang; Hua Yu; Yamin Zhang; Wei Wei; Yan Xu; Wei Deng; Wanjun Guo; Tao Li (Neuroscience Bulletin, 2023)

The Role of Cystathionine-β-Synthase, H2S, and miRNA-377 in Hypoxic-Ischemic Encephalopathy: Insights from Human and Animal Studies - Chun-Yang Liu; Hisham Al-Ward; Ning Liu; Francine Ngaffo Mekontso; Wei Chen; Wenxia Gao; Chunxue Zhang; Abduh Murshed; Zi-Rui Yu; Orion Fan; Yi Eve Sun; Hui Xu (Journal of Molecular Neuroscience, 2023)

Serum HBV RNA levels among untreated adults with chronic hepatitis B in distinct immune phases and liver histopathology statuses - Qin Xu; Hai Ding; Tao Bai; Rui Huang; Jian Wang; Jun Zhang; Hewei Luan; Jun Wang; Yue Yang; Yuxin Chen (Journal of Molecular Histology, 2023)

Three-dimensional visualization of the lymphatic, vascular and neural network in rat lung by confocal microscopy - Shitong Zhao; Jingjing Cui; Yuqing Wang; Dongsheng Xu; Yuxin Su; Jie Ma; Xuefeng Gong; Wanzhu Bai; Jia Wang; Rui Cao (Journal of Molecular Histology, 2023)

Mitochondrial dysfunction: a new molecular mechanism of intervertebral disc degeneration - Chao Song; Yulin Xu; Qinghua Peng; Rui Chen; Daqian Zhou; Kang Cheng; Weiye Cai; Tao Liu; Chenyi Huang; Zhijiang Fu; Cong Wei; Zongchao Liu (Inflammation Research, 2023)

Genome resequencing reveals the population structure and genetic diversity of almond in Xinjiang, China - Pengyu Wu; Dong Li; Rui Zhuang; Hao Zuo; Zhiyong Pan; Bo Yang; Chongzhi Xu (Genetic Resources and Crop Evolution, 2023)

Dietary supplementation of pyridoxine can enhance the growth performance and improve the protein, lipid utilization efficiency of mandarin fish (Siniperca chuatsi) - Rui-Peng Xie; Xu-Fang Liang; Di Peng; Qi-Wei Zhang; Dong-Liang Wu; Jun-Liang Chen; Ming Zeng (Fish Physiology and Biochemistry, 2023)

Soil microbial communities as potential regulators of N2O sources in highly acidic soils - Junhui Yin; Huaihai Chen; Pengpeng Duan; Kun Zhu; Naihui Li; Yan Ma; Yumeng Xu; Jingheng Guo; Rui Liu; Qing Chen (Soil Ecology Letters, 2023)

Triptolide induces PANoptosis in macrophages and causes organ injury in mice - Hong-Rui Zhang; Ya-Ping Li; Zi-Jian Shi; Qi-Qi Liang; Si-Yuan Chen; Yi-Ping You; Tao Yuan; Rong Xu; Li-Hui Xu; Dong-Yun Ouyang; Qing-Bing Zha; Xian-Hui He (Apoptosis, 2023)

Acylhydrazone Functionalized Triphenylamine-Based Fluorescent Probe for Cu2+: Tunable Structures of Conjugated Bridge and Its Practical Application - Xiaohong Cheng; Rui Zhang; Jinbo Sun; Ke Xu; Wangnan Li (Journal of Fluorescence, 2023)

Induction of Anxiety-Like Phenotypes by Knockdown of Cannabinoid Type-1 Receptors in the Amygdala of Marmosets - Lin Zhu; Di Zheng; Rui Li; Chen-Jie Shen; Ruolan Cai; Chenfei Lyu; Binliang Tang; Hao Sun; Xiaohui Wang; Yu Ding; Bin Xu; Guoqiang Jia; et al. (Neuroscience Bulletin, 2023)

Identification of potential genetic causal variants for obesity-related traits using statistical fine mapping - Rui Gong; Jonathan Greenbaum; Xu Lin; Yan Du; Kuan-Jui Su; Yun Gong; Jie Shen; Hong-Wen Deng (Molecular Genetics and Genomics, 2023)

Reduced attention on restricted organochlorine pesticides, whereas still noteworthy of the impact on the deep soil and groundwater: a historical site study in southern China - Changlin Xu; Yue Cai; Rui Wang; Jing Wu; Guoyi Yang; Yahui Lv; Dehong Liu; Yu Deng; Yaqi Zhu; Qing Zhang; Lijun Wang; Shengwei Zhang (Environmental Geochemistry and Health, 2023)

Occurrence, distribution and risk assessment of polycyclic aromatic hydrocarbons in soils around main water source areas of Beijing, China - Bin Li; Liang Zhao; Sining Zhong; Rui An; Ruoqi Ma; Xuming Xu; Qian Chen (Environmental Geochemistry and Health, 2023)

A new anchor-siphon drainage combined method used for slope stabilization - Hong-yue Sun; Xu Wang; Yang Yu; Jun-wei Shu; Tian-long Wang; Rui Luo; Zhao-wei Chu (Journal of Mountain Science, 2023)

Bradykinin-pretreated Human cardiac-specific c-kit+ Cells Enhance Exosomal miR-3059-5p and Promote Angiogenesis Against Hindlimb Ischemia in mice - Jingzhou Li; Fei Song; Ruolan Chen; Jinjuan Yang; Jie Liu; Li Huang; Fuyu Duan; Meng Kou; Boon Xuan Lian; Xiaoxia Zhou; Weimin Han; Liang Mao; et al. (Stem Cell Reviews and Reports, 2023)

Lactiplantibacillus plantarum Regulated Intestinal Microbial Community and Cytokines to Inhibit Salmonella typhimurium Infection - Rui-Han Liu; An-Qi Sun; Ye Liao; Zheng-Xu Tang; Shi-Han Zhang; Xin Shan; Jing-Tao Hu (Probiotics and Antimicrobial Proteins, 2023)

Neglected Adult Tinea Capitis in South China: A Retrospective Study in Nanchang, Jiangxi Province, from 2007 to 2021 - Yun Jin; Chengfang Geng; Oliver Blechert; Qing Jiang; Rui Xu; Yunpeng Luo; Xinyi Fan; Guirong Qiu; Ping Zhan (Mycopathologia, 2023)

Urine 2-hydroxyphenanthrene is associated with current asthma: evidence from NHANES 2007–2012 - Lingyi Lu; Tingfeng Mao; Rui Xu; Lanxia Liu; Jiefeng Qian; Kai Yang; Anjie Yuan; Xinyue Wang; Rong Ni (International Archives of Occupational and Environmental Health, 2023)

Risk factors for thrombocytopenia in patients receiving linezolid therapy: a systematic review and meta-analysis - Dan Zhang; Yasi Xu; Xiang Wang; Leping Hou; Mengyu Xing; Shuang Xu; Rui Guo; Ying Luo (European Journal of Clinical Pharmacology, 2023)

Complete Genome Sequence of Streptomyces sp. HP-A2021, a Promising Bacterium for Natural Product Discovery - Lan-Fang Li; Qing-Xuan Wu; Hao Wu; Yao Li; Qian Peng; Ren-Hao Han; Da-Hu Zhang; Wei-Dong Yu; Rui Xu; Juan Wang; Zhaobin Fan; Shao-Yang Hou (Biochemical Genetics, 2023)

Epidemiology, genetic diversity, and evolutionary dynamics of Tembusu virus - Peng Zhou; Bin Ma; Yuan Gao; Yumin Xu; Zhuofei Li; Hui Jin; Rui Luo (Archives of Virology, 2023)

Functional characterization of novel NPRL3 mutations identified in three families with focal epilepsy - Shiyue Du; Sheng Zeng; Li Song; Hongying Ma; Rui Chen; Junyu Luo; Xu Wang; Tingbin Ma; Xuan Xu; Hao Sun; Ping Yi; Jifeng Guo; et al. (Science China Life Sciences, 2023)

Cutting Efficiency of a Newly Developed Incubator-Based Laser Cutting Method and Its Effects on Potato Tissue Culture Plantlet Growth - Tao Xu; Hongbing Duan; Xingkui Cai; Rui Yang; Feihu Yao; Benfang Tan; Fengshun Liu (Potato Research, 2023)

The biocontrol agent Bacillus velezensis T-5 changes the soil bacterial community composition by affecting the tomato root exudate profile - Yian Gu; Weina Liang; Zhidan Li; Sijie Liu; Sun Liang; Peng Lei; Rui Wang; Nan Gao; Sha Li; Zongqi Xu; Hong Xu (Plant and Soil, 2023)

Development and validation a prognostic model based on natural killer T cells marker genes for predicting prognosis and characterizing immune status in glioblastoma through integrated analysis of single-cell and bulk RNA sequencing - Jiahe Hu; Lei Xu; Wenchao Fu; Yanan Sun; Nan Wang; Jiheng Zhang; Chengyun Yang; Xiaoling Zhang; Yuxin Zhou; Rongfang Wang; Haoxin Zhang; Ruishu Mou; et al. (Functional & Integrative Genomics, 2023)

Prediction of landslide block movement based on Kalman filtering data assimilation method - Yong Liu; Qing-jie Xu; Xing-rui Li; Ling-feng Yang; Hong Xu (Journal of Mountain Science, 2023)

AIWW: a new nutrition-screening tool for the oncologic population - Yi-Zhong Ge; Zhen-Ming Fu; Qi Zhang; Meng-Meng Song; Guo-Tian Ruan; Xi Zhang; Xiao-Wei Zhang; Xiang-Rui Li; Kang-Ping Zhang; Meng Tang; Xiao-Yue Liu; Ming Yang; et al. (Science China Life Sciences, 2023)

Specific pupylation as IDEntity reporter (SPIDER) for the identification of protein-biomolecule interactions - He-Wei Jiang; Hong Chen; Yun-Xiao Zheng; Xue-Ning Wang; Qingfeng Meng; Jin Xie; Jiong Zhang; ChangSheng Zhang; Zhao-Wei Xu; Zi-Qing Chen; Lei Wang; Wei-Sha Kong; et al. (Science China Life Sciences, 2023)

Spatial distribution of landslide shape induced by Luding Ms6.8 earthquake, Sichuan, China: case study of the Moxi Town - Xuemei Liu; Pengcheng Su; Yong Li; Zhaoxu Xia; Siyuan Ma; Rui Xu; Yao Lu; Dahu Li; Heng Lu; Renmao Yuan (Landslides, 2023)

Analysis of the Sedimentary Characteristics of a Modern Distributive Fluvial System: A Case Study of the Great Halten River in the Sugan Lake Basin, Qinghai, China - Xianghui Zhang; Changmin Zhang; Adrian Hartley; Qinghai Xu; Wenjie Feng; Taiju Yin; Rui Zhu (Journal of Earth Science, 2023)

Analysis of cuproptosis-related lncRNA signature for predicting prognosis and tumor immune microenvironment in pancreatic cancer - Hong-Fei Yao; Da-Peng Xu; Jia-Hao Zheng; Yu Xu; Qin-Yuan Jia; Yu-Heng Zhu; Jian Yang; Rui-Zhe He; Ding Ma; Min-Wei Yang; Xue-Liang Fu; De-Jun Liu; et al. (Apoptosis, 2023)

Methanol tolerance upgrading of Proteus mirabilis lipase by machine learning-assisted directed evolution - Rui Ma; Yingnan Li; Meng Zhang; Fei Xu (Systems Microbiology and Biomanufacturing, 2023)

Lead change of a HIF-2α antagonist guided by multiparameter optimization and utilization of an Olp→π*Ar interaction - Paul M. Wehn; Song Yang; Jonas A. Grina; James P. Rizzi; Stephen T. Schlachter; Bin Wang; Rui Xu; Hanbiao Yang; Xinlin Du; Guangzhou Han; Keshi Wang; Robert M. Czerwinski; et al. (Medicinal Chemistry Research, 2023)

A Novel D-π-A Type Fluorescent Probe for Cu2+ Based on Styryl-Pyridinium Salts Conjugating Di-(2-picolyl)amine (DPA) Units - Rui Cao; Mengyu Zhang; Wen Tang; Jing Wu; Meixiang Wang; Xiaoxiao Niu; Zhaodi Liu; Fuying Hao; Huajie Xu (Journal of Fluorescence, 2023)

Selenium toxicity and bioaccumulation in selenium-enriched fly (Chrysomya megacephala) maggots - Rui Jie Peng; Chao Zheng; Zhan Biao Yang; Xiao Xun Xu; Ming Hung Wong; Yu Bon Man; Zhang Cheng (Environmental Geochemistry and Health, 2023)

Removal of toilet paper fibers from residential wastewater: a life cycle assessment - Xiaoyu Wang; Guoqiang Liu; Weimin Sun; Zhiguo Cao; Huaqing Liu; Yiqun Xiong; Baoqin Li; Xiaoxu Sun; Yongbin Li; Rui Xu; Duanyi Huang; Pin Gao (Environmental Science and Pollution Research, 2023)

FHB resistance conferred by Fhb1 is under inhibitory regulation of two genetic loci in wheat (Triticum aestivum L.) - Guoqiang Li; Yang Yuan; Jiyang Zhou; Rui Cheng; Ruitong Chen; Xianmin Luo; Jinxing Shi; Heyu Wang; Boyang Xu; Youyu Duan; Jinkun Zhong; Xin Wang; et al. (Theoretical and Applied Genetics, 2023)

Correction to: Inhibition of mGluR5 alters BDNF/TrkB and GLT‑1 expression in the prefrontal cortex and hippocampus and ameliorates PTSD‑like behavior in rats - Shuyue Cheng; Jingjing Xu; Wei Wang; Rui Wang; Haonan Li; Zhijun Jiang; Dexiang Liu; Fang Pan (Psychopharmacology, 2023)

Design, synthesis and mechanism study of novel natural-derived isoquinoline derivatives as antifungal agents - Wei Chen; Rui Zhang; Yang Chen; Pingbing Yu; Yuxin Lan; Haojian Xu; Simin Lei (Molecular Diversity, 2023)

The role of Nod-like receptor protein 3 inflammasome activated by ion channels in multiple diseases - Xiaolin Xu; Xianli Wu; Gengyu Yue; Qimin An; Jun Lou; Xiaoxu Yang; Zhe Jin; Jianhong Ding; Yanxia Hu; Qian Du; Jingyu Xu; Rui Xie (Molecular and Cellular Biochemistry, 2023)
The inflammasome is a multimeric protein complex located in the cytoplasm that is activated by many factors and subsequently promotes the release of proinflammatory factors such as interleukin (IL)-1β and IL-18, resulting in a series of inflammatory responses that ultimately lead to the occurrence of various diseases. The Nod-like receptor protein 3 (NLRP3) inflammasome is the most characteristic type and the most widely studied among many inflammasomes. Activation of the NLRP3 inflammasome is closely related to the occurrence of many diseases, such as Alzheimer's disease. At present, a large number of studies have focused on the mechanisms underlying the activation of the NLRP3 inflammasome. Plenty of articles have reported the activation of the NLRP3 inflammasome by various ions, such as K + and Na + reflux and Ca 2+ influx. However, few articles have reviewed the effects of various ion channels on the activation of the NLRP3 inflammasome and the relationship between the diseases caused by these proteins. This article mainly summarizes the relationship between intracellular and extracellular ion activities and ion channels and the activation of the NLRP3 inflammasome. We also provide a general summary of the diseases of each system caused by NLRP3 activation. We hope that more research will provide options for the treatment of diseases driven by the NLRP3 inflammasome.

New methylene blue-mediated photodynamic inactivation of multidrug-resistant Fonsecaea nubica infected chromoblastomycosis in vitro - Mengxue Zheng; Xiaoqing Zhou; Jiayin Pang; Zengjun Yang; Yongzhen Zou; Lian Zhang; Yan Xu; Rui Yin (Brazilian Journal of Microbiology, 2023)

Rhizospheric soil organic carbon accumulated but its molecular groups redistributed via rhizospheric soil microorganisms along multi-root Cerasus humilis plantation chronosequence at the karst rocky desertification control area - Qin Tang; Qiang Li; Lingchen Tong; Rui Wu; Jiao Xu (Environmental Science and Pollution Research, 2023)

Extracellular Vesicles from NMN Preconditioned Mesenchymal Stem Cells Ameliorated Myocardial Infarction via miR-210-3p Promoted Angiogenesis - Yanan Pu; Chunyu Li; Xin Qi; Rui Xu; Liyang Dong; Yi Jiang; Qingyun Gong; Di Wang; Rong Cheng; Cheng Zhang; Yan Chen (Stem Cell Reviews and Reports, 2023)
Mesenchymal stem cell-derived extracellular vesicles (MSCs-EVs) possess cardioprotection in acute myocardial infarction. Nevertheless, the therapeutic intervention potential and the molecular mechanism of EVs from NMN (Nicotinamide mononucleotide) preconditioned hUCMSCs (N-EVs) in acute myocardial infarction remains unknown. In the present study, EVs from hUCMSCs (M-EVs) and N-EVs were identified by electron microscopy, immunoblotting and nanoparticle tracking analysis. Compared with M-EVs, N-EVs significantly increased the proliferation, migration, and angiogenesis of HUVECs. Meanwhile, N-EVs markedly reduced apoptosis and cardiac fibrosis and promoted angiogenesis in the peri-infarct region in the MI rats. A high-throughput miRNA sequencing and qPCR methods analysis revealed that miR-210-3p was abundant in N-EVs and the expression of miR-210-3p was obviously upregulated in HUVECs after N-EVs treated. Overexpression of miR-210-3p in HUVECs significantly enhanced the tube formation, migration and proliferative capacities of HUVECs. However, downregulation of miR-210-3p in HUVECs markedly decreased the tube formation, migration and proliferative capacities of HUVECs. Furthermore, bioinformatics analysis and luciferase assays revealed that EphrinA3 (EFNA3) was a direct target of miR-210-3p. Knockdown of miR-210-3p in N-EVs significantly impaired its ability to protect the heart after myocardial infarction. Altogether, these results indicated that N-EVs promoted the infarct healing through improvement of angiogenesis by miR-210-3p via targeting the EFNA3. Graphical Abstract Created with Biorender.com.

Biomarkers of aging - Hainan Bao; Jiani Cao; Mengting Chen; Min Chen; Wei Chen; Xiao Chen; Yanhao Chen; Yu Chen; Yutian Chen; Zhiyang Chen; Jagadish K. Chhetri; Yingjie Ding; et al. (Science China Life Sciences, 2023)

Increased hypertension risk for the elderly with high blood levels of strontium and lead - Jiebao Zhang; Chunfang Xu; Yan Guo; Xingyi Jin; Zi Cheng; Qi Tao; Lin Liu; Rui Zhan; Xuemin Yu; Hongjuan Cao; Fangbiao Tao; Jie Sheng; et al. (Environmental Geochemistry and Health, 2023)

A systematic knowledge pedigree analysis on green governance - Rui Yang; Yingwen Chen; Jie Zhong; Yujin Xu; Xin An (Environment, Development and Sustainability, 2023)

Comparison and Investigation of Exosomes from Human Amniotic Fluid Stem Cells and Human Breast Milk in Alleviating Neonatal Necrotizing Enterocolitis - Xiaohan Hu; Rui Zhang; Hansi Liang; Jingnan An; Yuan Yang; Jie Huo; Zhenjiang Chen; Wei Quan; Lu Jiang; Cancan Li; Jian Li; Fang Li; et al. (Stem Cell Reviews and Reports, 2023)
In view of the devastating impact of neonatal necrotizing enterocolitis (NEC) on newborns, the research on its intervention is particularly important. Although exosomes from human amniotic fluid stem cells (AFSC) and human breast milk (HBM) can protect against NEC, their mechanisms remain unclear. Here, we intend to compare the intervention effects of two types of exosomes on NEC mouse model and reveal their respective regulatory mechanisms. In general, both AFSC-derived exosomes (AFSC-exos) and HBM-derived exosomes (HBM- exos) can alleviate NEC- associated intestinal injury, significantly reduce NEC score, and reduce systemic and ileal inflammation and NEC related brain injury during experimental NEC. However, the mode and mechanism of action of the two sources of exosomes were not identical. In vivo, the number of ileal crypts was more significantly restored after HBM-exos intervention than AFSC-exos, and in vitro, HBM-exos preferentially inhibited the inflammatory response of intestinal epithelial cells (IECs), whereas AFSC-exos preferentially regulated the migration of IECs. Mechanistically, GO and KEGG analyses revealed the different therapeutic mechanisms of AFSC-exos and HBM-exos in NEC. Taken together, our results illustrate that AFSC-exos and HBM-exos reduce the severity of experimental NEC and intestinal damage through different mechanisms, supporting the potential of cell-free or breast milk free exosome therapy for NEC. Graphical Abstract

Inhibition of mGluR5 alters BDNF/TrkB and GLT-1 expression in the prefrontal cortex and hippocampus and ameliorates PTSD-like behavior in rats - Shuyue Cheng; Jingjing Xu; Wei Wang; Rui Wang; Haonan Li; Zhijun Jiang; Dexiang Liu; Fang Pan (Psychopharmacology, 2023)

Interaction Between the Glymphatic System and α-Synuclein in Parkinson’s Disease - Yu Zhang; Cui Zhang; Xu-Zhong He; Zhen-Hua Li; Jing-Cai Meng; Rui-Ting Mao; Xin Li; Rong Xue; Qian Gui; Guo-Xing Zhang; Lin-Hui Wang (Molecular Neurobiology, 2023)

Activating α7nAChR helps post-myocardial infarction healing by regulating macrophage polarization via the STAT3 signaling pathway - Xiao-Hui Niu; Rong-Hua Liu; Xiao Lv; Rui-Lin He; Fang-Zhou Lv; Shu-Jie Wu; Xu-Qing Li; Lei Li; Jia-Feng Lin (Inflammation Research, 2023)

Changes in the Microbiota and their Roles in Patients with Type 2 Diabetes Mellitus - Qiao-ling He; Hui-chao Wang; Yu-ke Ma; Rui-lin Yang; Zhi-feng Dai; Jing-nan Yang; Yao Xu; Dan-dan Wei; Li-ping Zhu; Xu-hong Lin (Current Microbiology, 2023)

Repetitive transcranial magnetic stimulation enhances the neuronal excitability of mice by regulating dynamic characteristics of Granule cells’ Ion channels - Haijun Zhu; Xiaonan Yin; Huilan Yang; Rui Fu; Wentao Hou; Chong Ding; Guizhi Xu (Cognitive Neurodynamics, 2023)

Energy and environmental performance evaluation of China's non-ferrous metals industry from the perspective of network structure - Rui Yang; Yujin Xu; Kaiyuan Liu (Clean Technologies and Environmental Policy, 2023)

Sandstorms damage the photosynthetic activities of Haloxylon ammodendron seedlings - Shengbo Shi; Dangwei Zhou; Rui Shi; Tao Sun; Fanglin Wang; Xiuzhen Gao; Yunian Zhang; Peng Zhao; Gaoxing Xu; Jinnian Tang (Acta Physiologiae Plantarum, 2023)
Haloxylon ammodendron is a preferred shrub species for buffering against wind and fixing sand in arid sandy areas of northwest China. To determine whether sandstorms cause damage to H. ammodendron seedlings, we investigated the effects of wind-blown sands on the photosynthetic function of H. ammodendron by simulating sand-carrying wind in the wind tunnel. The results showed that photosystem II (PSII) non-photochemical quenching ( NPQ ) was sensitive to wind erosion, and sustained blowing of sand-carrying winds enhanced NPQ reduction. The rapidly relaxing quenching NPQ f made up the majority component of NPQ ; the NPQ f / NPQ ratio was approximately 64.4% in the sand-free wind group and nearly 56.2% in the sand-carrying wind group. The distribution of the quantum efficiency of the excitation energy indicated that the relative proportions of the quantum yield of PSII photochemistry Φ PSII , the quantum yield of quenching due to light-induced Φ NPQ , and non-light-induced Φ NO were influenced by both wind erosion and light intensity; the sand-carrying wind resulted in a relative decrease in Φ NPQ and a corresponding increase in Φ NO . The maximum quantum efficiency of PSII photochemistry F v / F m was relatively stable in the sand-free wind group, with an average value of approximately 0.81. Compared to sand-free wind, sand-carrying winds caused remarkable decreases in F v / F m . Light intensity was the main factor affecting Φ PSII , Φ NPQ , and relative electron transport rate ( rETR ); there was no interaction effect between the duration of sand-carrying wind and light intensity. Taken together, wind-blown sands cause irreversible damage to the photosynthesis of H. ammodendron seedlings, which is the main factor restricting population regeneration in shelterbelts.

Diffusion simulation and risk assessment model establishment of chlorine gas leakage based on terrain conditions - Xiao-ting Ren; Xiao-ling Ma; Jiang-zheng Liu; Rui Liu; Chen-qian Zhao; Hao Wu; Zhao Wang; Chun-xu Hai; Xiao-di Zhang (Environmental Science and Pollution Research, 2023)

Particle sorting to improve the removal of fluoride and aluminum nitride from secondary aluminum dross by roasting - Huimin Xie; Zhaohui Guo; Rui Xu; Yanglin Zhang (Environmental Science and Pollution Research, 2023)

The circadian regulation of extracellular ATP - Xin Wang; Yu-Ting Dong; Xiu-Ming Hu; Ji-Zhou Zhang; Nan-Rui Shi; Yan-Qin Zuo; Xu Wang (Purinergic Signalling, 2023)
Extracellular ATP is a potent signaling molecule released from various cells throughout the body and is intimately involved in the pathophysiological functions of the nervous system and immune system by activating P2 purinergic receptors. Recent increasingly studies showed that extracellular ATP exhibits circadian oscillation with an approximately 24-h periodicity, which participates in regulatory pathways of central oscillator suprachiasmatic nucleus and peripheral oscillator bladder, respectively. Oscillators modulate the protein expression of ATP release channels and ectonucleotidase activity through clock genes; indeed, real-time alterations of ATP release and degradation determine outcomes of temporal character on extracellular ATP rhythm. The regulatory pathways on extracellular ATP rhythm are different in central and peripheral systems. In this review, we summarize the circadian rhythm of extracellular ATP and discuss several circadian regulatory pathways in different organs via ATP release and degradation, to provide a new understanding for purinergic signaling in the regulatory mechanism of circadian rhythm and a potential target to research the circadian regulation of extracellular ATP in other circadian oscillators.

Tet Enzyme-Mediated Response in Environmental Stress and Stress-Related Psychiatric Diseases - Meiling Xia; Rui Yan; Myoung-Hwan Kim; Xingshun Xu (Molecular Neurobiology, 2023)

Effects of Alpine Grassland Degradation on Soil Microbial Communities in Qilian Mountains of China - Chunming Li; Derong Zhang; Gengchun Xu; Rui Yan; Yang Huang; Liuqing Feng; Jin Yi; Xiangyu Xue; Huixia Liu (Journal of Soil Science and Plant Nutrition, 2023)

Quantitative estimation of bubble volume fraction of submarine seep plumes by modeling seismic oceanography data - Tonggang Han; Jiangxin Chen; Leonardo Azevedo; Bingshou He; Huaning Xu; Rui Yang (Journal of Oceanology and Limnology, 2023)

rTFPI Protects Cardiomyocytes from Hypoxia/Reoxygenation Injury through Inhibiting Autophagy and the Class III PI3K/Beclin-1 Pathway - Runan Yan; Wei Gao; Wenjia Chen; Yue Liu; Li Shen; Yue Dai; Rui Xu; Qing Chang; Yu Fu; Yong Zhao (Cell Biochemistry and Biophysics, 2023)

Combined effects of fluoroquinolone antibiotics and organophosphate flame retardants on Microcystis aeruginosa - Yang Zhao; Yingping Huang; Shuang Hu; Tao Xu; Yanfen Fang; Huigang Liu; Ying Xi; Rui Qu (Environmental Science and Pollution Research, 2023)

Effects of Acidification on the Wettability Modification of Coal and Adsorption Characteristics of Coalbed Methane - Rui Zhang; Mei Yuan; Bobo Li; Zhaoping Li; Qing Lv; Shiqing Xu (Natural Resources Research, 2023)

Electroacupuncture promotes remyelination and alleviates cognitive deficit via promoting OPC differentiation in a rat model of subarachnoid hemorrhage - Yingwen Wang; Xiaomin Yang; Yunchuan Cao; Xiaoguo Li; Rui Xu; Jin Yan; Zongduo Guo; Shanquan Sun; Xiaochuan Sun; Yue Wu (Metabolic Brain Disease, 2023)

Investigation of lake shrinkage attributed to climate change over the past 33 years in Inner Mongolia, China - Yanfei Zhang; Zilong Liao; Xiaomin Xu; Wentao Liang; Zhenhua Han; Gang Ji; Rui Jiao (Climatic Change, 2023)

Spatio-temporal variation prediction on Cd content in the rice grains from Northern Zhejiang Plain during 2014–2019 based on high-precision soil geochemical data - Hanqin Yin; Xinzhe Lu; Rui Sun; Chunlei Huang; Zhanjun Kang; Mingxing Xu; Yingchun Wei; ZiHua Cai (Journal of Geographical Sciences, 2023)

Effects of bepridil on early cardiac development of zebrafish - Ya-Lan Wei; Yu-Qing Lei; Zhou-Jie Ye; Xu-Dong Zhuang; Li-Ping Zhu; Xin-Rui Wang; Hua Cao (Cell and Tissue Research, 2023)

Effects of single or conjoint administration of lactic acid bacteria as potential probiotics on the growth, immune responses, and disease resistance of Carassius auratus - Ruoming Li; Teng Chi; Qing Xu; Juntong Liu; Xiaofeng Shan; Rui Zhou; Jiayun Yao; Wuwen Sun; Guiqin Wang (Aquaculture International, 2023)

Kingella pumchi sp. nov., an organism isolated from human vertebral puncture tissue - Meng Xiao; Ruina Liu; Juan Du; Rui Liu; Lei Zhai; He Wang; Su Yao; Ying-Chun Xu (Antonie van Leeuwenhoek, 2023)

First report of Cytospora tritici causing branch canker on English walnut in China - Shasha Xu; Rui Zhang; Deying Sun; Tiansheng Zhu; Xiaowei Chen; Xiaofei Chen; Xiaofei Chen (Journal of Plant Pathology, 2023)

Effects of chemical additives and mature compost on reducing nitrogen loss during food waste composting - Shangao Xiong; Yongdi Liu; Hao Zhang; Shaoqi Xu; Songrong Li; Xinqi Fan; Rui Chen; Guochun Ding; Ji Li; Yuquan Wei (Environmental Science and Pollution Research, 2023)

Plant-associated Microbe System in Treatment of Heavy Metals–contaminated Soil: Mechanisms and Applications - Zhiming Ren; Rui Cheng; Peng Chen; Yuanyuan Xue; Hong Xu; Yao Yin; Guangtuan Huang; Wei Zhang; Lehua Zhang (Water, Air, & Soil Pollution, 2023)

Positional cloning identified HvTUBULIN8 as the candidate gene for round lateral spikelet (RLS) in barley (Hordeum vulgare L.) - Dandan Qin; Gang Liu; Rui Liu; Chunchao Wang; Fuchao Xu; Qing Xu; Yu Ling; Guoqing Dong; Yanchun Peng; Shuangtao Ge; Ganggang Guo; Jing Dong; et al. (Theoretical and Applied Genetics, 2023)
Key message Map-based cloning, subcellular localization, virus-induced-gene-silencing and transcriptomic analysis reveal HvTUB8 as a candidate gene with pleiotropic effects on barley spike and leaf development via ethylene and chlorophyll metabolism. Abstract Barley lateral spikelet morphology and grain shape play key roles in grain physical quality and yield. Several genes and QTLs for these traits have been cloned or fine mapped previously. Here, we report the phenotypic and genotypic analysis of a barley mutant with round lateral spikelet (rls) from cv. Edamai 934. rls had round lateral spikelet, short but round grain, shortened awn, thick glume and dark green leaves. Histocytologic and ultrastructural analysis revealed that the difference of grain shape of rls was caused by change of cell arrangement in glume, and the dark leaf color resulted from enlarged chloroplast. HvTUBULIN8 ( HvTUB8 ) was identified as the candidate gene for rls by combination of RNA-Seq, map-based-cloning, virus-induced-gene-silencing (VIGS) and protein subcellular location. A single G-A substitution at the third exon of HvTUB8 resulted in change of Cysteine 354 to tyrosine. Furthermore, the mutant isoform Hvtub8 could be detected in both nucleus and cytoplasm, whereas the wild-type protein was only in cytoplasm and granular organelles of wheat protoplasts. Being consistent with the rare phenotype, the “A” allele of HvTUB8 was only detected in rls , but not in a worldwide barley germplasm panel with 400 accessions. VIGS confirmed that HvTUB8 was essential to maintain spike integrity. RNA-Seq results suggested that HvTUB8 may control spike morphogenesis via ethylene homeostasis and signaling, and control leaf color through chlorophyll metabolism. Collectively, our results support HvTUB8 as a candidate gene for barley spike and leaf morphology and provide insight of a novel mechanism of it in barley development.

Expression of phenylalanine ammonia lyase as an intracellularly free and extracellularly cell surface-immobilized enzyme on a gut microbe as a live biotherapeutic for phenylketonuria - Yu Jiang; Bingbing Sun; Fenghui Qian; Feng Dong; Chongmao Xu; Wuling Zhong; Rui Huang; Qiwei Zhai; Yu Jiang; Sheng Yang (Science China Life Sciences, 2023)

Clinical Decision on Disorders of Consciousness After Acquired Brain Injury: Stepping Forward - Rui-Zhe Zheng; Zeng-Xin Qi; Zhe Wang; Ze-Yu Xu; Xue-Hai Wu; Ying Mao (Neuroscience Bulletin, 2023)

LncRNA as potential biomarker and therapeutic target in glioma - Xun Xu; Yuan Liang; Ilgiz Gareev; Yanchao Liang; Rui Liu; Ning Wang; Guang Yang (Molecular Biology Reports, 2023)

The draft genome sequence and characterization of Exserohilum rostratum, a new causal agent of maize leaf spot disease in Chinese Mainland - Qingzhou Ma; Chongyang Cheng; Yuehua Geng; Rui Zang; Yashuang Guo; Lixin Yan; Chao Xu; Meng Zhang; Haiyan Wu (European Journal of Plant Pathology, 2023)

Leaching and characterization studies of heavy metals in contaminated soil using sequenced reagents of oxalic acid, citric acid, and a copolymer of maleic and acrylic acid instead of ethylenediaminetetraacetic acid - Eric Tindanzor; Zhaohui Guo; Tianshuang Li; Rui Xu; Xiyuan Xiao; Chi Peng (Environmental Science and Pollution Research, 2023)

Correction to: Characterization of keystone taxa and microbial metabolic potentials in copper tailing soils - Qiao Fan; Yeqiang Chen; Rui Xu; Zhaohui Guo (Environmental Science and Pollution Research, 2023)

China’s carbon dioxide emission forecast based on improved marine predator algorithm and multi-kernel support vector regression - Xiwen Qin; Siqi Zhang; Xiaogang Dong; Yichang Zhan; Rui Wang; Dingxin Xu (Environmental Science and Pollution Research, 2023)

Application of chelate GLDA for remediating Cd-contaminated farmlands using Tagetes patula L. - Hongchuan Li; Rui Jin; Zhaowen Xu; Hongxiang Hu; Yusef Kianpoor Kalkhajeh; Yingying Zhao; Linchuan Zhan (Environmental Science and Pollution Research, 2023)

The impact of natural disasters on household debt: evidence from 2014 China family panel studies - Rui Zhang; Sheng Xu; Ruidong Sun (Environmental Science and Pollution Research, 2023)

Characterization of keystone taxa and microbial metabolic potentials in copper tailing soils - Qiao Fan; Yeqiang Chen; Rui Xu; Zhaohui Guo (Environmental Science and Pollution Research, 2023)

Selenite Ameliorates Cadmium-induced Cytotoxicity Through Downregulation of ROS Levels and Upregulation of Selenoprotein Thioredoxin Reductase 1 in SH-SY5Y Cells - Hecheng Wang; Shibo Sun; Yan Ren; Rui Yang; Jianli Guo; Yu Zong; Qiuxian Zhang; Jing Zhao; Wei Zhang; Weiping Xu; Shui Guan; Jianqiang Xu (Biological Trace Element Research, 2023)

Crosstalk between exosomes and autophagy in spinal cord injury: fresh positive target for therapeutic application - Rui-yu Li; Qi Hu; Xu Shi; Zhen-yu Luo; Dong-hua Shao (Cell and Tissue Research, 2023)
Spinal cord injury (SCI) is a very serious clinical traumatic illness with a very high disability rate. It not only causes serious functional disorders below the injured segment, but also causes unimaginable economic burden to social development. Exosomes are nano-sized cellular communication carriers that exist stably in almost all organisms and cell types. Because of their capacity to transport proteins, lipids, and nucleic acids, they affect various physiological and pathological functions of recipient cells and parental cells. Autophagy is a process that relies on the lysosomal pathway to degrade cytoplasmic proteins and organelles and involves a variety of pathophysiological processes. Exosomes and autophagy play critical roles in cellular homeostasis following spinal cord injury. Presently, the coordination mechanism of exosomes and autophagy has attracted much attention in the early efficacy of spinal cord injury. In this review, we discussed the interaction of autophagy and exosomes from the perspective of molecular mechanisms, which might provide novel insights for the early therapeutic application of spinal cord injury.

Establishment and comprehensive analysis of a new human cell line (NK-NJ) with NK-cell characteristics established from extranodal natural killer cell lymphoma/leukemia - Jin-Hua Liang; Wei-Ting Wang; Kai-Xin Du; Tong-Yao Xing; Yan Wang; Hui Wang; Lu Liu; Rui Guo; Yang Shao; Junheng Liang; Yue Li; Hao-Rui Shen; et al. (Human Cell, 2022)

Multiple MicroRNAs are Involved in Regulating Peanut (Arachis hypogaea L.) Resistance to Sclerotium rolfsii at the Early Stage - Yongju Xu; Xiaojun Zhang; Rui Hou; Xiaohong Zhang; Shuang Li; Fuliang Yue; Xiangqiong Zhang; Xunlu Zhu (Tropical Plant Biology, 2022)

Applying and Integrating Urban Contamination Factors into Community Garden Siting - Katie R. Kirsch; Galen D. Newman; Rui Zhu; Thomas J. McDonald; Xiaohui Xu; Jennifer A. Horney (Journal of Geovisualization and Spatial Analysis, 2022)

Site-directed RNA editing by harnessing ADARs: advances and challenges - Ming Li; Cheng Yan; Yue Jiao; Yuqin Xu; Chen Bai; Rui Miao; Jiying Jiang; Jiao Liu (Functional & Integrative Genomics, 2022)

Temperature-dependent development and reproduction of Tarsonemus confusus (Acari: Tarsonemidae): an important pest mite of horticulture - Litao Li; Lichen Yu; Limin He; Xiong Zhao He; Rui Jiao; Changxin Xu (Experimental and Applied Acarology, 2022)

Oxidative stress and inflammation caused by 1-tetradecyl-3-methylimidazolium tetrafluoroborate in rat livers - Huafei Yuan; Feng Xu; Xingxing Tian; Haiyan Wei; Rui Zhang; Yueyue Ge; Hongmei Xu (Environmental Science and Pollution Research, 2022)

Effects of snow absence on available N pools and enzyme activities within soil aggregates in a spruce forest on the eastern Tibetan Plateau - Zhijie Li; Rüdiger Reichel; Zimin Li; Kaijun Yang; Li Zhang; Bo Tan; Rui Yin; Kerui Zhao; Zhenfeng Xu (Soil Ecology Letters, 2022)

An improved bicubic imaging fitting algorithm for 3D radar detection target - Fan-Ruo Li; Feng Yang; Rui Yan; Qiao Xu; Yi-Jin Li; Hong-Jia Xing (Applied Geophysics, 2022)

The integrated exposure assessment and potential risks of five organophosphorus pesticides in vegetables in Zhejiang, China (2018–2020) - Quan Zhang; Rui Cao; Tao Tang; Zeteng Ying; Shitao Hu; Yitian Xu (Environmental Science and Pollution Research, 2022)

Enhancing extracellular electron transfer through selective enrichment of Geobacter with Fe@CN-modified carbon-based anode in microbial fuel cells - Xiao-Long Cheng; Qiang Xu; Qian-Wen Yang; Rui-Rui Tian; Biao Li; Su Yan; Xue-Ying Zhang; Jun Zhou; Xiao-Yu Yong (Environmental Science and Pollution Research, 2022)

Burst Area Identification of Water Supply Network by Improved DenseNet Algorithm with Attention Mechanism - Jing Cheng; Sen Peng; Rui Cheng; Xingqi Wu; Xu Fang (Water Resources Management, 2022)

Modification of alternative splicing in bovine somatic cell nuclear transfer embryos using engineered CRISPR-Cas13d - Rui Cheng; Xiaoman Zheng; Yingmei Wang; Xing Ma; Xin Liu; Wenjun Xu; Mengyun Wang; Yuanpeng Gao; Xupeng Xing; Chuan Zhou; Hongzheng Sun; Zekun Guo; et al. (Science China Life Sciences, 2022)

ACC deaminase-encoding Pseudomonas putida arrests seed germination: an alternative strategy for grass and weed control - Di Zhou; Jia-Ling Zhao; Rui Wang; Hai-Lin Wang; Daniela D. Herrera-Balandrano; Tang-Min Chen; Xiao-Feng Lu; Xu-Chu Duan; Mahdi Shahriar; Xin-Chi Shi; Pedro Laborda; Su-Yan Wang (Plant and Soil, 2022)

Characterization of thermal conductivity of seasonally frozen turfy soil from Northeastern China - Yuanyuan He; Yan Xu; Yan Lv; Lei Nie; Xiaoting Feng; Tingting Liu; Tao Zhang; Yuzheng Wang; Chao Du; Xiangjian Rui; Fansheng Kong (Bulletin of Engineering Geology and the Environment, 2022)

Hedgehog pathway is negatively regulated during the development of Drosophila melanogaster PheRS-m (Drosophila homologs gene of human FARS2) mutants - Lidangzhi Mo; Rui Li; Chunxia He; Qi Chen; Changwei Xu; Liangliang Shen; Kun Chen; Yuanming Wu (Human Cell, 2022)

Neuronal Death Mechanisms and Therapeutic Strategy in Ischemic Stroke - Rui Mao; Ningning Zong; Yujie Hu; Ying Chen; Yun Xu (Neuroscience Bulletin, 2022)
Ischemic stroke caused by intracranial vascular occlusion has become increasingly prevalent with considerable mortality and disability, which gravely burdens the global economy. Current relatively effective clinical treatments are limited to intravenous alteplase and thrombectomy. Even so, patients still benefit little due to the short therapeutic window and the risk of ischemia/reperfusion injury. It is therefore urgent to figure out the neuronal death mechanisms following ischemic stroke in order to develop new neuroprotective strategies. Regarding the pathogenesis, multiple pathological events trigger the activation of cell death pathways. Particular attention should be devoted to excitotoxicity, oxidative stress, and inflammatory responses. Thus, in this article, we first review the principal mechanisms underlying neuronal death mediated by these significant events, such as intrinsic and extrinsic apoptosis, ferroptosis, parthanatos, pyroptosis, necroptosis, and autophagic cell death. Then, we further discuss the possibility of interventions targeting these pathological events and summarize the present pharmacological achievements.

Loss of Myomixer Results in Defective Myoblast Fusion, Impaired Muscle Growth, and Severe Myopathy in Zebrafish - Ping Wu; Pengzheng Yong; Zhanxiong Zhang; Rui Xu; Renjie Shang; Jun Shi; Jianshe Zhang; Pengpeng Bi; Elizabeth Chen; Shaojun Du (Marine Biotechnology, 2022)

Effect of winter feeding frequency on growth performance, biochemical blood parameters, oxidative stress, and appetite-related genes in Takifugu rubripes - Xiaoqiang Gao; Xinyi Wang; Xi Wang; Hongxu Li; Liang Xu; Yingying Fang; Shuquan Cao; Bin Huang; Haibin Chen; Rui Xing; Baoliang Liu (Fish Physiology and Biochemistry, 2022)

Clinical profiles and antimicrobial resistance patterns of invasive Salmonella infections in children in China - Wen Song; Qingwen Shan; Yue Qiu; Xianyao Lin; Chunhui Zhu; Zhiqiang Zhuo; Caihong Wang; Jianning Tong; Rui Li; Chaomin Wan; Yu Zhu; Minxia Chen; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2022)
Invasive Salmonella infections result in a significant burden of disease including morbidity, mortality, and financial cost in many countries. Besides typhoid fever, the clinical impact of non-typhoid Salmonella infections is increasingly recognized with the improvement of laboratory detection capacity and techniques. A retrospective multicenter study was conducted to analyze the clinical profiles and antimicrobial resistance patterns of invasive Salmonella infections in hospitalized children in China during 2016–2018. A total of 130 children with invasive Salmonella infections were included with the median age of 12 months (range: 1–144 months). Seventy-nine percent of cases occurred between May and October. Pneumonia was the most common comorbidity in 33 (25.4%) patients. Meningitis and septic arthritis caused by nontyphoidal Salmonella (NTS) infections occurred in 12 (9.2%) patients and 5 (3.8%) patients. Patients < 12 months (OR: 16.04) and with septic shock (OR: 23.4), vomit (OR: 13.33), convulsion (OR: 15.86), C-reactive protein (CRP) ≥ 40 g/L (OR: 5.56), and a higher level of procalcitonin (PCT) (OR: 1.05) on admission were statistically associated to an increased risk of developing meningitis. Compared to 114 patients with NTS infections , 16 patients with typhoid fever presented with higher levels of CRP and PCT ( P < 0.05). The rates of resistance to ampicillin, sulfamethoxazole/trimethoprim, ciprofloxacin, and ceftriaxone among Salmonella Typhi and NTS isolates were 50% vs 57.3%, 9.1% vs 24.8%, 0% vs 11.2%, and 0% vs 9.9%, respectively. NTS has been the major cause of invasive Salmonella infections in Chinese children and can result in severe diseases. Antimicrobial resistance among NTS was more common.

Integration of ABC curve, three dimensions of alpha diversity indices, and spatial patterns of fish assemblages into the health assessment of the Chishui River basin, China - Fandong Yu; Fei Liu; Zhijun Xia; Chunsen Xu; Jianwei Wang; Rui Tang; Zujun Ai; Youzhao Zhang; Miaomiao Hou; Xinhua Zou (Environmental Science and Pollution Research, 2022)

Outdoor air pollution exposure and the risk of asthma and wheezing in the offspring - Lei Hua; Liangliang Ju; Hanbing Xu; Changlian Li; Shu Sun; Qi Zhang; Jiyu Cao; Rui Ding (Environmental Science and Pollution Research, 2022)

Identification of Ferroptotic Genes in Spinal Cord Injury at Different Time Points: Bioinformatics and Experimental Validation - Yu Kang; Qiangwei Li; Rui Zhu; Shuang Li; Xin Xu; Xuanming Shi; Zongsheng Yin (Molecular Neurobiology, 2022)

Dynamic mechanical behavior of coral rock subjected to high strain rate loading - Houzhen Wei; Linjian Ma; Jiawen Wu; Jin Yu; Zeng Li; Rui Xu (Marine Geophysical Research, 2022)

Effects of perfluorooctanoic acid (PFOA) on activated sludge microbial community under aerobic and anaerobic conditions - Duanyi Huang; Rui Xu; Xiaoxu Sun; Yongbin Li; Enzong Xiao; Zhimin Xu; Qi Wang; Pin Gao; Zhaohui Yang; Hanzhi Lin; Weimin Sun (Environmental Science and Pollution Research, 2022)

Optimization of the induction, germination, and plant regeneration system for somatic embryos in apomictic walnut (Juglans regia L.) - Hongcheng Fang; Yuhui Dong; Rui Zhou; Qingpeng Wang; Qicheng Duan; Changxi Wang; Yan Bao; Shengyi Xu; Xinya Lang; Shasha Gai; Rong Chen; Ke Qiang Yang (Plant Cell, Tissue and Organ Culture (PCTOC), 2022)

Proteomic analysis of coarse and fine skin tissues of Liaoning cashmere goat - Zhixian Bai; Yanan Xu; Ming Gu; Weidong Cai; Yu Zhang; Yuting Qin; Rui Chen; Yinggang Sun; Yanzhi Wu; Zeying Wang (Functional & Integrative Genomics, 2022)

Effects of biochar underwent different aging processes on soil properties and Cd passivation - Juanjuan Qu; Xu Zhang; Qingkai Guan; Linghui Kong; Rui Yang; Xianfa Ma (Environmental Science and Pollution Research, 2022)

Longitalea arenae gen. nov., sp. nov. and Longitalea luteola sp. nov., two new members of the family Chitinophagaceae isolated from desert soil - Shuai Li; Lei Dong; Jia-Rui Han; Guo-Yuan Shi; Chun-Yan Lu; Lu Xu; Wen-Hui Lian; Dalal Hussien M. Alkhalifah; Wael N. Hozzein; Wen-Jun Li (Archives of Microbiology, 2022)

Development of Solid-State Anaerobic Digestion and Aerobic Composting Hybrid Processes for Organic Solid Waste Treatment and Resource Recovery: a Review - Chuanren Qi; Rongrong Yin; Xingzu Gao; Jie Chen; Rui Wang; Zhicheng Xu; Wenhai Luo; Guoxue Li; Yangyang Li (Current Pollution Reports, 2022)

Metatranscriptomic analysis of host response and vaginal microbiome of patients with severe COVID-19 - Meng Xiao; Bo Lu; Rui Ding; Xia Liu; Xian Wu; Yaqian Li; Xudong Liu; Lin Qiu; Zhibo Zhang; Jing Xie; Yu Chen; Dong Zhang; et al. (Science China Life Sciences, 2022)

A study on the infection status and transmission of avian leukosis virus subgroup J in Hy-line brown roosters - Fanfeng Meng; Qiuchen Li; Rui Han; Guanlong Xu; Xintao Gao; Fubing Luo; Guangnian Shen; Xiaodong Liu; Zhifang Zhang; Peng Zhao; Guozhong Zhang (Archives of Virology, 2022)

Investigation of present-day in situ stresses in a shale gas reservoir of Sichuan Basin, China: field measurement, stress field modeling, and engineering implications - Rui Yong; Jianfa Wu; Yi Song; Ersi Xu; Bin Xu; Quanzhou Wang; Lingke Wu (Arabian Journal of Geosciences, 2022)

Impacts of Topographic Complexity on Modeling Moisture Transport and Precipitation over the Tibetan Plateau in Summer - Gudongze Li; Haoming Chen; Mingyue Xu; Chun Zhao; Lei Zhong; Rui Li; Yunfei Fu; Yanhong Gao (Advances in Atmospheric Sciences, 2022)
The non-hydrostatic global variable resolution model (MPAS-atmosphere) is used to conduct the simulations for the South Asian Summer monsoon season (June, July, and August) in 2015 with a refinement over the Tibetan Plateau (TP) at the convection-permitting scale (4 km). Two experiments with different topographical datasets, complex (4-km) and smooth (60-km) topography, are designed to investigate the impacts of topographical complexity on moisture transport and precipitation. Compared with the observations and reanalysis data, the simulation can successfully capture the general features of key meteorological fields over the TP despite slightly underestimating the inflow through the southern TP. The results indicate that the complex topography can decrease the inward and outward moisture transport, ultimately increasing the total net moisture transport into the TP by ∼11%. The impacts of complex topography on precipitation are negligible over the TP, but the spatial distributions of precipitation over the Himalayas are significantly modulated. With the inclusion of complex topography, the sharper southern slopes of the Himalayas shift the lifted airflow and hence precipitation northward compared to the smooth topography. In addition, more small-scale valleys are resolved by the inclusion of complex topography, which serve as channels for moisture transport across the Himalayas, further favoring a northward shift of precipitation. Overall, the difference between the two experiments with different topography datasets is mainly attributed to their differing representation of the degree of the southern slopes of the Himalayas and the extent to which the valleys are resolved.

Impact of N application rate on tea (Camellia sinensis) growth and soil bacterial and fungi communities - Sheng Tang; Jingjie Zhou; Wankun Pan; Rui Tang; Qingxu Ma; Meng Xu; Tong Qi; Zhengbo Ma; Haoran Fu; Lianghuan Wu (Plant and Soil, 2022)

Spirulina platensis aqueous extracts ameliorate colonic mucosal damage and modulate gut microbiota disorder in mice with ulcerative colitis by inhibiting inflammation and oxidative stress - Jian Wang; Liqian Su; Lun Zhang; Jiali Zeng; Qingru Chen; Rui Deng; Ziyan Wang; Weidong Kuang; Xiaobao Jin; Shuiqing Gui; Yinghua Xu; Xuemei Lu (Journal of Zhejiang University-SCIENCE B, 2022)

The interplay of particle properties and solution chemistry on aggregation kinetics of soil nanoparticles - Ning Hu; Chen-yang Xu; Zeng-chao Geng; Fei-nan Hu; Qi-rui Li; Ren-tian Ma; Qiang Wang (Journal of Soils and Sediments, 2022)

China’s food security situation and key questions in the new era: A perspective of farmland protection - Xinyuan Liang; Xiaobin Jin; Bo Han; Rui Sun; Weiyi Xu; Hanbing Li; Jie He; Jin Li (Journal of Geographical Sciences, 2022)

Determination of the effective utilization coefficient of irrigation water based on geographically weighted regression - Rui Shi; Gaoxu Wang; Xuan Zhang; Yi Xu; Yongxiang Wu; Wei Wu (Frontiers of Earth Science, 2022)

Combining gradual and abrupt analysis to detect variation of vegetation greenness on the loess areas of China - Panxing He; Zongjiu Sun; Dongxiang Xu; Huixia Liu; Rui Yao; Jun Ma (Frontiers of Earth Science, 2022)

Combining double probability distribution functions to unmix bimodal grain-size distributions of sediments - Rui Xu; Rui Yuan; Donghui Li; Liang Xu; Mingfeng Gu (Arabian Journal of Geosciences, 2022)

Effects of dietary protein concentration on growth and anti-oxidant capacity of coho salmon Oncorhynchus kisutch (Walbaum, 1792) alevins - Cong-mei Xu; Hai-rui Yu; Qin Zhang; Ling-yao Li; Jing-jing Fan; Meng-jie Guo; Fang-hui Li; Xiang-yi Qiu; Ling-ling Shan (Aquaculture International, 2022)

Regulatory effects of Glycyrrhiza total flavones on fatty liver injury induced by a high-fat diet in tilapia (Oreochromis niloticus) via the Nrf2 and TLR signaling pathways - Jinliang Du; Rui Jia; Liping Cao; Zhengyan Gu; Qin He; Pao Xu; Guojun Yin; Yuzhong Ma (Aquaculture International, 2022)

Identification of PDXDC1 as a novel pleiotropic susceptibility locus shared between lumbar spine bone mineral density and birth weight - Yu-Qian Song; Shi-Di Hu; Xu Lin; Xiang-He Meng; Xiao Wang; Yin-Hua Zhang; Cheng Peng; Rui Gong; Tao Xu; Tong Zhang; Chen-Zhong Li; Dao-Yan Pan; et al. (Journal of Molecular Medicine, 2022)
An increasing number of epidemiological studies have suggested that birth weight (BW) may be a determinant of bone health later in life, although the underlying genetic mechanism remains unclear. Here, we applied a pleiotropic conditional false discovery rate (cFDR) approach to the genome-wide association study (GWAS) summary statistics for lumbar spine bone mineral density (LS BMD) and BW, aiming to identify novel susceptibility variants shared between these two traits. We detected 5 novel potential pleiotropic loci which are located at or near 7 different genes ( NTAN1 , PDXDC1 , CACNA1G , JAG1 , FAT1P1 , CCDC170 , ESR1 ), among which PDXDC1 and FAT1P1 have not previously been linked to these phenotypes. To partially validate the findings, we demonstrated that the expression of PDXDC1 was dramatically reduced in ovariectomized (OVX) mice in comparison with sham-operated (SHAM) mice in both the growth plate and trabecula bone. Furthermore, immunohistochemistry assay with serial sections showed that both osteoclasts and osteoblasts express PDXDC1 , supporting its potential role in bone metabolism. In conclusion, our study provides insights into some shared genetic mechanisms for BMD and BW as well as a novel potential therapeutic target for the prevention of OP in the early stages of the disease development. Key messages We investigated pleiotropy-informed enrichment between LS BMD and BW. We identified genetic variants related to both LS BMD and BW by utilizing a cFDR approach. PDXDC1 is a novel pleiotropic gene which may be related to both LS BMD and BW. Elevated expression of PDXDC1 is related to higher BMD and lower ratio n-6/n-3 PUFA indicating a bone protective effect of PDXDC1.

Hippocampal Activated Microglia May Contribute to Blood–Brain Barrier Impairment and Cognitive Dysfunction in Post-Traumatic Stress Disorder-Like Rats - Kun Ni; Jixiang Zhu; Xuan Xu; Yue Liu; Shuai Yang; Yulin Huang; Rui Xu; Li Jiang; Juan Zhang; Wei Zhang; Zhengliang Ma (Journal of Molecular Neuroscience, 2022)

Association between glucagon-like peptide-1 receptor gene polymorphism and treatment response to GLP1R agonists in Chinese patients with type 2 diabetes: a prospective cohort study - Ziwan Guan; Yue Du; Rui Li; Shufang Zhang; Yuedong Xu; Xiaoqian Zhang; Fan Zhang; Ying Yin; Kunrong Wu; Xiaoli Li; Yan Li (European Journal of Clinical Pharmacology, 2022)

Physiological homeostasis alteration and cellular structure damage of Chlorella vulgaris exposed to silver nanoparticles with various microstructural morphologies - Ningcan Deng; Haibo Li; Yinghua Li; Fan Mo; Mingshuai Wang; Zhe Li; Xi Chen; Jianing Xu; Rui Chai; Hongxuan Wang (Environmental Science and Pollution Research, 2022)

AT1 Receptors: Their Actions from Hypertension to Cognitive Impairment - Hanxue Wu; Qi Sun; Shenglan Yuan; Jiawei Wang; Fanni Li; Hongli Gao; Xingjuan Chen; Rui Yang; Jiaxi Xu (Cardiovascular Toxicology, 2022)

Correction to: Desiccation cracking in clay‑bottom ash mixtures: insights from crack image analysis and digital image correlation - Rui Liu; Mark Vail; Behrad Koohbor; Cheng Zhu; Chao‑Sheng Tang; Hao Xu; Xiang‑Chao Shi (Bulletin of Engineering Geology and the Environment, 2022)

Desiccation cracking in clay-bottom ash mixtures: insights from crack image analysis and digital image correlation - Rui Liu; Mark Vail; Behrad Koohbor; Cheng Zhu; Chao-Sheng Tang; Hao Xu; Xiang-Chao Shi (Bulletin of Engineering Geology and the Environment, 2022)

Polar Sea Ice Identification and Classification Based on HY-2A/SCAT Data - Rui Xu; Chaofang Zhao; Xiaochun Zhai; Ke Zhao; Jichang Shen; Ge Chen (Journal of Ocean University of China, 2022)

Experimental study on the mechanical properties and energy evolution of hard rock during water immersion - Fan-Bo Wei; Bing-Rui Chen; Rui Wang; Guo-Liang Li; Tao Li; Xu Wang; Xin-Hao Zhu (Arabian Journal of Geosciences, 2022)

Mechanism of Adipose-Derived Mesenchymal Stem Cell-Derived Extracellular Vesicles Carrying miR-21-5p in Hyperoxia-Induced Lung Injury - Yunfei Wu; Zhihui Zhang; Jun Li; Hai Zhong; Rui Yuan; Zihui Deng; Xu Wu (Stem Cell Reviews and Reports, 2022)

A two-phase comprehensive NSCLC prognostic study identifies lncRNAs with significant main effect and interaction - Jing Zhu; Jinxing Guan; Xinyu Ji; Yunjie Song; Xiaoshuang Xu; Qianqian Wang; Quanan Zhang; Renhua Guo; Rui Wang; Ruyang Zhang (Molecular Genetics and Genomics, 2022)
Long noncoding RNA (lncRNA) are involved in regulating physiological behaviors for various malignant tumors, including non-small-cell lung cancer (NSCLC). However, few studies comprehensively evaluated both lncRNA–lncRNA interaction effects and main effects of lncRNA on overall survival of NSCLC. Hence, we performed a two-phase designed study of lncRNA expression in tumor tissues using 604 NSCLC patients from The Cancer Genome Atlas as the discovery phase and 839 patients from Gene Expression Omnibus as the validation phase. In the discovery phase, we adopted a two-step strategy, Screening before Testing , for dimension reduction and signal detection. These candidate lncRNAs first screened out by the weighted random forest (Ranger), were then tested through the Cox proportional hazards model adjusted for covariates. Significant lncRNAs with either type of effects aforementioned were carried forward into the validation phase to confirm their significances again. As a result, in the discovery phase, 19 lncRNAs were identified by Ranger, among which five lncRNAs and one pair of lncRNA–lncRNA interaction exhibited significant effects (FDR- q ≤ 0.05) main and interaction effects on NSCLC survival, respectively, through Cox model. After the independent validation, we finally observed that one lncRNA (ENSG00000227403.1) with main effect was robustly associated with NSCLC prognosis ( HR discovery = 0.90, P = 1.20 × 10 –3 ; HR validation = 0.94, P = 4.11 × 10 –3 ) and one pair of lncRNAs (ENSG00000267121.4 and ENSG00000272369.1) had significant interaction effect on NSCLC survival ( HR discovery = 1.12, P = 3.07 × 10 –4 ; HR validation = 1.11, P = 0.0397). Our comprehensive NSCLC prognostic study of lncRNA provided population-level evidence for further functional study.

A Reliable Murine Model of Disseminated Infection Induced by Talaromyces Marneffei - Juan He; Jia-Sheng Li; Hong-Yan Xu; Yi-Qun Kuang; Jun Li; Hong-Bin Li; Zhe Li; Hui-Ling Zhou; Rui-Rui Wang; Yu-Ye Li (Mycopathologia, 2022)

Transcriptome Analysis Reveals Molecular Mechanisms Underlying Methyl Jasmonate-mediated Biosynthesis of Protopanaxadiol-type Saponins in Panax notoginseng Leaves - Ying Li; Yuan Lin; Bing Jia; Geng Chen; Huineng Shi; Rui Xu; Xuejiao Li; Junrong Tang; Qingyan Tang; Guanghui Zhang; Jianli Yang; Wei Fan; et al. (Journal of Plant Biology, 2022)

Molecular cloning and functional characterization of two squalene synthase genes in Atractylodes lancea - Junxian Wu; Rui Xu; Jimei Lu; Weiwei Liu; Hanwen Yu; Mengli Liu; Jing Li; Minzhen Yin; Huasheng Peng; Liangping Zha (Planta, 2022)

Mutual impacts and interactions of antibiotic resistance genes, microcystin synthetase genes, graphene oxide, and Microcystis aeruginosa in synthetic wastewater - Shichao Wu; Xiyan Ji; Xin Li; Jing Ye; Wenwu Xu; Rui Wang; Meifang Hou (Environmental Science and Pollution Research, 2022)

Chronic Ethanol Exposure Induces Deleterious Changes in Cardiomyocytes Derived from Human Induced Pluripotent Stem Cells - Rui Liu; Fangxu Sun; Lawrence C. Armand; Ronghu Wu; Chunhui Xu (Stem Cell Reviews and Reports, 2021)

A multi-dosing regimen to enhance the spatial memory of normal rats with α5-containing GABAA receptor negative allosteric modulator L-655,708 - Congcong Yuan; An Gao; Qiang Xu; Beibei Zhang; Rui Xue; Yan Dou; Chunshui Yu (Psychopharmacology, 2021)

Simvastatin Blocks Reinstatement of Cocaine-induced Conditioned Place Preference in Male Mice with Brain Lipidome Remodeling - Wei Xu; Yuman He; Jiamei Zhang; Hongchun Li; Xuemei Wan; Menglu Li; Yonghai Wang; Rui Xu; Haoluo Zhang; Yanping Dai; Haxiaoyu Liu; Linhong Jiang; et al. (Neuroscience Bulletin, 2021)

Fast and efficient correction for population stratification in multi-locus genome-wide association studies - Rui Liu; Min Yuan; Xu Steven Xu; Yaning Yang (Genetica, 2021)

The transcribed ultraconserved element uc.51 promotes the proliferation and metastasis of breast cancer by stabilizing NONO - Xiaoqing Shi; Xiaofeng Huang; Rui Chen; Yan Li; Yinggang Xu; Weiwei Zhang; Qiannan Zhu; Xiaoming Zha; Jue Wang (Clinical & Experimental Metastasis, 2021)

Selenium-Alleviated Testicular Toxicity by Modulating Inflammation, Heat Shock Response, and Autophagy Under Oxidative Stress in Lead-Treated Chickens - Size Wang; Lulu Hou; Min Wang; Rui Feng; Xu Lin; Shifeng Pan; Qian Zhao; He Huang (Biological Trace Element Research, 2021)

Establishment of an immortalized cell line derived from the pupal ovary of Mythimna separata (Lepidoptera: Noctuidae) and identification of the cell source - Yan Tong; Lu-Qiang Cheng; Xuan Li; Xu-Peng Yu; Rui-Hao Shu; Ji-Hong Zhang; Qian Meng; Qi-Lian Qin; Kai Tang; Jian-Xiang Xu; Huan Zhang (Cell and Tissue Research, 2021)

Altered gray matter volume in MRI-negative focal to bilateral tonic–clonic seizures - Honghao Xu; Haitao Zhu; Lei Luo; Rui Zhang (Acta Neurologica Belgica, 2021)

A New Instrumental Array in Sichuan, China, to Monitor Vibrations and Perturbations of the Lithosphere, Atmosphere, and Ionosphere - Chieh-Hung Chen; Yang-Yi Sun; Kai Lin; Chen Zhou; Rui Xu; Haiyin Qing; Yongxin Gao; Tao Chen; Fei Wang; Huaizhong Yu; Peng Han; Chi-Chia Tang; et al. (Surveys in Geophysics, 2021)

Loganin ameliorates depression-like behaviors of mice via modulation of serotoninergic system - Chen-Hao Pan; Cong-Yuan Xia; Yu Yan; Yan Han; Rui Shi; Jun He; Ze-Xing Wang; Yu-Ming Wang; Wei-Ku Zhang; Jie-Kun Xu (Psychopharmacology, 2021)

A drug–biomarker interaction model to predict the key targets of Scutellaria barbata D. Don in adverse-risk acute myeloid leukaemia - Teng Wang; Chun-yi Lyu; Yue-hua Jiang; Xue-yan Dong; Yan Wang; Zong-hong Li; Jin-xin Wang; Rui-rong Xu (Molecular Diversity, 2021)

Mechanism of environmental factors regulating water consumption of Larix gmelinii forests - Xin Zhang; Qiuliang Zhang; Zhihong Xu; Rui Wang; Yanan Jian; Jingfu Yang; Changlei Sun; Jiafu Wang (Journal of Soils and Sediments, 2021)

Structure and variation of root-associated bacterial communities of Cyperus rotundus L. in the contaminated soils around Pb/Zn mine sites - Pin Gao; Benru Song; Rui Xu; Xiaoxu Sun; Hanzhi Lin; Fuqing Xu; Baoqin Li; Weimin Sun (Environmental Science and Pollution Research, 2021)

Slope system stability reliability analysis with multi-parameters using generalized probability density evolution method - Dezhi Zai; Rui Pang; Bin Xu; Qunying Fan; Mingyuan Jing (Bulletin of Engineering Geology and the Environment, 2021)

The TCP transcription factor PeTCP10 modulates salt tolerance in transgenic Arabidopsis - Yuzeng Xu; Huanlong Liu; Yameng Gao; Rui Xiong; Min Wu; Kaimei Zhang; Yan Xiang (Plant Cell Reports, 2021)

Clarification of the etiology of peach bacteria leaf shot hole caused by Pantoea spp. in Henan Province, China, based on morphological characteristics and multi-locus sequences analysis - Rui Zang; Lu-lu Song; Chao Xu; Xin-ming Yin; Zhan-xiang Qiao; Yue-hua Geng; Meng Zhang (European Journal of Plant Pathology, 2021)

lncRNA SNHG16 Mediates Cell Proliferation and Apoptosis in Cholangiocarcinoma by Directly Targeting miR-146a-5p/GATA6 Axis - Tao Wu; Ming-Sheng Lei; Xu-Zhao Gao; Ting-Gang Xiong; Kang Yang; Qian Gong; Rui Tang; Yue-Peng Tian; Xiao-Hua Fu (Biochemical Genetics, 2021)

Correction to: Automatic calculating grain size of gravels based on micro-resistivity image of well - Donghui Li; Rui Yuan; Zhenfeng Ding; Rui Xu (Arabian Journal of Geosciences, 2021)

Microseismic source location method based on a velocity model database and statistical analysis - Bing-Rui Chen; Tao Li; Xin-Hao Zhu; Fan-Bo Wei; Xu Wang; Ming-Xing Xie (Arabian Journal of Geosciences, 2021)

Axisymmetric large strain consolidation by vertical drains considering well resistance under vacuum pressure - Yupeng Cao; Rui Zhang; Guizhong Xu; Jianwen Xu (Arabian Journal of Geosciences, 2021)

Circular RNA circ-CHI3L1.2 modulates cisplatin resistance of osteosarcoma cells via the miR-340-5p/LPAATβ axis - Zehua Zhang; Qiang Zhou; Fei Luo; Rui Zhou; Jianzhong Xu; Jun Xiao; Fei Dai; Lei Song (Human Cell, 2021)

High-throughput sequencing reveals the spatial distribution variability of microbial community in coastal waters in Shenzhen - Rui Zhang; Yu Liu; Xianfeng Zhao; Zhihui Zhao; Honglian Zhang; Xiaoping Huang; Weiqing Xu; Yuchun Shen; Wensheng Lan (Ecotoxicology, 2021)

Evaluation of Brain Network Properties in Patients with MRI-Negative Temporal Lobe Epilepsy: An MEG Study - Yuejun Li; Haitao Zhu; Qiqi Chen; Lu Yang; Xincai Bao; Fangqing Chen; Haiyan Ma; Honghao Xu; Lei Luo; Rui Zhang (Brain Topography, 2021)

Automatic calculating grain size of gravels based on micro-resistivity image of well - Donghui Li; Rui Yuan; Zhenfeng Ding; Rui Xu (Arabian Journal of Geosciences, 2021)

Dynamic simulation of tropical coral reef ecosystem being disturbed by multiple situations - Geng Wang; Rui Dong; Huimin Xu; Dewen Ding (Acta Oceanologica Sinica, 2021)

TREM-1 Exacerbates Neuroinflammatory Injury via NLRP3 Inflammasome-Mediated Pyroptosis in Experimental Subarachnoid Hemorrhage - Pengfei Xu; Ye Hong; Yi Xie; Kang Yuan; Juanji Li; Rui Sun; Xiaohao Zhang; Xiaolei Shi; Rongrong Li; Jiaonan Wu; Xinfeng Liu; Wei Hu; et al. (Translational Stroke Research, 2021)

The mTOR/NF-κB Pathway Mediates Neuroinflammation and Synaptic Plasticity in Diabetic Encephalopathy - Ting Xu; Jiao Liu; Xin-rui Li; Yinghua Yu; Xuan Luo; Xian Zheng; Yuan Cheng; Pei-quan Yu; Yi Liu (Molecular Neurobiology, 2021)

Construction and application of easy-to-detect cyanobacteria with vp28 gene - Min-Min Zhuang; Wen Peng; Yang Xu; Xiao-Hui Jia; Ding-Ji Shi; Pei-Min He; Rui Jia (Journal of Applied Phycology, 2021)

Exosomal miR-193b-5p as a regulator of LPS-induced inflammation in dairy cow mammary epithelial cells - Haotian Xu; Tianqi Zhang; Xuequan Hu; Yingying Xie; Rui Wu; Shuai Lian; Jianfa Wang (In Vitro Cellular & Developmental Biology - Animal, 2021)

Temperature and Moisture Modulate the Contribution of Soil Fauna to Litter Decomposition via Different Pathways - Bo Tan; Rui Yin; Jian Zhang; Zhenfeng Xu; Yang Liu; Shuqin He; Li Zhang; Han Li; Lixia Wang; Sining Liu; Chengming You; Changhui Peng (Ecosystems, 2021)

MicroRNA-363-3p Inhibits the Expression of Renal Fibrosis Markers in TGF-β1-Treated HK-2 Cells by Targeting TGF-β2 - Xiangnan Dong; Yang Li; Rui Cao; Honglan Xu (Biochemical Genetics, 2021)

Seasonal variations of water quality response to land use metrics at multi-spatial scales in the Yangtze River basin - Jiahui Xu; Rui Liu; Maofei Ni; Jing Zhang; Qin Ji; Zuolin Xiao (Environmental Science and Pollution Research, 2021)

Serum Iron and Ferritin Levels Are Correlated with Complement C3 - Shuang Wen; Yeqin Sha; Yinling Li; Zhilian Rui; Chenhong Si; Yuning Zhou; Fengfeng Yan; Bicheng Wang; Jingming Hu; Xu Han; Dongyan Shi (Biological Trace Element Research, 2021)

Foetidibacter luteolus gen. nov., sp. nov., isolated from the rhizosphere of Salvia miltiorrhiza - Qian Pu; Guo-hong Zeng; Gui-wei Wang; Ling-er Lu; Ang Li; Xu-rui Cheng; Xue-ying Wang; Ou Li; Cong Sun; Xiu-fang Hu (Archives of Microbiology, 2021)

Conservation and divergence of the TaSOS1 gene family in salt stress response in wheat (Triticum aestivum L.) - Wei Jiang; Rui Pan; Sebastian Buitrago; Chu Wu; Salah Fatouh Abou-Elwafa; Yanhao Xu; Wenying Zhang (Physiology and Molecular Biology of Plants, 2021)

Systematic analysis of differentially expressed ZmMYB genes related to drought stress in maize - Peng-Yu Zhang; Xiao Qiu; Jia-Xu Fu; Guo-Rui Wang; Li Wei; Tong-Chao Wang (Physiology and Molecular Biology of Plants, 2021)

A New Approach to Embed Complex Fracture Network in Tight Oil Reservoir and Well Productivity Analysis - Jiaxiang Xu; Lifeng Yang; Zhe Liu; Yunhong Ding; Rui Gao; Zhen Wang; Shaoyuan Mo (Natural Resources Research, 2021)

Effects of Tobacco Stem-Derived Biochar on Soil Properties and Bacterial Community Structure under Continuous Cropping of Bletilla striata - Linyan Zhao; Huilin Guan; Rui Wang; Haoji Wang; Zecheng Li; Wei Li; Ping Xiang; Wumei Xu (Journal of Soil Science and Plant Nutrition, 2021)

Effects of Diversified Cropping Sequences and Tillage Practices on Soil Organic Carbon, Nitrogen, and Associated Fractions in the North China Plain - Ahmad Latif Virk; Wen-Sheng Liu; Jia-Rui Niu; Cheng-Tang Xu; Qiu-Yue Liu; Zheng-Rong Kan; Xin Zhao; Hai-Lin Zhang (Journal of Soil Science and Plant Nutrition, 2021)

Classification technology of domestic waste from 2000 to 2019: a bibliometrics-based review - Tianxue Yang; Jiangcheng Xu; Ying Zhao; Tiancheng Gong; Rui Zhao; Mengyang Sun; Beidou Xi (Environmental Science and Pollution Research, 2021)

Generation and identification of endothelial-specific Hrh2 knockout mice - Rui Meng; Wen-Ke Cai; Wen-Mang Xu; Qiang Feng; Ping Wang; Yan-hua Huang; Yu-Xin Fan; Tao Zhou; Qin Yang; Zhi-Ran Li; Gong-Hao He (Transgenic Research, 2021)

Water Qualities and Products Generated in Dechlorination Process Using Ultra-high Lime with Aluminum Method - Jiali Xu; Peng Chen; Chen Dou; Di Yin; GuangYuan Meng; Rui Cheng; Haifeng Liu; Lehua Zhang (Water, Air, & Soil Pollution, 2021)

A functional chromogen gene C from wild rice is involved in a different anthocyanin biosynthesis pathway in indica and japonica - Weihua Qiao; Yanyan Wang; Rui Xu; Ziyi Yang; Yan Sun; Long Su; Lizhen Zhang; Junrui Wang; Jingfen Huang; Xiaoming Zheng; Shijia Liu; Yunlu Tian; et al. (Theoretical and Applied Genetics, 2021)

Correction to: Exploring the Genetic Association of the ABAT Gene with Alzheimer’s Disease - Quanzhen Zheng; Rui Bi; Min Xu; Deng-Feng Zhang; Li-Wen Tan; Ya-Ping Lu; Yong-Gang Yao (Molecular Neurobiology, 2021)

Exploring the Genetic Association of the ABAT Gene with Alzheimer’s Disease - Quanzhen Zheng; Rui Bi; Min Xu; Deng-Feng Zhang; Li-Wen Tan; Ya-Ping Lu; Yong-Gang Yao (Molecular Neurobiology, 2021)

Divergent Projection Patterns Revealed by Reconstruction of Individual Neurons in Orbitofrontal Cortex - Junjun Wang; Pei Sun; Xiaohua Lv; Sen Jin; Anan Li; Jianxia Kuang; Ning Li; Yadong Gang; Rui Guo; Shaoqun Zeng; Fuqiang Xu; Yu-Hui Zhang (Neuroscience Bulletin, 2021)

Microbiological profiles and antimicrobial resistance patterns of pediatric bloodstream pathogens in China, 2016–2018 - Yue Qiu; Junwen Yang; Yiping Chen; Jinhong Yang; Qingxiong Zhu; Chunhui Zhu; Shuangjie Li; Jing Liu; Chaomin Wan; Yu Zhu; Minxia Chen; Yi Xu; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2021)

Epimutational effects of electronic cigarettes - Rui Yan; Xu-Li Chen; Yan-Ming Xu; Andy T. Y. Lau (Environmental Science and Pollution Research, 2021)

A novel Schiff base cobalt(III) complex induces a synergistic effect on cervical cancer cells by arresting early apoptosis stage - Wen-Hui Liao; Xue-Qing Song; Yan-Jie Kong; Rui-Dan Bao; Fang-Fang Li; Jie Zhou; Qi-Hua Zhao; Jing-Yuan Xu; Ni Xie; Ming-Jin Xie (BioMetals, 2021)

Uncertainty Visualisation of a 3D Geological Geometry Model and Its Application in GIS-Based Mineral Resource Assessment: A Case Study in Huayuan District, Northwestern Hunan Province, China - Nan Li; Cangbai Li; Wenkai Chu; Keyan Xiao; Weihan Tao; Xianglong Song; Rui Cao; Yang Xu; Mingjing Fan (Journal of Earth Science, 2021)

BeiDou-3 broadcast clock estimation by integration of observations of regional tracking stations and inter-satellite links - Yufei Yang; Yuanxi Yang; Xiaogong Hu; Chengpan Tang; Rui Guo; Zhanshi Zhou; Junyi Xu; Junyang Pan; Mudan Su (GPS Solutions, 2021)

TGF-β1-modified MSC-derived exosomal miR-135b attenuates cartilage injury via promoting M2 synovial macrophage polarization by targeting MAPK6 - Rui Wang; Bin Xu (Cell and Tissue Research, 2021)

Polymorphisms in the DC-SIGN gene and their association with the severity of hand, foot, and mouth disease caused by enterovirus 71 - Ya-Ping Li; Mu-Qi Wang; Chen-Rui Liu; Hui-Ling Deng; Yuan Wu; Shuang-Suo Dang; Li-Hong Xu (Archives of Virology, 2021)

Self-Assembled Micelles Improve the Oral Bioavailability of Dihydromyricetin and Anti-Acute Alcoholism Activity - Jing Ye; Sha Bao; Shiying Zhao; Yujing Zhu; Qiao Ren; Rui Li; Xiaohong Xu; Quan Zhang (AAPS PharmSciTech, 2021)

New titanite U–Pb and molybdenite Re–Os ages for a hydrothermal vein-type Cu deposit in the Lanping Basin, Yunnan, SW China: constraints on regional metallogeny and implications for exploration - Juan Li; Lei-Luo Xu; Xian-Wu Bi; Yong-Yong Tang; Xiang-Yuan Sheng; Hai-Jun Yu; Gong Liu; Rui Ma (Mineralium Deposita, 2021)

Heteroaggregation of humic acid with montmorillonite in divalent electrolytes: effects of humic acid content and ionic concentration - Xiaodan Gao; Yingde Xu; Zhongyi Li; Song Li; Rui Tian; Hang Li; Rattan Lal; Lingzhi Liu; Muhammad Farhan Saeed; Jingkuan Wang (Journal of Soils and Sediments, 2021)

Estimates on thermal impact of gas-line and alleviating effect of countermeasures in patchy permafrost of northwestern China - Rui Shi; Xu Wang; Zhi Wen; Desheng Li (Bulletin of Engineering Geology and the Environment, 2021)

Small RNA Sequencing Analysis of Germinating Single-bud Seedcane Sett in Sugarcane - Kai-Chao Wu; Lin Xu; Zhi-Nian Deng; Tian Pang; Rong-Hua Zhang; Yi-Jie Li; Xiao-Yan Liu; Cheng-Feng Huang; Wen-Xian Qin; Jian-Feng Wei; Li-Ping Wei; Yang-Rui Li; et al. (Sugar Tech, 2021)

The role of hydrous mantle-derived magmas in the generation of Late Cretaceous granitoids in the Gangdese batholith: insights from the Shanba and Zongga plutons in the southern Lhasa subterrane, Tibet - Rui-Qiang Wang; Jian-Sheng Qiu; Ding-Jun Wen; Hang Xu (Mineralogy and Petrology, 2021)

Gentianella acuta prevents acute myocardial infarction induced by isoproterenol in rats via inhibition of galectin-3/TLR4/MyD88/NF-кB inflammatory signalling - Jia-Huan Sun; Hong-Xia Yang; Ting-Ting Yao; Yuan Li; Lin Ruan; Geng-Rui Xu; Chuang Zhang; Guo-Xin Guo; Ai-Ying Li (Inflammopharmacology, 2021)

Identification of pepper genes involved in the response to CO2 enrichment using RNA-Seq analysis - Jing Zhang; Rui Bai; Mengya Shang; Xiaoyong Xu; Hongxia Song; Shaowen Zheng; Leiping Hou; Meilan Li; Guoming Xing (Horticulture, Environment, and Biotechnology, 2021)

Renewable energy hybrid subsidy combining input and output subsidies - Zi-rui Chen; Xu Xiao; Pu-yan Nie (Environmental Science and Pollution Research, 2021)

3D slope reliability analysis based on the intelligent response surface methodology - LaiFu Song; Xiang Yu; Bin Xu; Rui Pang; ZeYu Zhang (Bulletin of Engineering Geology and the Environment, 2021)

Formaldehyde-induced hematopoietic stem and progenitor cell toxicity in mouse lung and nose - Yun Zhao; Laura C. Magaña; Haiyan Cui; Jiawei Huang; Cliona M. McHale; Xu Yang; Mark R. Looney; Rui Li; Luoping Zhang (Archives of Toxicology, 2021)

Combining forecast of landslide displacement based on chaos theory - Xunchang Li; Chao Jiang; Rui Xu; Wei Yang; HaoHao Wang; Yu Zou (Arabian Journal of Geosciences, 2021)

Is small hydropower beautiful? Social impacts of river fragmentation in China’s Red River Basin - Tyler Harlan; Rui Xu; Jun He (Ambio, 2021)

An insight into shallow gas hydrates in the Dongsha area, South China Sea - Bin Liu; Jiangxin Chen; Luis M. Pinheiro; Li Yang; Shengxuan Liu; Yongxian Guan; Haibin Song; Nengyou Wu; Huaning Xu; Rui Yang (Acta Oceanologica Sinica, 2021)

Elevated plasma phage load as a marker for intestinal permeability in leukemic patients - Xue-rui Yin; Ping Liu; Xi Xu; Ying Xia; Kai-zhao Huang; Qiong-dan Wang; Mei-mei Lai; Qi-gui Yu; Xiao-qun Zheng (Medical Microbiology and Immunology, 2020)

Rho GTPases in cancer radiotherapy and metastasis - Rui-Jie Zeng; Chun-Wen Zheng; Wan-Xian Chen; Li-Yan Xu; En-Min Li (Cancer and Metastasis Reviews, 2020)

MHC-DRB1 exon 2 polymorphism and its association with mycoplasma ovipneumonia resistance or susceptibility genotypes in sheep - Kaisheng Wang; Xianxia Liu; Qiongqiong Li; Kexing Wan; Rui Gao; Guohua Han; Chaochen Li; Mengsi Xu; Bin Jia; Xiaoyun Shen (Journal of Genetics, 2020)

Correction to: Diffuse leptomeningeal glioneuronal tumor in a Chinese adult: a novel case report and review of literature - Honghao Xu; Fangqing Chen; Haitao Zhu; Lei Luo; Rui Zhang (Acta Neurologica Belgica, 2020)

Cytokinin (6-benzylaminopurine) elevates lignification and the expression of genes involved in lignin biosynthesis of carrot - Ahmed Khadr; Ya-Hui Wang; Rong-Rong Zhang; Xin-Rui Wang; Zhi-Sheng Xu; Ai-Sheng Xiong (Protoplasma, 2020)

Utilizing borehole electrical image and conventional logs to characterize petrology of mixed volcanic and sedimentary rocks in Jiamuhe Formation at JL2 Wellfield, Zhongguai Uplift, Junggar Basin, NW China - Rui Yuan; Lei Zhang; Qinghai Xu; Youlun Feng; Zhiyuan An; Jun Wu; Kang Zhao; Shuai Liu; Peng Huang (Arabian Journal of Geosciences, 2020)

The Protective Effect of Safinamide in Ischemic Stroke Mice and a Brain Endothelial Cell Line - Tingting Xu; Rui Sun; Guoshi Wei; Shanshan Kong (Neurotoxicity Research, 2020)

Evaluating Spatial Heterogeneity of Land Surface Hydrothermal Conditions in the Heihe River Basin - Yuan Zhang; Shaomin Liu; Xiao Hu; Jianghao Wang; Xiang Li; Ziwei Xu; Yanfei Ma; Rui Liu; Tongren Xu; Xiaofan Yang (Chinese Geographical Science, 2020)

Complete genome sequence of a novel mycovirus isolated from the phytopathogenic fungus Corynespora cassiicola in China - Yanfen Wang; Hang Zhao; Caiying Xue; Chao Xu; Yuehua Geng; Rui Zang; Yuxia Guo; Haiyan Wu; Meng Zhang (Archives of Virology, 2020)

BDNF improves axon transportation and rescues visual function in a rodent model of acute elevation of intraocular pressure - Rui Du; Xu Wang; Shigang He (Science China Life Sciences, 2020)

Mapping spatio-temporal dynamics of main water parameters and understanding their relationships with driving factors using GF-1 images in a clear reservoir - Shuai Zeng; Yunmei Li; Heng Lyu; Jiafeng Xu; Xianzhang Dong; Rui Wang; Ziqian Yang; Jianchao Li (Environmental Science and Pollution Research, 2020)

Alleviation of Cd phytotoxicity and enhancement of rape seedling growth by plant growth–promoting bacterium Enterobacter sp. Zm-123 - Meng Zhang; Zonghui Jin; Xu Zhang; Guoliang Wang; Rui Li; Juanjuan Qu; Yu Jin (Environmental Science and Pollution Research, 2020)

An improved FAHP based methodology for groundwater potential zones in Longchuan River basin, Yunnan Province, China - Dayou Luo; Xingping Wen; Haonan Zhang; Junlong Xu; Rui Zhang (Earth Science Informatics, 2020)

Molecular Characterization and Promoter Analysis of Novel Sugar Transporter Gene ScERD6 in Sugarcane - Xiao-Rong Miao; Xu-Peng Zeng; Jun-Qi Niu; Aamir Mahmood; Li-Tao Yang; Bao-Qing Zhang; Yang-Rui Li (Sugar Tech, 2020)

Effects of crop straw biochars on aluminum species in soil solution as related with the growth and yield of canola (Brassica napus L.) in an acidic Ultisol under field condition - Wen-rui Zhao; Jiu-yu Li; Kai-ying Deng; Ren-yong Shi; Jun Jiang; Zhi-neng Hong; Wei Qian; Xian He; Ren-kou Xu (Environmental Science and Pollution Research, 2020)

The impact of prenatal exposure to PM2.5 on childhood asthma and wheezing: a meta-analysis of observational studies - Wu Yan; Xu Wang; Tianyu Dong; Mengqi Sun; Mingzhi Zhang; Kacey Fang; Yi Chen; Rui Chen; Zhiwei Sun; Yankai Xia (Environmental Science and Pollution Research, 2020)

Enhancement of the activity of Cu/TiO2 catalyst by Eu modification for selective catalytic reduction of NOx with NH3 - Yuan-zhen Liu; Qi-yan Xu; Rui-tang Guo; Chao-peng Duan; Gui-lin Wu; Yu-fang Miao; Jing-wen Gu (Environmental Science and Pollution Research, 2020)

Genetic variants in Ras/Raf/MEK/ERK pathway are associated with gastric cancer risk in Chinese Han population - Xiaowei Wang; Xu Wu; Junyi Xin; Shuwei Li; Rui Zheng; Dan Guan; Weida Gong; Qinghong Zhao; Meilin Wang; Haiyan Chu; Mulong Du; Guoquan Tao; et al. (Archives of Toxicology, 2020)

Overexpression of Purinergic P2X4 Receptors in Hippocampus Rescues Memory Impairment in Rats with Type 2 Diabetes - Ping-An Zhang; Qian Sun; Yong-Chang Li; Rui-Xia Weng; Rui Wu; Hong-Hong Zhang; Guang-Yin Xu (Neuroscience Bulletin, 2020)
Purinergic receptors have been reported to be involved in brain disorders. In this study, we explored their roles and mechanisms underlying the memory impairment in rats with type 2 diabetes mellitus (T2DM). T2DM rats exhibited a worse performance in the T-maze and Morris water maze (MWM) than controls. Microglia positive for P2X purinoceptor 4 (P2X4R) in the hippocampus were reduced and activated microglia were increased in T2DM rats. Long Amplicon PCR (LA-PCR) showed that DNA amplification of the p2x4r gene in the hippocampus was lower in T2DM rats. Minocycline significantly reduced the number of activated microglia and the mean distance traveled by T2DM rats in the MWM. Most importantly, P2X4R overexpression suppressed the activated microglia and rescued the memory impairment of T2DM rats. Overall, T2DM led to excessive activation of microglia in the hippocampus, partly through the DNA damage-mediated downregulation of P2X4Rs, thus contributing to memory impairment.

Correlation Between CCG Polymorphisms and CAG Repeats During Germline Transmission in Chinese Patients with Huntington’s Disease - Hong-Rong Cheng; Xiao-Yan Li; Hui-Li Yu; Miao Xu; Yan-Bin Zhang; Shi-Rui Gan; Hong-Lei Li; Zhi-Ying Wu (Neuroscience Bulletin, 2020)

Analysis of pituitary transcriptomics indicates that lncRNAs are involved in the regulation of sheep estrus - Xiaoyue Li; Cunyuan Li; Yueren Xu; Rui Yao; Huixiang Li; Wei Ni; Renzhe Quan; Mengdan Zhang; Li Liu; Shuting Yu; Yaseen Ullah; Ruirui Hu; et al. (Functional & Integrative Genomics, 2020)

The characteristic of the synonymous codon usage and phylogenetic analysis of hepatitis B virus - Xiaoming Qi; Chaojun Wei; Yonghong Li; Yu Wu; Hui Xu; Rui Guo; Yanjuan Jia; Zhenhao Li; Zhenhong Wei; Wanxia Wang; Jing Jia; Yuanting Li; et al. (Genes & Genomics, 2020)
Background Hepatitis B virus (HBV) infection is a crucial medical issue worldwide. The dependence of HBV replication on host cell machineries and their co-evolutionary interactions prompt the codon usage pattern of viral genes to translation selection and mutation pressure. Objective The evolutionary characteristics of HBV and the natural selection effects of the human genome on the codon usage characteristics were analyzed to provide a basis for medication development for HBV infection. Methods The codon usage pattern of sequences from different HBV genotypes of our isolates and reference HBV genome sequences downloaded from the National Center for Biotechnology Information (NCBI) database were analyzed by computing the relative synonymous codon usage (RSCU), nucleotide content, codon adaptation index (CAI) and the effective number of codons (ENC). Results The highest ENC values were observed in the C genotypes, followed by the B genotypes. The ENC values indicated a weak codon usage bias (CUB) in HBV genome. The number of codons differentially used between the three genotypes was markedly higher than that of similarly used codons. High CAI values indicated a good adaptability of HBV to its host. The ENC plot indicated the occurrence of mutational pressure in the three genotypes. The mean Ka/Ks ratios in the three genotypes were lower than 1, which indicated a negative selection pressure. The CAI and GC3% plot indicated the existence of CUB in the HBV genome. Conclusions Nucleotide composition, mutation bias, negative selection and mutational pressure are key factors influencing the CUB and phylogenetic diversity in HBV genotypes. The data provided here could be useful for developing drugs for HBV infection.

3D-QSAR, HQSAR, molecular docking, and new compound design study of 1,3,6-trisubstituted 1,4-diazepan-7-ones as human KLK7 inhibitors - Le Fu; Yi Chen; Chun-mei Xu; Tao Wu; Hong-mei Guo; Zhi-hua Lin; Rui Wang; Mao Shu (Medicinal Chemistry Research, 2020)

Effects of different NO3−:NH4+ ratios on the photosynthesis and ultrastructure of lettuce seedlings - Xu Zhu; Rui Yang; Yingyan Han; Jinghong Hao; Chaojie Liu; Shuangxi Fan (Horticulture, Environment, and Biotechnology, 2020)

Clinical strategies for differentiating IgG4-related cholecystitis from gallbladder carcinoma to avoid unnecessary surgical resection - Rui Zhang; Hao-Ming Lin; Zhao-Xi Cai; Su-Juan Du; Hong Zeng; Lei-Bo Xu; Jie Wang; Chao Liu (Science China Life Sciences, 2020)

Two-Dimensional Discrepancies in Fracture Geometric Factors and Connectivity Between Field-Collected and Stochastically Modeled DFNs: A Case Study of Sluice Foundation Rock Mass in Datengxia, China - Wen Zhang; Rui Fu; Chun Tan; Zhifa Ma; Ying Zhang; Shengyuan Song; Peihua Xu; Shuonan Wang; Yunpeng Zhao (Rock Mechanics and Rock Engineering, 2020)

PDB-1 from Potentilla discolor Bunge suppresses lung cancer cell migration and invasion via FAK/Src and MAPK signaling pathways - Na-na Meng; Rui-rui Zhang; Chao Liu; Qing Wang; Xin-kun Wang; Xu Guo; Ping-ping Wang; Jin-yue Sun (Medicinal Chemistry Research, 2020)

Spent mushroom substrate combined with alkaline amendment passivates cadmium and improves soil property - Zonghui Jin; Meng Zhang; Rui Li; Xu Zhang; Guoliang Wang; Xuesheng Liu; Juanjuan Qu; Yu Jin (Environmental Science and Pollution Research, 2020)

Plasma Endostatin Levels at Acute Phase of Ischemic Stroke Are Associated with Post-Stroke Cognitive Impairment - Sifan Qian; Ruyi Li; Chenhuan Zhang; Rui Zhang; Daoxia Guo; Xiaoqing Bu; Aili Wang; Hao Peng; Jing Chen; Yonghong Zhang; Jiang He; Tan Xu; et al. (Neurotoxicity Research, 2020)

Long-term fertilization and intensive cropping enhance carbon and nitrogen accumulated in soil clay-sized particles of red soil in South China - Hu Xu; Kailou Liu; Wenju Zhang; Yichao Rui; Jingye Zhang; Lei Wu; Gilles Colinet; Qinghai Huang; Xianni Chen; Minggang Xu (Journal of Soils and Sediments, 2020)

Solar UV radiation exacerbates photoinhibition of a diatom by antifouling agents Irgarol 1051 and diuron - Rui Hou; Yaping Wu; Juntian Xu; Kunshan Gao (Journal of Applied Phycology, 2020)

Appropriate Dynamically-Reinforced Supporting Time Determination in Relation to the Time Effect of Stress Field Evolution: A Case Study on the Deep Soft-Rock Roadway in China - Li Cong; Ying-ming Li; Xiang-rui Meng; Chun-liang Dong; Guang-ming Zhao; Rui Peng; Ji-cheng Xu (Geotechnical and Geological Engineering, 2020)

Tracing solute sources and carbon dynamics under various hydrological conditions in a karst river in southwestern China - Jing Liu; Bo Chen; Zhu-Yan Xu; Yuan Wei; Zhi-Hua Su; Rui Yang; Yong-Xue Ji; Xiao-Dan Wang; Li-Li Zhang; Ning An; Fei Yang (Environmental Science and Pollution Research, 2020)

Sulfur content in coal formed during different geologic periods in the Guangxi Province and the relationship with the depositional environment - Bohui Xu; Yuxin Song; Yuan Tian; Rui Yang; Fei Xu; Shuli Ding; Pengfei Sun (Arabian Journal of Geosciences, 2020)

Diffuse leptomeningeal glioneuronal tumor in a Chinese adult: a novel case report and review of literature - Honghao Xu; Fangqing Chen; Haitao Zhu; Lei Luo; Rui Zhang (Acta Neurologica Belgica, 2020)

Sources and ore-forming fluid pathways of carbonate-hosted Pb–Zn deposits in Southwest China: implications of Pb–Zn–S–Cd isotopic compositions - Chong Xu; Hong Zhong; Rui-Zhong Hu; Han-Jie Wen; Wei-Guang Zhu; Zhong-Jie Bai; Hai-Feng Fan; Fang-Fang Li; Ting Zhou (Mineralium Deposita, 2020)

Decreasing intraocular pressure significantly improves retinal vessel density, cytoarchitecture and visual function in rodent oxygen induced retinopathy - Rui Du; Xu Wang; Ke Shen; Shigang He (Science China Life Sciences, 2020)

MiR-125a-5p Regulates Vitamin D Receptor Expression in a Mouse Model of Experimental Autoimmune Encephalomyelitis - Han-Chun Long; Rui Wu; Chun-Feng Liu; Fei-Long Xiong; Zu Xu; Dian He; Yi-Fan Zhang; Bing Shao; Ping-An Zhang; Guang-Yin Xu; Lan Chu (Neuroscience Bulletin, 2020)

Application of metagenomic next-generation sequencing for bronchoalveolar lavage diagnostics in critically ill patients - Ying Li; Bing Sun; Xiao Tang; Ya-lan Liu; Hang-yong He; Xu-yan Li; Rui Wang; Fei Guo; Zhao-hui Tong (European Journal of Clinical Microbiology & Infectious Diseases, 2020)

Risk factors and clinical characteristics of tacrolimus-induced acute nephrotoxicity in children with nephrotic syndrome: a retrospective case-control study - Ping Gao; Xin-Lei Guan; Rui Huang; Xiao-Fang Shang-guan; Jiang-Wei Luan; Mao-Chang Liu; Hua Xu; Xiao-Wen Wang (European Journal of Clinical Pharmacology, 2020)

Forest gaps retard carbon and nutrient release from twig litter in alpine forest ecosystems - Bo Tan; Jian Zhang; Wanqin Yang; Rui Yin; Zhenfeng Xu; Yang Liu; Li Zhang; Han Li; Chengming You (European Journal of Forest Research, 2020)

LncRNA NBR2 suppresses migration and invasion of colorectal cancer cells by downregulating miRNA-21 - Jinghui Bai; Jian Xu; Jian Zhao; Rui Zhang (Human Cell, 2020)

Strength Parameters of Rock Considering Area and Stress Correction During Shearing - Hang Lin; Yushan Hua; Rui Yong; Daxing Lei; Wanzhong Xu; Shigui Du (Geotechnical and Geological Engineering, 2020)

Uptake and accumulation of pentachloronitrobenzene in pak choi and the human health risk - Ming Li; Guanghui Xu; Rui Yu; Yang Wang; Yong Yu (Environmental Geochemistry and Health, 2020)

Genetic variants in circTUBB interacting with smoking can enhance colorectal cancer risk - Ke Zhang; Shuwei Li; Dongying Gu; Kaili Xu; Rui Zheng; Junyi Xin; Yixuan Meng; Shuai Ben; Haiyan Chu; Zhengdong Zhang; Yongqian Shu; Mulong Du; et al. (Archives of Toxicology, 2020)

Preparation and In vitro Evaluation of FDM 3D-Printed Ellipsoid-Shaped Gastric Floating Tablets with Low Infill Percentages - Di Chen; Xiang-Yu Xu; Rui Li; Gen-Ao Zang; Yue Zhang; Ming-Rui Wang; Meng-Fei Xiong; Jia-Rui Xu; Ting Wang; Hui Fu; Qin Hu; Bin Wu; et al. (AAPS PharmSciTech, 2020)

Intracranial Aneurysms: Pathology, Genetics, and Molecular Mechanisms - Zhen Xu; Yan-Ning Rui; John P. Hagan; Dong H. Kim (NeuroMolecular Medicine, 2019)

Quality control of marine big data—a case study of real-time observation station data in Qingdao - Chengcheng Qian; Aichao Liu; Rui Huang; Qingrong Liu; Wenkun Xu; Shan Zhong; Le Yu (Journal of Oceanology and Limnology, 2019)

Digestive characteristics and blood chemistry profile of triploid rainbow trout Oncorhynchus mykiss: influence of body size and seasonal variation - Yuqiong Meng; Buying Han; Changzhong Li; Kangkang Qian; Xiaohong Liu; Xuemin Hu; Xu Yang; Haining Tian; Rui Ma (Fisheries Science, 2019)

Effects of climate change on lake area and vegetation cover over the past 55 years in Northeast Inner Mongolia grassland, China - Yanfei Zhang; Wentao Liang; Zilong Liao; Zhenhua Han; Xiaomin Xu; Rui Jiao; Hualin Liu (Theoretical and Applied Climatology, 2019)

Poly-PR in C9ORF72-Related Amyotrophic Lateral Sclerosis/Frontotemporal Dementia Causes Neurotoxicity by Clathrin-Dependent Endocytosis - Rui Wang; Xingyun Xu; Zongbing Hao; Shun Zhang; Dan Wu; Hongyang Sun; Chenchen Mu; Haigang Ren; Guanghui Wang (Neuroscience Bulletin, 2019)

Decreased miR-325-5p Contributes to Visceral Hypersensitivity Through Post-transcriptional Upregulation of CCL2 in Rat Dorsal Root Ganglia - Rui Wu; Ping-An Zhang; Xuelian Liu; Yuan Zhou; Meijie Xu; Xinghong Jiang; Jun Yan; Guang-Yin Xu (Neuroscience Bulletin, 2019)

Effect of genotype and environment on agronomical characters of common vetch (Vicia sativa L.) - Rui Dong; Shu H. Shen; Mohamed Z. Z. Jahufer; De K. Dong; Dong Luo; Qiang Zhou; Xu T. Chai; Kai Luo; Zhi B. Nan; Yan R. Wang; Zhi P. Liu (Genetic Resources and Crop Evolution, 2019)

Choline, not folate, can attenuate the teratogenic effects ofdibutyl phthalate (DBP) during early chick embryo development - Rui Wang; Da-Guang Sun; Ge Song; Chun Yi Guan; Yi Cui; Xu Ma; Hong-Fei Xia (Environmental Science and Pollution Research, 2019)

ATP induces caspase-3/gasdermin E-mediated pyroptosis in NLRP3 pathway-blocked murine macrophages - Chen-Ying Zeng; Chen-Guang Li; Jun-Xiang Shu; Li-Hui Xu; Dong-Yun Ouyang; Feng-Yi Mai; Qiong-Zhen Zeng; Cheng-Cheng Zhang; Rui-Man Li; Xian-Hui He (Apoptosis, 2019)

Effects of Exogenous Application of Melatonin on Quality and Sugar Metabolism in ‘Zaosu’ Pear Fruit - Jianlong Liu; Rongrong Yue; Min Si; Meng Wu; Liu Cong; Rui Zhai; Chengquan Yang; Zhigang Wang; Fengwang Ma; Lingfei Xu (Journal of Plant Growth Regulation, 2019)

Calycosin down-regulates c-Met to suppress development of glioblastomas - Xiaohu Nie; Yue Zhou; Xiaobing Li; Jie Xu; Xuyan Pan; Rui Yin; Bin Lu (Journal of Biosciences, 2019)

Three Tibetan grassland plant species tend to partition niches with limited plasticity in nitrogen use - Li Zhang; Rui Pang; Xingliang Xu; Minghua Song; Yikang Li; Huakun Zhou; Xiaoyong Cui; Yanfen Wang; Hua Ouyang (Plant and Soil, 2019)

Effects of exogenous putrescine on the ultrastructure of and calcium ion flow rate in lettuce leaf epidermal cells under drought stress - Xu Zhu; Lin Wang; Rui Yang; Yingyan Han; Jinghong Hao; Chaojie Liu; Shuangxi Fan (Horticulture, Environment, and Biotechnology, 2019)

Disruption of stcA blocks sterigmatocystin biosynthesis and improves echinocandin B production in Aspergillus delacroxii - Taoling Min; Lei Xiong; Yan Liang; Rui Xu; Chenchang Fa; Sheng Yang; Haifeng Hu (World Journal of Microbiology and Biotechnology, 2019)

The severity of drought and precipitation prediction in the eastern fringe of the Tibetan Plateau - Yang Zhao; Xiangde Xu; Liufeng Liao; Yuhong Wang; Xiaoping Gu; Rui Qin; Yunyun Guo; Zhaoping Kang; Fang Wang; Min Wang (Theoretical and Applied Climatology, 2019)

Optimizing cold storage of the ectoparasitic mite Pyemotes zhonghuajia (Acari: Pyemotidae), an efficient biological control agent of stem borers - Limin He; Litao Li; Lichen Yu; Xiong Z. He; Rui Jiao; Changxin Xu; Linlin Zhang; Jinli Liu (Experimental and Applied Acarology, 2019)

Nanoparticles: Oral Delivery for Protein and Peptide Drugs - Shu-jun Cao; Shuo Xu; Hui-ming Wang; Yong Ling; Jiahua Dong; Rui-dong Xia; Xiang-hong Sun (AAPS PharmSciTech, 2019)

Targeted Gene Disruption in Pacific Oyster Based on CRISPR/Cas9 Ribonucleoprotein Complexes - Hong Yu; Huijuan Li; Qi Li; Rui Xu; Chenyang Yue; Shaojun Du (Marine Biotechnology, 2019)

Mechanical Effect Analysis and Comparative Site Tests on Surrounding Rock with Different Bolt Anchoring Lengths and Pre-tightening Forces - Qi Wang; Hongtao Wang; Rui Pan; Shucai Li; Manchao He; Bei Jiang; Qian Qin; Chong Zhang; Yingdong Xu (Geotechnical and Geological Engineering, 2019)

Effects of different substrates on nitrogen and phosphorus removal in horizontal subsurface flow constructed wetlands - Rui Xu; Yong Zhang; Rong Liu; Yun Cao; Guoxiang Wang; Lingchen Ji; Yifan Xu (Environmental Science and Pollution Research, 2019)

Brick tea consumption is a risk factor for dental caries and dental fluorosis among 12-year-old Tibetan children in Ganzi - Rui Zhang; Li Cheng; Tao Zhang; Ting Xu; Meng Li; Wei Yin; Qingling Jiang; Yingming Yang; Tao Hu (Environmental Geochemistry and Health, 2019)

Interactions among chilling tolerance, sucrose degradation and organic acid metabolism in UV-C-irradiated peach fruit during postharvest cold storage - Dandan Zhou; Shaoxia Chen; Rui Xu; Sicong Tu; Kang Tu (Acta Physiologiae Plantarum, 2019)

Overexpression of BcbZIP134 negatively regulates the biosynthesis of saikosaponins - Jiao Xu; Su-Rui Wu; Yan-Hong Xu; Zhan-Yu Ge; Chun Sui; Jian-He Wei (Plant Cell, Tissue and Organ Culture (PCTOC), 2019)

Differential response to warming of the uptake of nitrogen by plant species in non-degraded and degraded alpine grasslands - Zhe Pang; Lili Jiang; Shiping Wang; Xingliang Xu; Yichao Rui; Zhenhua Zhang; Caiyun Luo; Yanfen Wang (Journal of Soils and Sediments, 2019)

Temperature-control-induced masculinization in tiger puffer Takifugu rubripes - He Zhou; Zixin Zhuang; Rui Zhang; Qizheng Xu; Yuting Liang; Zhiqiang Jiang; Xia Li; Tianyu Ma; Yajuan Li (Journal of Oceanology and Limnology, 2019)

Highly Sensitive and Selective Fluorescent Probe for Detection of Fe3+ Based on Rhodamine Fluorophore - Yang Wang; Rui Guo; Xufeng Hou; Mengmeng Lei; Qihang Zhou; Zhihong Xu (Journal of Fluorescence, 2019)

Contributions to species of Xylariales in China-1. Durotheca species - Qing De Long; Li Li Liu; Xu Zhang; Ting Chi Wen; Ji Chuan Kang; Kevin David Hyde; Xiang Chun Shen; Qi Rui Li (Mycological Progress, 2019)

Brain Network Reconfiguration During Motor Imagery Revealed by a Large-Scale Network Analysis of Scalp EEG - Fali Li; Chanlin Yi; Limeng Song; Yuanling Jiang; Wenjing Peng; Yajing Si; Tao Zhang; Rui Zhang; Dezhong Yao; Yangsong Zhang; Peng Xu (Brain Topography, 2019)

Chromosome level comparative analysis of Brassica genomes - Wenliang Wang; Rui Guan; Xing Liu; Haorui Zhang; Bo Song; Qiwu Xu; Guangyi Fan; Wenbin Chen; Xiaoming Wu; Xin Liu; Jianbo Wang (Plant Molecular Biology, 2019)

Long noncoding RNA UCA1 promotes the proliferation of hypoxic human pulmonary artery smooth muscle cells - Tian-Tian Zhu; Rui-Li Sun; Ya-Ling Yin; Jin-Ping Quan; Ping Song; Jian Xu; Ming-Xiang Zhang; Peng Li (Pflügers Archiv - European Journal of Physiology, 2019)

Modeling beach profile changes by typhoon impacts at Xiamen coast - Kai Yin; Sudong Xu; Wenrui Huang; Rui Li; Hong Xiao (Natural Hazards, 2019)

Multipotential Toxic Metals Accumulated in Urban Soil and Street Dust from Xining City, NW China: Spatial Occurrences, Sources, and Health Risks - Meng Zhang; Xiaoping Li; Rui Yang; Jiwen Wang; Yuwei Ai; Yu Gao; Yuchao Zhang; Xu Zhang; Xiangyang Yan; Bin Liu; Hongtao Yu (Archives of Environmental Contamination and Toxicology, 2019)

Template for MR Visualization and Needle Targeting - Rui Li; Sheng Xu; Ivane Bakhutashvili; Ismail B. Turkbey; Peter Choyke; Peter Pinto; Bradford Wood; Zion T. H. Tse (Annals of Biomedical Engineering, 2019)

Postprandial change in glucose metabolism at the molecular level in the adipose tissue of omnivorous GIFT Oreochromis niloticus - Jing-Yun Feng; Qin-Qin Liu; Hang-Zhong Xu; Rui-Hong Chen; Li Luo; Shi-Mei Lin; Yong-Jun Chen; De-Shou Wang (Fisheries Science, 2019)

Soil infiltration rate of forestland and grassland over different vegetation restoration periods at Loess Plateau in northern hilly areas of China - Shahmir Ali Kalhoro; Kang Ding; Beiying Zhang; Wenyuan Chen; Rui Hua; Akhtar Hussain Shar; Xuexuan Xu (Landscape and Ecological Engineering, 2019)

Improved ARAIM fault modes determination scheme based on feedback structure with probability accumulation - Qian Meng; Jianye Liu; Qinghua Zeng; Shaojun Feng; Rui Xu (GPS Solutions, 2019)

Investigation of early Bronze Age civilizations in Yunnan: a scientific analysis of metallurgical relics found at the Guangfentou ruins in Jiangchuan - Guisen Zou; Jianfeng Cui; Xu Liu; Xiaorui Li; Rui Min (Archaeological and Anthropological Sciences, 2019)

Transcriptome Reveals Differentially Expressed Genes in Saccharum spontaneum GX83-10 Leaf Under Drought Stress - Kai-Chao Wu; Li-Ping Wei; Cheng-Mei Huang; Yuan-Wen Wei; Hui-Qing Cao; Lin Xu; Hai-Bin Luo; Sheng-Li Jiang; Zhi-Nian Deng; Yang-Rui Li (Sugar Tech, 2018)

Effects of clipping and shading on 15NO3− and 15NH4+ recovery by plants in grazed and ungrazed temperate grasslands - Rui Pang; Yue Sun; Xingliang Xu; Minghua Song; Hua Ouyang (Plant and Soil, 2018)

Plant organic N uptake maintains species dominance under long-term warming - Lili Jiang; Shiping Wang; Pang Zhe; Xingliang Xu; Paul Kardol; Yaoming Li; Lirong Zhang; Yanfen Wang; Zhong Lei; Zhichun Lan; Paul W. Hill; Zhenhua Zhang; et al. (Plant and Soil, 2018)

Eighty Years of Mycopathologia: A Retrospective Analysis of Progress Made in Understanding Human and Animal Fungal Pathogens - Vishnu Chaturvedi; Jean-Philippe Bouchara; Ferry Hagen; Ana Alastruey-Izquierdo; Hamid Badali; Anamelia Lorenzetti Bocca; Jose F. Cano-Lira; Cunwei Cao; Sudha Chaturvedi; Sanjay H. Chotirmall; Anne D. van Diepeningen; Jean-Pierre Gangneux; et al. (Mycopathologia, 2018)

Microtremor survey and stability analysis of a soil-rock mixture landslide: a case study in Baidian town, China - Wen-wei Gao; Wei Gao; Rui-lin Hu; Pei-fen Xu; Jia-guo Xia (Landslides, 2018)

Occurrence of cucumber mosaic virus subgroup II and its genetic diversity in Sichuan, southwest of China - Chunyan Fei; Zhenpeng Xu; Lijuan Chen; Wenshan Zou; Rui Lv; Honghui Lin; Dehui Xi (Journal of Plant Pathology, 2018)

Composition of stable isotope in precipitation and its influences by different vapor sources in the eastern Qilian Mountains - Wen-xiong Jia; Xing-gang Ma; Xiu-ting Xu; Rui-feng Yuan; Dan Ding; Guo-feng Zhu (Journal of Mountain Science, 2018)

Spatial Distribution and Risk Assessment of Heavy Metals in Paddy Soils of Yongshuyu Irrigation Area from Songhua River Basin, Northeast China - Zhengwu Cui; Yang Wang; Na Zhao; Rui Yu; Guanghui Xu; Yong Yu (Chinese Geographical Science, 2018)

High-Order Statistics of Temperature Fluctuations in an Unstable Atmospheric Surface Layer over Grassland - Rui Lyu; Fei Hu; Lei Liu; Jingjing Xu; Xueling Cheng (Advances in Atmospheric Sciences, 2018)

Use of cationic microbubbles targeted to P-selectin to improve ultrasound-mediated gene transfection of hVEGF165 to the ischemic myocardium - Wei-hui Shentu; Cao-xin Yan; Chun-mei Liu; Rui-xiang Qi; Yao Wang; Zhao-xu Huang; Li-ming Zhou; Xiang-dong You (Journal of Zhejiang University-SCIENCE B, 2018)

Three-dimensional numerical modeling of gravity anomalies based on Poisson equation in space-wavenumber mixed domain - Shi-Kun Dai; Dong-Dong Zhao; Qian-Jiang Zhang; Kun Li; Qing-Rui Chen; Xu-Long Wang (Applied Geophysics, 2018)

Paleoenvironmental implications of the calcium isotope characteristics in the MD81349 from the Nintyeast Ridge in the Indian Ocean - Feng Wang; Nianqiao Fang; Chaoyong Hu; Sarah Goldsmith; Yonghang Xu; Xuan Ding; Aijun Wang; Ping Chen; Rui Bao (Acta Oceanologica Sinica, 2018)

Time is nothing: emotional consistency of autobiographical memory and its neural basis - Rui Xu; Juan Yang; Chunliang Feng; Haiyan Wu; Ruiwang Huang; Qiuli Yang; Zhihao Li; Pengfei Xu; Ruolei Gu; Yue-jia Luo (Brain Imaging and Behavior, 2018)

Structural Strength Analysis of a Tri-Floater Floating Foundation for Offshore VAWT - Liqin Liu; Haixiang Zhao; Wanhai Xu; Rui Yuan; Ying Guo (Journal of Ocean University of China, 2018)

Identification of drug target candidates of the swine pathogen Actinobacillus pleuropneumoniae by construction of protein–protein interaction network - Siqi Li; Zhipeng Su; Chengjun Zhang; Zhuofei Xu; Xiaoping Chang; Jiawen Zhu; Ran Xiao; Lu Li; Rui Zhou (Genes & Genomics, 2018)

SNAI1, an endothelial–mesenchymal transition transcription factor, promotes the early phase of ocular neovascularization - Jia-Xing Sun; Tian-Fang Chang; Man-Hong Li; Li-Juan Sun; Xian-Chun Yan; Zi-Yan Yang; Yuan Liu; Wen-Qin Xu; Yang Lv; Jing-Bo Su; Liang Liang; Hua Han; et al. (Angiogenesis, 2018)

Fine mapping and identification of a novel locus qGL12.2 control grain length in wild rice (Oryza rufipogon Griff.) - Lan Qi; Yingbin Ding; Xiaoming Zheng; Rui Xu; Lizhen Zhang; Yanyan Wang; Xiaoning Wang; Lifang Zhang; Yunlian Cheng; Weihua Qiao; Qingwen Yang (Theoretical and Applied Genetics, 2018)

The Role of WD40-Repeat Protein 62 (MCPH2) in Brain Growth: Diverse Molecular and Cellular Mechanisms Required for Cortical Development - Belal Shohayeb; Nicholas Rui Lim; Uda Ho; Zhiheng Xu; Mirella Dottori; Leonie Quinn; Dominic Chi Hiung Ng (Molecular Neurobiology, 2018)

Effects of Rhizoma Alismatis extract on biochemical indices and adipose gene expression in oleic acid-induced hepatocyte injury in Jian carp (Cyprinus carpio var. Jian) - Jinliang Du; Rui Jia; Li-ping Cao; Weidong Ding; Pao Xu; Guojun Yin (Fish Physiology and Biochemistry, 2018)

Study of Phosphorus Removal by Using Sponge Iron Adsorption - Rui Xue; Jian Xu; Li Gu; Longhui Pan; Qiang He (Water, Air, & Soil Pollution, 2018)

A novel 76-mer peptide mimic with the synergism of superoxide dismutase and glutathione peroxidase - Yawei Xu; Yan Zhou; Rui Yin; Cheng Wang; Haijiao Chu; Junling Wang (In Vitro Cellular & Developmental Biology - Animal, 2018)

Probing the toxic mechanism of bisphenol A with acid phosphatase at the molecular level - Mengchen Xu; Rui Zhang; Wei Song; Wansong Zong; Rutao Liu (Environmental Science and Pollution Research, 2018)

Porosity model and air leakage flow field simulation of goaf based on DEM-CFD - Gang Wang; Hao Xu; Mengmeng Wu; Yue Wang; Rui Wang; Xiaoqiang Zhang (Arabian Journal of Geosciences, 2018)

Tripartite equilibrium strategy for a carbon tax setting problem in air passenger transport - Jiuping Xu; Rui Qiu; Zhimiao Tao; Heping Xie (Environmental Science and Pollution Research, 2018)

The adaptability of a wetland plant species Myriophyllum aquaticum to different nitrogen forms and nitrogen removal efficiency in constructed wetlands - Rui Wang; Na Bai; Shengjun Xu; Guoqiang Zhuang; Zhihui Bai; Zhirui Zhao; Xuliang Zhuang (Environmental Science and Pollution Research, 2018)

AngleNav: MEMS Tracker to Facilitate CT-Guided Puncture - Rui Li; Sheng Xu; William F. Pritchard; John W. Karanian; Venkatesh P. Krishnasamy; Bradford J. Wood; Zion Tsz Ho Tse (Annals of Biomedical Engineering, 2018)

Expression of BpIAA10 from Betula platyphylla (birch) is differentially regulated by different hormones and light intensities - Wendi Xu; Rui Han; Sijia Xu; Jing Jiang; Guifeng Liu (Plant Cell, Tissue and Organ Culture (PCTOC), 2018)

Physico-Chemical Properties, Aerosolization and Dissolution of Co-Spray Dried Azithromycin Particles with L-Leucine for Inhalation - Sharad Mangal; Haichen Nie; Rongkun Xu; Rui Guo; Alex Cavallaro; Dmitry Zemlyanov; Qi Zhou (Pharmaceutical Research, 2018)

The Arc Gene Confers Genetic Susceptibility to Alzheimer’s Disease in Han Chinese - Rui Bi; Li-Li Kong; Min Xu; Guo-Dong Li; Deng-Feng Zhang; Tao Li; Yiru Fang; Chen Zhang; Buchang Zhang; Yong-Gang Yao (Molecular Neurobiology, 2018)

Up-regulation of FOS-like antigen 1 contributes to neuronal apoptosis in the cortex of rat following traumatic brain injury - Xide Xu; Rui Jiang; Peipei Gong; Qianqian Liu; Yinan Chen; Shiqiang Hou; Debin Yuan; Jiansheng Shi; Qing Lan (Metabolic Brain Disease, 2018)

Screening HCV genotype-specific epitope peptides based on conserved sequence analysis and B cell epitope prediction in HCV E2 region - Rui Hua; Xiaoyu Jiang; Lingxia Qi; Shanshan Guan; Ziyu Kuai; Yongbo Qiao; Yan Xu; Xin Gong; Yuhua Shi; Wei Kong; Junqi Niu; Hao Zhang; et al. (Immunologic Research, 2018)

Preparation of Fe-Cu-kaolinite for catalytic wet peroxide oxidation of 4-chlorophenol - Shiwei Zhou; Rui Xu; Jingzhe He; Yongchun Huang; Zejiang Cai; Minggang Xu; Zhengguo Song (Environmental Science and Pollution Research, 2018)

A single nucleotide mutation of IspF gene involved in the MEP pathway for isoprenoid biosynthesis causes yellow-green leaf phenotype in rice - Rui Huang; Yang Wang; Pingrong Wang; Chunmei Li; Fuliang Xiao; Nenggang Chen; Na Li; Caixia Li; Changhui Sun; Lihua Li; Rongjun Chen; Zhengjun Xu; et al. (Plant Molecular Biology, 2018)

Spatial trends and pollution assessment for mercury in the surface soils of the Nansi Lake catchment, China - Ming-Yi Ren; Li-Yuan Yang; Long-Feng Wang; Xue-mei Han; Jie-Rui Dai; Xu-Gui Pang (Environmental Science and Pollution Research, 2018)

TQ-B3203, a potent proliferation inhibitor derived from camptothecin - Xiquan Zhang; Meng Cao; Jing Xing; Fei Liu; Ping Dong; Xin Tian; Hongjiang Xu; Laifang Zhang; Hongmei Gu; Ling Yang; Rui Li; Ming Zheng; et al. (Medicinal Chemistry Research, 2017)

Comparisons of Evaluation Factors and Application Effects of the New [BQ]GSI System with International Rock Mass Classification Systems - Shen Yan-jun; Yan Rui-xin; Yang Geng-she; Xu Guang-li; Wang Shan-yong (Geotechnical and Geological Engineering, 2017)

Flocculation of coal washing wastewater using polysaccharide produced by Paenibacillus mucilaginosus WL412 - Haiyang Xu; Jing Li; Renjie Fu; Rui Cheng; Shiming Wang; Jianfa Zhang (Environmental Science and Pollution Research, 2017)

White Matter Connectivity Pattern Associate with Characteristics of Scalp EEG Signals - Jinnan Gong; Cheng Luo; Xuebin Chang; Rui Zhang; Benjamin Klugah-Brown; Lanjin Guo; Peng Xu; Dezhong Yao (Brain Topography, 2017)

Attenuation of ethanol abstinence-induced anxiety- and depressive-like behavior by the phosphodiesterase-4 inhibitor rolipram in rodents - Mei-Fang Gong; Rui-Ting Wen; Ying Xu; Jian-Chun Pan; Ning Fei; Yan-Meng Zhou; Jiang-Ping Xu; Jian-Hui Liang; Han-Ting Zhang (Psychopharmacology, 2017)

Assessment of rhizosphere processes for removing water-borne macrolide antibiotics in constructed wetlands - Yiping Tai; Nora Fung-Yee Tam; Yunv Dai; Yang Yang; Jianhua Lin; Ran Tao; Yufen Yang; Jiaxi Wang; Rui Wang; Wenda Huang; Xiaodan Xu (Plant and Soil, 2017)

Inhibition of P2X7 Receptor Ameliorates Nuclear Factor-Kappa B Mediated Neuroinflammation Induced by Status Epilepticus in Rat Hippocampus - Cheng Huang; Xiao-sa Chi; Rui Li; Xin Hu; Hai-xia Xu; Jin-mei Li; Dong Zhou (Journal of Molecular Neuroscience, 2017)

Protective effect of Ganoderma lucidum polysaccharide against carbon tetrachloride-induced hepatic damage in precision-cut carp liver slices - Yingjuan Liu; Chunyun Zhang; Jinliang Du; Rui Jia; Liping Cao; Galina Jeney; Hiroki Teraoka; Pao Xu; Guojun Yin (Fish Physiology and Biochemistry, 2017)

Genome editing in potato plants by agrobacterium-mediated transient expression of transcription activator-like effector nucleases - Jin Ma; Heng Xiang; Danielle J. Donnelly; Fan-Rui Meng; Huimin Xu; Dion Durnford; Xiu-Qing Li (Plant Biotechnology Reports, 2017)

Improved GNSS-based indoor positioning algorithm for mobile devices - Rui Xu; Wu Chen; Ying Xu; Shengyue Ji; Jianye Liu (GPS Solutions, 2017)

Lysophosphatidic acid enhances human umbilical cord mesenchymal stem cell viability without differentiation via LPA receptor mediating manner - Narengerile Li; Ya-Li Yan; Sachaofu Fu; Rui-Juan Li; Peng-Fei Zhao; Xi-Yuan Xu; Jing-Ping Yang; Alatangaole Damirin (Apoptosis, 2017)

Oligosaccharide elicitor prepared from Salecan triggers the defense responses of Arabidopsis thaliana Col0 against Botrytis cinerea infection - Haiyang Xu; Jing Li; Shiming Wang; Linxiang Xu; Rui Cheng; Jianfa Zhang (World Journal of Microbiology and Biotechnology, 2017)

Genetic and transcriptomic analyses of lignin- and lodging-related traits in Brassica napus - Lijuan Wei; Hongju Jian; Kun Lu; Nengwen Yin; Jia Wang; Xiujian Duan; Wei Li; Liezhao Liu; Xinfu Xu; Rui Wang; Andrew H. Paterson; Jiana Li (Theoretical and Applied Genetics, 2017)

Rare Genetic Variants of the Transthyretin Gene Are Associated with Alzheimer’s Disease in Han Chinese - Qun Xiang; Rui Bi; Min Xu; Deng-Feng Zhang; Liwen Tan; Chen Zhang; Yiru Fang; Yong-Gang Yao (Molecular Neurobiology, 2017)

Allometric equations of select tree species of the Tibetan Plateau, China - Fei Ran; Rui-ying Chang; Yang Yang; Wan-ze Zhu; Ji Luo; Gen-xu Wang (Journal of Mountain Science, 2017)

Endothelial Progenitor Cells’ Classification and Application in Neurological Diseases - Jing-jing Yuan; Jing Yang; Shi-lei Sun; Rui Zhang; Yu-ming Xu (Tissue Engineering and Regenerative Medicine, 2017)

Memantine Can Reduce Ethanol-Induced Caspase-3 Activity and Apoptosis in H4 Cells by Decreasing Intracellular Calcium - Xiaolong Wang; Jiajun Chen; Hongbo Wang; Hao Yu; Changliang Wang; Jiabin You; Pengfei Wang; Chunmei Feng; Guohui Xu; Xu Wu; Rui Zhao; Guohua Zhang (Journal of Molecular Neuroscience, 2017)

Occurrence and profiles of polybrominated diphenyl ethers (PBDEs) in riverine sediments of Shanghai: a combinative study with human serum from the locals - Ming-Hong Wu; Ben-Tuo Xu; Gang Xu; Ming-Nan Wang; Jing Ma; Chen-Yuan Pan; Rui Sun; Tao Han; Liang Tang (Environmental Geochemistry and Health, 2017)

Site-directed mutagenesis under the direction of in silico protein docking modeling reveals the active site residues of 3-ketosteroid-Δ1-dehydrogenase from Mycobacterium neoaurum - Ning Qin; Yanbing Shen; Xu Yang; Liqiu Su; Rui Tang; Wei Li; Min Wang (World Journal of Microbiology and Biotechnology, 2017)

Multi-parametric study of temperature and thermal damage of tumor exposed to high-frequency nanosecond-pulsed electric fields based on finite element simulation - Yan Mi; Shaoqin Rui; Chengxiang Li; Chenguo Yao; Jin Xu; Changhao Bian; Xuefeng Tang (Medical & Biological Engineering & Computing, 2017)

A Shinella β-N-acetylglucosaminidase of glycoside hydrolase family 20 displays novel biochemical and molecular characteristics - Junpei Zhou; Zhifeng Song; Rui Zhang; Caihong Chen; Qian Wu; Junjun Li; Xianghua Tang; Bo Xu; Junmei Ding; Nanyu Han; Zunxi Huang (Extremophiles, 2017)

Comprehensive Analysis of R2R3-MYB Genes During Adventitious Root Formation in Cuttings of Morus alba - Xiao Long Du; Xu Cao; Chao Rui Yin; Zhuang Tang; Wei Du; Yue Yuan Ban; Jia Ling Cheng (Journal of Plant Growth Regulation, 2017)

Apigenin attenuates streptozotocin-induced pancreatic β cell damage by its protective effects on cellular antioxidant defense - Ning Wang; Wen Jing Yi; Lu Tan; Jia Hui Zhang; Jiamin Xu; Yi Chen; Mengting Qin; Shuang Yu; Jing Guan; Rui Zhang (In Vitro Cellular & Developmental Biology - Animal, 2017)

Formation and evolution of Emeishan basalt saprolite in vadose zones of Touzhai landslide source rockmass - Ji-qing Yang; Ze-min Xu; Rui Zhang; Ji-pu Chen; Zhe Ren; Rong-zhang Luo; Xiu-shuo Zhang (Journal of Mountain Science, 2017)

Lipidomic profiling of juvenile yellow head catfish (Pelteobagrus fulvidraco) in response to Fucoidan diet - Panpan Xu; Yajun Wang; Juanjuan Chen; Rui Yang; Qicun Zhou (Aquaculture International, 2017)

Land use legacies and nitrogen fertilization affect methane emissions in the early years of rice field development - Rui Shao; Ming Xu; Renqiang Li; Xiaoqin Dai; Lixiang Liu; Ye Yuan; Huimin Wang; Fengting Yang (Nutrient Cycling in Agroecosystems, 2017)

Physiological characteristics and metabolomics of transgenic wheat containing the maize C4 phosphoenolpyruvate carboxylase (PEPC) gene under high temperature stress - Xueli Qi; Weigang Xu; Jianzhou Zhang; Rui Guo; Mingzhong Zhao; Lin Hu; Huiwei Wang; Haibin Dong; Yan Li (Protoplasma, 2017)

Oxidative Damage Induced by Arsenic in Mice or Rats: A Systematic Review and Meta-Analysis - Mengchuan Xu; Dongsheng Rui; Yizhong Yan; Shangzhi Xu; Qiang Niu; Gangling Feng; Yan Wang; Shugang Li; Mingxia Jing (Biological Trace Element Research, 2017)

Demethyleneberberine alleviates inflammatory bowel disease in mice through regulating NF-κB signaling and T-helper cell homeostasis - Ying-Ying Chen; Rui-Yan Li; Mei-Jing Shi; Ya-Xing Zhao; Yan Yan; Xin-Xin Xu; Miao Zhang; Xiao-Tong Zhao; Yu-Bin Zhang (Inflammation Research, 2017)

Characterization of uncultivated magnetotactic bacteria from the sediments of Yuehu Lake, China - Haijian Du; Rui Zhang; Wenyan Zhang; Cong Xu; Yiran Chen; Hongmiao Pan; Ke Zhou; Long-fei Wu; Tian Xiao (Acta Oceanologica Sinica, 2017)

The effects of 18β-glycyrrhetinic acid and glycyrrhizin on intestinal absorption of paeoniflorin using the everted rat gut sac model - Rui He; Yongsong Xu; Jingjing Peng; Tingting Ma; Jing Li; Muxin Gong (Journal of Natural Medicines, 2017)

Oxidized graphene-aggravated allergic asthma is antagonized by antioxidant vitamin E in Balb/c mice - Shuai Shang; Jinquan Li; Yun Zhao; Zhuge Xi; Zhisong Lu; Baizhan Li; Xu Yang; Rui Li (Environmental Science and Pollution Research, 2017)

Improved salt tolerance of medicinal plant Codonopsis pilosula by Bacillus amyloliquefaciens GB03 - Qing-Qing Han; Yong-Na Wu; Hui-Juan Gao; Rui Xu; Paul W. Paré; Huazhong Shi; Qi Zhao; Hui-Ru Li; Sardar Ali Khan; Yin-Quan Wang; Suo-Min Wang; Jin-Lin Zhang (Acta Physiologiae Plantarum, 2017)

MicroRNA-9 Mediates the Cell Apoptosis by Targeting Bcl2l11 in Ischemic Stroke - Na Wei; Lin Xiao; Rui Xue; Dandan Zhang; Jun Zhou; Huayan Ren; Si Guo; Jingjing Xu (Molecular Neurobiology, 2016)

Occurrence, fate, and risk assessment of selected endocrine disrupting chemicals in wastewater treatment plants and receiving river of Shanghai, China - Gang Xu; Sihan Ma; Liang Tang; Rui Sun; Jiajia Xiang; Bentuo Xu; Yangyang Bao; Minghong Wu (Environmental Science and Pollution Research, 2016)

Adenovirus-mediated shRNA interference against HSV-1 replication in vitro - Bo Song; Xinjing Liu; Qingzhi Wang; Rui Zhang; Ting Yang; Zhiqiang Han; Yuming Xu (Journal of NeuroVirology, 2016)

Neuroprotective Effects of a PSD-95 Inhibitor in Neonatal Hypoxic-Ischemic Brain Injury - Baofeng Xu; Ai-Jiao Xiao; Wenliang Chen; Ekaterina Turlova; Rui Liu; Andrew Barszczyk; Christopher L. F. Sun; Ling Liu; Michael Tymianski; Zhong-Ping Feng; Hong-Shuo Sun (Molecular Neurobiology, 2016)

Metastasis associated genomic aberrations in stage II rectal cancer - Hong Zhao; Zhi-Zhou Shi; Rui Jiang; Dong-Bing Zhao; Hai-Tao Zhou; Jian-Wei Liang; Xin-Yu Bi; Jian-Jun Zhao; Zhi-Yu Li; Jian-Guo Zhou; Zhen Huang; Ye-Fan Zhang; et al. (Genes & Genomics, 2016)

Paraburkholderia caffeinitolerans sp. nov., a caffeine degrading species isolated from a tea plantation soil sample - Zi-Qing Gao; Dong-Ying Zhao; Lei Xu; Rui-Ting Zhao; Ming Chen; Chun-Zhi Zhang (Antonie van Leeuwenhoek, 2016)

Economic Impact of Stem Borer-Resistant Genetically Modified Sugarcane in Guangxi and Yunnan Provinces of China - Jie Ye; Ying-Ying Yang; Li-Ping Xu; Yang-Rui Li; You-Xiong Que (Sugar Tech, 2016)

Evaluating Sugarcane Productivity in China over Different Periods Using Data Envelopment Analysis and the Malmquist Index - Jie Ye; You-Xiong Que; Yang-Rui Li; Li-Ping Xu (Sugar Tech, 2016)

Erythropoietin Attenuates the Memory Deficits in Aging Rats by Rescuing the Oxidative Stress and Inflammation and Promoting BDNF Releasing - Zhankui Jia; Rui Xue; Shengli Ma; Jingjing Xu; Si Guo; Songchao Li; Erwei Zhang; Jun Wang; Jinjian Yang (Molecular Neurobiology, 2016)

Expression Profile of MiR-128 in the Astrocytoma Patients and Cell Lines - Jingjing Xu; Yuqiong Liu; Si Guo; Shengli Ma; Lin Xiao; Na Wei; Rui Xue (Molecular Neurobiology, 2016)

Application of TiO2-organobentonite modified by cetyltrimethylammonium chloride photocatalyst and polyaluminum chloride coagulant for pretreatment of aging landfill leachate - Yi-Jie Zhang; Zhao-Hui Yang; Pei-Pei Song; Hai-Yin Xu; Rui Xu; Jing Huang; Juan Li; Yan Zhou (Environmental Science and Pollution Research, 2016)

Genomewide analysis of the lateral organ boundaries domain gene family in Vitis vinifera - HUI CAO; CAI-YUN LIU; CHUN-XIANG LIU; YUE-LING ZHAO; RUI-RUI XU (Journal of Genetics, 2016)

Relationship of tropical-cyclone-induced remote precipitation with tropical cyclones and the subtropical high - Rui Xing; Zhiying Ding; Sangjie You; Haiming Xu (Frontiers of Earth Science, 2016)

Assessing spatial likelihood of flooding hazard using naïve Bayes and GIS: a case study in Bowen Basin, Australia - Rui Liu; Yun Chen; Jianping Wu; Lei Gao; Damian Barrett; Tingbao Xu; Linyi Li; Chang Huang; Jia Yu (Stochastic Environmental Research and Risk Assessment, 2016)

Prehistoric agriculture development in the Yunnan-Guizhou Plateau, southwest China: Archaeobotanical evidence - HaiMing Li; XinXin Zuo; LiHong Kang; LeLe Ren; FengWen Liu; HongGao Liu; NaiMeng Zhang; Rui Min; Xu Liu; GuangHui Dong (Science China Earth Sciences, 2016)

Transcriptome analysis reveals translational regulation in barley microspore-derived embryogenic callus under salt stress - Cheng-hong Liu; Rui-ju Lu; Gui-mei Guo; Ting He; Ying-bo Li; Hong-wei Xu; Run-hong Gao; Zhi-wei Chen; Jian-hua Huang (Plant Cell Reports, 2016)

Curdlan blocks the immune suppression by myeloid-derived suppressor cells and reduces tumor burden - Ke Rui; Jie Tian; Xinyi Tang; Jie Ma; Ping Xu; Xinyu Tian; Yungang Wang; Huaxi Xu; Liwei Lu; Shengjun Wang (Immunologic Research, 2016)

Cloning and characterizing of the murine IRF-3 gene promoter region - Hua-Guo Xu; Lifei Liu; Shan Gao; Rui Jin; Wei Ren; Guo-Ping Zhou (Immunologic Research, 2016)

Multi-Level Assessment of Fracture Calluses in Rats Subjected to Low-Magnitude High-Frequency Vibration with Different Rest Periods - Jiazi Gao; He Gong; Xu Huang; Rui Zhang; Renshi Ma; Dong Zhu (Annals of Biomedical Engineering, 2016)

Inoculation of Fe/Mn-oxidizing bacteria enhances Fe/Mn plaque formation and reduces Cd and As accumulation in Rice Plant tissues - Ming Fang Dong; Ren Wei Feng; Rui Gang Wang; Yang Sun; Yong Zhen Ding; Ying Ming Xu; Zhi Lian Fan; Jun Kang Guo (Plant and Soil, 2016)

Cognitive-enhancing effects of hydrolysate of polygalasaponin in SAMP8 mice - Pan Xu; Shu-ping Xu; Ke-zhu Wang; Cong Lu; Hong-xia Zhang; Rui-le Pan; Chang Qi; Yan-yan Yang; Ying-hui Li; Xin-min Liu (Journal of Zhejiang University-SCIENCE B, 2016)

Characterization of a NaCl-tolerant β-N-acetylglucosaminidase from Sphingobacterium sp. HWLB1 - Junpei Zhou; Zhifeng Song; Rui Zhang; Limei Ding; Qian Wu; Junjun Li; Xianghua Tang; Bo Xu; Junmei Ding; Nanyu Han; Zunxi Huang (Extremophiles, 2016)

Dynamics of Dissolved Oxygen and the Affecting Factors in Sediment of Polluted Urban Rivers under Aeration Treatment - Bo Liu; Wen-lin Wang; Rui-ming Han; Ming Sheng; Lin-lin Ye; Xu Du; Xin-ting Wu; Guo-xiang Wang (Water, Air, & Soil Pollution, 2016)

Profiling lipidome changes of Pyropia haitanensis in short-term response to high-temperature stress - Juanjuan Chen; Min Li; Rui Yang; Qijun Luo; Jilin Xu; Yangfang Ye; Xiaojun Yan (Journal of Applied Phycology, 2016)

Impact of temperature variation between adjacent days on childhood hand, foot and mouth disease during April and July in urban and rural Hefei, China - Jian Cheng; Rui Zhu; Zhiwei Xu; Jinju Wu; Xu Wang; Kesheng Li; Liying Wen; Huihui Yang; Hong Su (International Journal of Biometeorology, 2016)

Soil microbial community composition and its driving factors in alpine grasslands along a mountain elevational gradient - Hai-jun Cui; Gen-xu Wang; Yan Yang; Yang Yang; Rui-ying Chang; Fei Ran (Journal of Mountain Science, 2016)

The role of exogenous electron donors for accelerating 2,4,6-trichlorophenol biotransformation and mineralization - Ning Yan; Rongjie Li; Hua Xu; Ling Li; Lihui Yang; Yongming Zhang; Rui Liu; Bruce E. Rittmann (Biodegradation, 2016)

A novel surfactant-, NaCl-, and protease-tolerant β-mannanase from Bacillus sp. HJ14 - Rui Zhang; Zhifeng Song; Qian Wu; Junpei Zhou; Junjun Li; Yuelin Mu; Xianghua Tang; Bo Xu; Junmei Ding; Shucan Deng; Zunxi Huang (Folia Microbiologica, 2016)

EPMA-World Congress 2015 - Jella-Andrea Abraham; Olga Golubnitschaja; Ildar Akhmetov; Russell J. Andrews; Leonidas Quintana; Russell J. Andrews; Babak Baban; Jun Yao Liu; Xu Qin; Tailing Wang; Mahmood S. Mozaffari; Viktoriia V. Bati; et al. (EPMA Journal, 2016)

Plasma miR-221/222 Family as Novel Descriptive and Prognostic Biomarkers for Glioma - Rui Zhang; Bo Pang; Tao Xin; Hua Guo; Yi Xing; Shangchen Xu; Bin Feng; Bin Liu; Qi Pang (Molecular Neurobiology, 2016)

Optimization of combinations of ginsenoside-Rg1, ginsenoside-Rb1, evodiamine and rutaecarpine for effective therapy of mouse migraine - Yanchuan Wu; Xueqiang Pan; Yongsong Xu; Xuran Lu; Shida He; Rui He; Muxin Gong (Journal of Natural Medicines, 2016)

Upregulation of long noncoding RNA TMEVPG1 enhances T helper type 1 cell response in patients with Sjögren syndrome - Juan Wang; Huiyong Peng; Jie Tian; Jie Ma; Xinyi Tang; Ke Rui; Xinyu Tian; Yungang Wang; Jianguo Chen; Liwei Lu; Huaxi Xu; Shengjun Wang (Immunologic Research, 2016)

Inhibition of IRF3 expression reduces TGF-β1-induced proliferation of hepatic stellate cells - Ming-ming Ni; Tao Xu; Ya-rui Wang; Ying-hua He; Qun Zhou; Cheng Huang; Xiao-ming Meng; Jun Li (Journal of Physiology and Biochemistry, 2016)

CXCL16 upregulates RANKL expression in rheumatoid arthritis synovial fibroblasts through the JAK2/STAT3 and p38/MAPK signaling pathway - Chang-hong Li; Lin-lin Xu; Jin-xia Zhao; Lin Sun; Zhong-qiang Yao; Xiao-li Deng; Rui Liu; Lin Yang; Rui Xing; Xiang-yuan Liu (Inflammation Research, 2016)

Landslide monitoring in southwestern China via time-lapse electrical resistivity tomography - Dong Xu; Xiang-Yun Hu; Chun-Ling Shan; Rui-Heng Li (Applied Geophysics, 2016)

Grazing modifies inorganic and organic nitrogen uptake by coexisting plant species in alpine grassland - Lili Jiang; Shiping Wang; Zhe Pang; Changshun Wang; Paul Kardol; Xiaoqi Zhou; Yichao Rui; Zhi chun Lan; Yanfen Wang; Xingliang Xu (Biology and Fertility of Soils, 2016)

Identification of a regulatory element responsible for salt induction of rice OsRAV2 through ex situ and in situ promoter analysis - Yong-Bo Duan; Juan Li; Rui-Ying Qin; Rong-Fang Xu; Hao Li; Ya-Chun Yang; Hui Ma; Li Li; Peng-Cheng Wei; Jian-Bo Yang (Plant Molecular Biology, 2016)

Notch2 signaling contributes to cell growth, invasion, and migration in salivary adenoid cystic carcinoma - Jing Qu; Min Song; Jian Xie; Xiao-Yu Huang; Xiao-Meng Hu; Rui-Huan Gan; Yong Zhao; Li-Song Lin; Jiang Chen; Xu Lin; Da-Li Zheng; You-Guang Lu (Molecular and Cellular Biochemistry, 2016)

Protective action of the phyllanthin against carbon tetrachloride-induced hepatocyte damage in Cyprinus carpio - Rui Jia; Jin-Liang Du; Li-Ping Cao; Ying-Juan Liu; Pao Xu; Guo-Jun Yin (In Vitro Cellular & Developmental Biology - Animal, 2016)

Gas-phase ammonia and PM2.5 ammonium in a busy traffic area of Nanjing, China - Wenxin Wang; Shanshan Wang; Jianhua Xu; Rui Zhou; Chanzhen Shi; Bin Zhou (Environmental Science and Pollution Research, 2016)

The Prevention Effect of Selenium on Prevalence of Children Kaschin-Beck Disease in Active Endemic Areas in Qinghai Plateau - Qiang Li; Zhi-jun Zhao; Pei-zhen Yang; Xiao-qing Xu; Yu-fang Liu; Hui-zhen Yu; Xiao Ma; Rui Du; Lei Zhu (Biological Trace Element Research, 2016)

Flow regime of the three outlets on the south bank of Jingjiang River, China: an impact assessment of the Three Gorges Reservoir for 2003–2010 - Rui Zhang; Shuang-hu Zhang; Wei Xu; Ben-de Wang; Hao Wang (Stochastic Environmental Research and Risk Assessment, 2015)

Curcumin Promotes Cell Cycle Arrest and Inhibits Survival of Human Renal Cancer Cells by Negative Modulation of the PI3K/AKT Signaling Pathway - Hao Zhang; Weili Xu; Baolin Li; Kai Zhang; Yudong Wu; Haidong Xu; Junyong Wang; Jun Zhang; Rui Fan; Jinxing Wei (Cell Biochemistry and Biophysics, 2015)

Molecular and biochemical characterizations of a new low-temperature active mannanase - Rui Zhang; Junpei Zhou; Yajie Gao; Yaping Guan; Junjun Li; Xianghua Tang; Bo Xu; Junmei Ding; Zunxi Huang (Folia Microbiologica, 2015)

Effect of irrigation on the soil respiration of constructed grasslands in Inner Mongolia, China - Ji–Rui Gong; Sha Xu; Yihui Wang; Qinpu Luo; Min Liu; Wei Zhang (Plant and Soil, 2015)

Mutations in human IFT140 cause non-syndromic retinal degeneration - Mingchu Xu; Lizhu Yang; Feng Wang; Huajin Li; Xia Wang; Weichen Wang; Zhongqi Ge; Keqing Wang; Li Zhao; Hui Li; Yumei Li; Ruifang Sui; et al. (Human Genetics, 2015)

Estimation of Permeability from NMR Logs Based on Formation Classification Method in Tight Gas Sands - Deng-Feng Wei; Xiao-Peng Liu; Xiao-Xin Hu; Rui Xu; Ling-Ling Zhu (Acta Geophysica, 2015)

DNA methylation level of promoter region of activating transcription factor 5 in glioma - Xiao-min Hua; Juan Wang; Dong-meng Qian; Jing-yi Song; Hao Chen; Xiu-li Zhu; Rui Zhou; Yu-dan Zhao; Xiu-zhi Zhou; Ling Li; Li Zhang; Xu-xia Song; et al. (Journal of Zhejiang University-SCIENCE B, 2015)

Predicting Inter-session Performance of SMR-Based Brain–Computer Interface Using the Spectral Entropy of Resting-State EEG - Rui Zhang; Peng Xu; Rui Chen; Fali Li; Lanjin Guo; Peiyang Li; Tao Zhang; Dezhong Yao (Brain Topography, 2015)

Thermosensation and longevity - Rui Xiao; Jianfeng Liu; X. Z. Shawn Xu (Journal of Comparative Physiology A, 2015)

Cloning and analysis of β-amyrin synthase gene in Bupleurum chinense - Ke Gao; Su-rui Wu; Ling Wang; Yan-hong Xu; Jian-he Wei; Chun Sui (Genes & Genomics, 2015)

GRY79 encoding a putative metallo-β-lactamase-trihelix chimera is involved in chloroplast development at early seedling stage of rice - Chunmei Wan; Chunmei Li; Xiaozhi Ma; Yang Wang; Changhui Sun; Rui Huang; Ping Zhong; Zhiyan Gao; Dan Chen; Zhengjun Xu; Jianqing Zhu; Xiaoling Gao; et al. (Plant Cell Reports, 2015)

Activation of VEGF/Flk-1-ERK Pathway Induced Blood–Brain Barrier Injury After Microwave Exposure - Li-Feng Wang; Xiang Li; Ya-Bing Gao; Shui-Ming Wang; Li Zhao; Ji Dong; Bin-Wei Yao; Xin-Ping Xu; Gong-Min Chang; Hong-Mei Zhou; Xiang-Jun Hu; Rui-Yun Peng (Molecular Neurobiology, 2015)

Baicalein inhibits prostate cancer cell growth and metastasis via the caveolin-1/AKT/mTOR pathway - Zhaoxin Guo; Xiaolin Hu; Zhaoquan Xing; Rui Xing; Renguang Lv; Xiangyu Cheng; Jing Su; Zunlin Zhou; Zhonghua Xu; Sten Nilsson; Zhaoxu Liu (Molecular and Cellular Biochemistry, 2015)

Hepatoprotective and antioxidant effects of phyllanthin against carbon tetrachloride-induced liver injury in Cyprinus carpio - Rui Jia; Jin-Liang Du; Li-Ping Cao; Ying-Juan Liu; Pao Xu; Guo-Jun Yin (Aquaculture International, 2015)

All-trans retinoic acid up-regulates the human CD2AP gene expression through Sp1/Sp3 binding sites - Hua-Guo Xu; Rui Jin; Shan Gao; Wei Ren; Li Zou; Lifei Liu; Guo-Ping Zhou (Immunologic Research, 2015)

Higenamine regulates Nrf2-HO-1-Hmgb1 axis and attenuates intestinal ischemia–reperfusion injury in mice - Chao Liu; Chenyu Zhu; Guangsheng Wang; Rui Xu; Yaoming Zhu (Inflammation Research, 2015)

A comprehensive meta-analysis of association between genetic variants of GDF5 and osteoarthritis of the knee, hip and hand - Rui Zhang; Jianfeng Yao; Peng Xu; Baohu Ji; James V. Luck; Brian Chin; Shemin Lu; John R. Kelsoe; Jie Ma (Inflammation Research, 2015)

Decreased expression of microRNA-125a-3p upregulates interleukin-23 receptor in patients with Hashimoto’s thyroiditis - Huiyong Peng; Yingzhao Liu; Jie Tian; Jie Ma; Xinyi Tang; Jun Yang; Ke Rui; Yue Zhang; Chaoming Mao; Liwei Lu; Huaxi Xu; Shengjun Wang (Immunologic Research, 2015)

Ribosomal Protein L3 Mutations are Associated with cfr-Mediated Linezolid Resistance in Clinical Isolates of Staphylococcus cohnii - Hongtao Xu; Rui Tian; Yanming Li; Dongke Chen; Yalin Liu; Yunjian Hu; Fei Xiao (Current Microbiology, 2015)

A simple and rapid approach to manipulate pseudorabies virus genome by CRISPR/Cas9 system - Aotian Xu; Chao Qin; Yue Lang; Mingyue Wang; Mengyang Lin; Chuang Li; Rui Zhang; Jun Tang (Biotechnology Letters, 2015)

Burkholderia metalliresistens sp. nov., a multiple metal-resistant and phosphate-solubilising species isolated from heavy metal-polluted soil in Southeast China - Jun Kang Guo; Yong Zhen Ding; Ren Wei Feng; Rui Gang Wang; Ying Ming Xu; Chun Chen; Xiu Li Wei; Wei Min Chen (Antonie van Leeuwenhoek, 2015)

A novel method for rapid in vivo induction of homogeneous polyploids via calluses in a woody fruit tree (Ziziphus jujuba Mill.) - Qing-Hua Shi; Ping Liu; Meng-Jun Liu; Jiu-Rui Wang; Juan Xu (Plant Cell, Tissue and Organ Culture (PCTOC), 2015)

MiR-1224-5p acts as a tumor suppressor by targeting CREB1 in malignant gliomas - Jin Qian; Rui Li; Ying-Yi Wang; Yan Shi; Wen-Kang Luan; Tao Tao; Jun-Xia Zhang; Yi-Chang Xu; Yong-Ping You (Molecular and Cellular Biochemistry, 2015)

GITRL as a genetic adjuvant enhances enterovirus 71 VP1 DNA vaccine immunogenicity - Jing Yuan; Xinyi Tang; Kai Yin; Jie Tian; Ke Rui; Jie Ma; Chaoming Mao; Jianguo Chen; Liwei Lu; Huaxi Xu; Shengjun Wang (Immunologic Research, 2015)

Capecitabine plus oxaliplatin (XELOX) compared with 5-fluorouracil/leucovorin plus oxaliplatin (FOLFOXs) in advanced gastric cancer: meta-analysis of randomized controlled trials - Hong-Bin Xu; Fang Huang; Rui Su; Fu-Ming Shen; Qian-Zhou Lv (European Journal of Clinical Pharmacology, 2015)

An instrumented flume to investigate the initiation mechanism of the post-earthquake huge debris flow in the southwest of China - W. Hu; Q. Xu; C. Rui; R. Q. Huang; T. W. J. van Asch; X. Zhu; Q. Q. Xu (Bulletin of Engineering Geology and the Environment, 2015)

Evaluation of yeasts from Tibetan fermented products as agents for biocontrol of blue mold of Nashi pear fruits - Hao Hu; Yang Xu; Huang-ping Lu; Rui Xiao; Xiao-dong Zheng; Ting Yu (Journal of Zhejiang University-SCIENCE B, 2015)

Inhibiting β-Amyloid-Associated Alzheimer’s Pathogenesis In Vitro and In Vivo by a Multifunctional Dimeric Bis(12)-hupyridone Derived from Its Natural Analogue - Shengquan Hu; Rui Wang; Wei Cui; Zaijun Zhang; Shinghung Mak; Daping Xu; Chunglit Choi; Karl Wahkeung Tsim; Paul R. Carlier; Mingyuen Lee; Yifan Han (Journal of Molecular Neuroscience, 2015)

Improved FLL-assisted PLL with in-phase pre-filtering to mitigate amplitude scintillation effects - Rui Xu; Zhizhao Liu; Wu Chen (GPS Solutions, 2015)

Tumor Necrosis Factor-Related Apoptosis Inducing Ligand Gene Polymorphisms are Correlated with Gastric Cancer in Central China - Changgao Wang; Shufang Xu; Fengming Yi; Xiaobing Wang; Yuan Lei; Sha Huang; Rui Zhou; Bing Xia (Pharmaceutical Research, 2015)

Effect of grazing on the abundance of functional genes associated with N cycling in three types of grassland in Inner Mongolia - K. Ding; L. Zhong; X. P. Xin; Z. H. Xu; X. M. Kang; W. J. Liu; Y. C. Rui; L. L. Jiang; L. Tang; Y. F. Wang (Journal of Soils and Sediments, 2015)

Assessment of growth rate, chlorophyll a fluorescence, lipid peroxidation and antioxidant enzyme activity in Aphanizomenon flos-aquae, Pediastrum simplex and Synedra acus exposed to cadmium - Xiaofei Ran; Rui Liu; Sha Xu; Fang Bai; Jinzhu Xu; Yanjun Yang; Junqiong Shi; Zhongxing Wu (Ecotoxicology, 2015)

A novel missense mutation in collagenous domain of EDA gene in a Chinese family with X-linked hypohidrotic ectodermal dysplasia - DAXU LI; RAN XU; FUMENG HUANG; BIYUAN WANG; YU TAO; ZIJIAN JIANG; HAIRUI LI; JIANFENG YAO; PENG XU; XIAOKANG WU; LE REN; RUI ZHANG; et al. (Journal of Genetics, 2015)

Characterization of Sphingomonas sp. JB13 exo-inulinase: a novel detergent-, salt-, and protease-tolerant exo-inulinase - Junpei Zhou; Mozhen Peng; Rui Zhang; Junjun Li; Xianghua Tang; Bo Xu; Junmei Ding; Yajie Gao; Junrong Ren; Zunxi Huang (Extremophiles, 2015)

Statures in Han populations of China - LianBin Zheng; YongLan Li; HuanJiu Xi; KeLi Yu; ShunHua Lu; Rui Shi; YouFeng Wen; JingPing Bao; XingHua Zhang; YuLing Li; Fu Ren; GuoChang Xu (Science China Life Sciences, 2015)

Upregulation of HIF-1α Via Activation of ERK and PI3K Pathway Mediated Protective Response to Microwave-Induced Mitochondrial Injury in Neuron-Like Cells - Li Zhao; Yue-Feng Yang; Ya-Bing Gao; Shui-Ming Wang; Li-Feng Wang; Hong-Yan Zuo; Ji Dong; Xin-Ping Xu; Zhen-Tao Su; Hong-Mei Zhou; Ling-Ling Zhu; Rui-Yun Peng (Molecular Neurobiology, 2014)

Expression and prognostic role of SGTA in human breast carcinoma correlates with tumor cell proliferation - Ting Zhu; Zhengxiang Ji; Caixia Xu; Zhiyang Peng; Liang Gu; Rui Zhang; Yangchen Liu (Journal of Molecular Histology, 2014)

Optimal intervention time of vagal stimulation attenuating myocardial ischemia/reperfusion injury in rats - Qiang Wang; Rui-Ping Li; Fu-Shan Xue; Shi-Yu Wang; Xin-Long Cui; Yi Cheng; Gao-Pu Liu; Xu Liao (Inflammation Research, 2014)

Detection and Analysis of 12 Heavy Metals in Blood and Hair Sample from a General Population of Pearl River Delta Area - Jiqiang Li; Dongzhi Cen; Donglan Huang; Xufeng Li; Jiajun Xu; Shilin Fu; Rui Cai; Xiaocong Wu; Ming Tang; Yao Sun; Jiren Zhang; Jingfen Zheng (Cell Biochemistry and Biophysics, 2014)

Genomewide identification and expression analysis of the ARF gene family in apple - XIAO-CUI LUO; MEI-HONG SUN; RUI-RUI XU; HUAI-RUI SHU; JIA-WEI WANG; SHI-ZHONG ZHANG (Journal of Genetics, 2014)

Association of microRNA-3144 variant with the susceptibility to hepatocellular carcinoma - Jun Zhang; Rui Wang; Min Cai; Shunji Yu; Yanyun Ma; Weihong Xu; Chunfang Gao; Jiucun Wang; Lifang Hou; Yi Liu; Jie Liu (Genes & Genomics, 2014)

Rheological Characteristics of Weak Rock Mass and Effects on the Long-Term Stability of Slopes - Tianhong Yang; Tao Xu; Hongyuan Liu; Chunming Zhang; Shanyong Wang; Yongqin Rui; Li Shen (Rock Mechanics and Rock Engineering, 2014)

Involvement of calcium-sensing receptors in hypoxia-induced vascular remodeling and pulmonary hypertension by promoting phenotypic modulation of small pulmonary arteries - Xue Peng; Hong-Xia Li; Hong-Jiang Shao; Guang-Wei Li; Jian Sun; Yu-Hui Xi; Hong-Zhu Li; Xin-Yan Wang; Li-Na Wang; Shu-Zhi Bai; Wei-Hua Zhang; Li Zhang; et al. (Molecular and Cellular Biochemistry, 2014)

Impact of diurnal temperature range on human health: a systematic review - Jian Cheng; Zhiwei Xu; Rui Zhu; Xu Wang; Liu Jin; Jian Song; Hong Su (International Journal of Biometeorology, 2014)

PAHs in PM2.5 in Zhengzhou: concentration, carcinogenic risk analysis, and source apportionment - Jia Wang; Ning Bo Geng; Yi Fei Xu; Wen Ding Zhang; Xiao Yan Tang; Rui Qin Zhang (Environmental Monitoring and Assessment, 2014)

Isolation and functional characterization of a novel rice constitutive promoter - Juan Li; Rong-Fang Xu; Rui-Ying Qin; Hui Ma; Hao Li; Ying-Ping Zhang; Li Li; Peng-Cheng Wei; Jian-Bo Yang (Plant Cell Reports, 2014)

Production of low phytic acid rice by hairpin RNA- and artificial microRNA-mediated silencing of OsMIK in seeds - Wen-Xu Li; Jian-Zhong Huang; Hai-Jun Zhao; Yuan-Yuan Tan; Hai-Rui Cui; Yves Poirier; Qing-Yao Shu (Plant Cell, Tissue and Organ Culture (PCTOC), 2014)

Upregulation of EHD2 after Intracerebral Hemorrhage in Adult Rats - Kaifu Ke; Ying Rui; Lei Li; Heyi Zheng; Wei Xu; Xiang Tan; Jianhua Cao; Xiaoyan Wu; Gang Cui; Maohong Cao (Journal of Molecular Neuroscience, 2014)

ORF005L from infectious spleen and kidney necrosis virus is located in the inner mitochondrial membrane and induces apoptosis - Rui Wang; Yang Yi; Lihong Liu; Yanghong Lu; Shaoping Weng; Jianguo He; Xiaopeng Xu (Virus Genes, 2014)

Effects of Hydrogen Sulfide on Growth, Antioxidative Capacity, and Ultrastructural Changes in Oilseed Rape Seedlings Under Aluminum Toxicity - Ping Qian; Rui Sun; Basharat Ali; Rafaqat A. Gill; Ling Xu; Weijun Zhou (Journal of Plant Growth Regulation, 2014)

Gabapentin Enhances the Morphine Anti-Nociceptive Effect in Neuropathic Pain via the Interleukin-10-Heme Oxygenase-1 Signalling Pathway in Rats - Yu-Hua Bao; Quan-Hong Zhou; Rui Chen; Hao Xu; Lu-Lu Zeng; Xin Zhang; Wei Jiang; Dong-Ping Du (Journal of Molecular Neuroscience, 2014)

A thermo-halo-tolerant and proteinase-resistant endoxylanase from Bacillus sp. HJ14 - Junpei Zhou; Qian Wu; Rui Zhang; Minghe Mo; Xianghua Tang; Junjun Li; Bo Xu; Junmei Ding; Qian Lu; Zunxi Huang (Folia Microbiologica, 2014)

DNA Methylation: Roles in Rheumatoid Arthritis - Feng-Lai Yuan; Xia Li; Rui-Sheng Xu; Dong-Lin Jiang; Xiao-Gang Zhou (Cell Biochemistry and Biophysics, 2014)

Seed-specific silencing of OsMRP5 reduces seed phytic acid and weight in rice - Wen-Xu Li; Hai-Jun Zhao; Wei-Qin Pang; Hai-Rui Cui; Yves Poirier; Qing-Yao Shu (Transgenic Research, 2014)

Consumption of hydrogen-rich water alleviates renal injury in spontaneous hypertensive rats - Hai-Guang Xin; Bei-Bei Zhang; Zhi-Qin Wu; Xiao-Feng Hang; Wen-Sheng Xu; Wu Ni; Rui-Qi Zhang; Xiao-Hui Miao (Molecular and Cellular Biochemistry, 2014)

Expression of bone morphogenetic protein 2, 4, and related components of the BMP signaling pathway in the mouse uterus during the estrous cycle - Yan Li; Quan-wei Wei; Jian-gang Feng; Mu-lin Xu; Rui-hua Huang; Fang-xiong Shi (Journal of Zhejiang University-SCIENCE B, 2014)

Internal loop photo-biodegradation reactor used for accelerated quinoline degradation and mineralization - Ling Chang; Yongming Zhang; Lu Gan; Hua Xu; Ning Yan; Rui Liu; Bruce E. Rittmann (Biodegradation, 2014)

Effect of Iodine Excess on Th1, Th2, Th17, and Treg Cell Subpopulations in the Thyroid of NOD.H-2h4 Mice - Xiao Yang; Tianshu Gao; Rui Shi; Xiyu Zhou; Jinqiao Qu; Jia Xu; Zhongyan Shan; Weiping Teng (Biological Trace Element Research, 2014)

The sensitivity analysis of different induced polarization models used in magnetotelluric method - Rui Tang; Peng Yu; Yang Xiang; Xu Zhang (Acta Geodaetica et Geophysica, 2014)

The association between the Lys751Gln polymorphism in the XPD gene and the risk of bladder cancer - Tianyuan Xiong; Jiqiao Yang; Haichuan Wang; Fanyi Wu; Yang Liu; Rui Xu; Zi Lv; Pei Xue; Wen Cao; Yonggang Zhang (Molecular Biology Reports, 2014)

The metabolism of 8-heptadecene in Pyropia (Bangiaceae, Rhodophyta) - Min Zhang; Rui-Xia Li; Chuan-Ming Hu; Li-En Yang; Jun Tang; Qin-Qin Lu; Tao Zhang; Zong-Gen Shen; Song-Dong Shen; Pu Xu; Jian-Yi Zhu (Journal of Applied Phycology, 2014)

Recombinant expression and characterization of an acid-, alkali- and salt-tolerant β-1,3-1,4-glucanase from Paenibacillus sp. S09 - Rui Cheng; Linxiang Xu; Shiming Wang; Yang Wang; Jianfa Zhang (Biotechnology Letters, 2014)

Selection and Characterization of a Peptide Specifically Targeting to Gastric Cancer Cell Line SGC-7901 Using Phage Display - Han Wang; Rui Li; Caixia Ma; Shaoying Lu; Dan Zhang; Yonge Guo; ChunYan Li; Jinling Wu; Qixuan Wang; Jinhui Xu; Yanyan Hu; Yuen Liu; et al. (International Journal of Peptide Research and Therapeutics, 2014)

MicroRNA-128 regulates the differentiation of rat bone mesenchymal stem cells into neuron-like cells by Wnt signaling - Rui Wu; Yue Tang; Wenqiao Zang; Yuanyuan Wang; Min Li; Yuwen Du; Guoqiang Zhao; Yuming Xu (Molecular and Cellular Biochemistry, 2014)

Phytoremediation potential of Pteris vittata L. under the combined contamination of As and Pb: beneficial interaction between As and Pb - Xiao-ming Wan; Mei Lei; Tong-bin Chen; Guang-dong Zhou; Jun Yang; Xiao-yong Zhou; Xi Zhang; Rui-xiang Xu (Environmental Science and Pollution Research, 2014)

Lack of association between the polymorphisms of hypoxia-inducible factor 1A (HIF1A) gene and SLE susceptibility in a Chinese population - Chen-Chen Feng; Qian-Ling Ye; Yan Zhu; Rui-Xue Leng; Gui-Mei Chen; Jie Yang; Han Cen; Xiao-Ke Yang; Rui Li; Wang-Dong Xu; Hai-Feng Pan; Dong-Qing Ye (Immunogenetics, 2014)

Characterization of OsMIK in a rice mutant with reduced phytate content reveals an insertion of a rearranged retrotransposon - Hai-Jun Zhao; Hai-Rui Cui; Xiu-Hong Xu; Yuan-Yuan Tan; Jun-Jie Fu; Guo-Zhen Liu; Yves Poirier; Qing-Yao Shu (Theoretical and Applied Genetics, 2013)

Paclobutrazol Improved the Reproductive Growth and the Quality of Seed Oil of Jatropha curcas - Gang Xu; Rui Luo; Yinan Yao (Journal of Plant Growth Regulation, 2013)

Microbial Treatment for Prevention and Removal of Paraffin Deposition on the Walls of Crude Pipelines - Jiang Hong Liu; Yun Peng Jia; Yi Tong Chen; Rui Dan Xu (Indian Journal of Microbiology, 2013)

Effect of Intravenous Infusion of Dexmedetomidine Combined with Inhalation of Isoflurane on Arterial Oxygenation and Intrapulmonary Shunt During Single-Lung Ventilation - Rui Xia; Hong Yin; Zhong-yuan Xia; Qing-jun Mao; Gong-da Chen; Wei Xu (Cell Biochemistry and Biophysics, 2013)

Expression and Functional Significance of Ezrin in Human Brain Astrocytoma - Jie Mao; Xian-rui Yuan; Shan-shui Xu; Xiao-chun Jiang; Xin-tong Zhao (Cell Biochemistry and Biophysics, 2013)

Wip1 Phosphatase Involved in Lipopolysaccharide-Induced Neuroinflammation - Xiang Tan; Jingjing Zhang; Wei Jin; Lei Li; Wei Xu; Heyi Zheng; Ying Rui; Kaifu Ke; Ranran Zhou; Maohong Cao; Yongjin Pan (Journal of Molecular Neuroscience, 2013)

Elevated risk of opportunistic viral infection in patients with Crohn’s disease during biological therapies: a meta analysis of randomized controlled trials - Xiaobing Wang; Feng Zhou; Junzhang Zhao; Rui Zhou; Meifang Huang; Jin Li; Wei Wang; Shufang Xu; Bing Xia (European Journal of Clinical Pharmacology, 2013)

Up-regulation of SGTB is associated with neuronal apoptosis after neuroinflammation induced by lipopolysaccharide - Maohong Cao; Wei Xu; Jian Yu; Heyi Zheng; Xiang Tan; Lei Li; Ying Rui; Guangfei Xu; Gang Cui; Jian Xu; Jianhua Cao; Tao Tao; et al. (Journal of Molecular Histology, 2013)

Up-regulated expression of Bnip3L after intracerebral hemorrhage in adult rats - Ying Rui; Kaifu Ke; Lei Li; Heyi Zheng; Wei Xu; Xiang Tan; Jianhua Cao; Xiaoyan Wu; Gang Cui; Guangwei Zhao; Yilu Gao; Maohong Cao (Journal of Molecular Histology, 2013)

Estimations of net primary productivity and evapotranspiration based on HJ-1A/B data in Jinggangshan city, China - Rong-hua Zhang; Rui Sun; Jun-ping Du; Ting-long Zhang; Yao Tang; Hong-wei Xu; Sheng-tian Yang; Wei-guo Jiang (Journal of Mountain Science, 2013)

Increased Expression of Small Heat Shock Protein αB-crystallin After Intracerebral Hemorrhage in Adult Rats - Kaifu Ke; Lei Li; Ying Rui; Heyi Zheng; Xiang Tan; Wei Xu; Jianhua Cao; Jian Xu; Gang Cui; Guangfei Xu; Maohong Cao (Journal of Molecular Neuroscience, 2013)

Membrane Damage Induced by Supercritical Carbon Dioxide in Rhodotorula mucilaginosa - Jun Li; Aiying Wang; Fengmei Zhu; Rui Xu; Xiao Song Hu (Indian Journal of Microbiology, 2013)

The Effect of Energy Substrates on PHB Accumulation of Acidiphilium cryptum DX1-1 - Ai-ling Xu; Jin-lan Xia; Zhi-wen Song; Peng Jiang; Yan Xia; Min-xi Wan; Rui-yong Zhang; Yi Yang; Ke-ke Liu (Current Microbiology, 2013)

Comprehensive identification of high-frequency and co-occurring Mafa-DPA1, Mafa-DQA1, Mafa-DRA, and Mafa-DOA alleles in Vietnamese cynomolgus macaques - Ruirui Xiang; Huiling Zhang; Qing Deng; Rui Yue; Haite Tang; Yanqi Zhang; Fei Ling; Min Zhuo; Hongli Du; Shiqian Xu; Qiang Xu; Xiaoning Wang (Immunogenetics, 2013)

Activating transcription factor 4 is involved in endoplasmic reticulum stress-mediated apoptosis contributing to vascular calcification - Xiao-Hui Duan; Jin-Rui Chang; Jing Zhang; Bao-Hong Zhang; Yu-Lin Li; Xu Teng; Yi Zhu; Jie Du; Chao-Shu Tang; Yong-Fen Qi (Apoptosis, 2013)

The member of high temperature requirement family HtrA2 participates in neuronal apoptosis after intracerebral hemorrhage in adult rats - Huiqing Sun; Lei Li; Feng Zhou; Lin Zhu; Kaifu Ke; Xiang Tan; Wei Xu; Ying Rui; Heyi Zheng; Zhengming Zhou; Huiguang Yang (Journal of Molecular Histology, 2013)

Determination of oxidized scytonemin in Nostoc commune Vauch cultured on different conditions by high performance liquid chromatography coupled with triple quadrupole mass spectrometry - Juanjuan Chen; Lijuan Zhao; Jilin Xu; Rui Yang; Shan He; Xiaojun Yan (Journal of Applied Phycology, 2013)

Cloning, characterization and expression of the LECT2 gene in grass carp - Tian Yuan; Chuang Li; Ji-Rui Gu; Yue-Jun Fu; Heng Xu (Fish Physiology and Biochemistry, 2013)

Involvement of dopamine D2 receptors activation in ischemic post-conditioning-induced cardioprotection through promoting PKC-ε particulate translocation in isolated rat hearts - Jun Gao; Jin Guo; Hongxia Li; Shuzhi Bai; Hong Li; Bo Wu; Lina Wang; Yuhui Xi; Ye Tian; Guangdong Yang; Rui Wang; Lingyun Wu; et al. (Molecular and Cellular Biochemistry, 2013)

Jasmonates modulate the promotion effects induced by SNP on root development of wheat under osmotic stress through lipoxygenase activation - Xianye Wang; Ning Wang; Qi Rui; Peng Zhang; Langlai Xu (Journal of Plant Biochemistry and Biotechnology, 2013)

Hydrological Simulation by SWAT Model with Fixed and Varied Parameterization Approaches Under Land Use Change - Jinkang Du; Hanyi Rui; Tianhui Zuo; Qian Li; Dapeng Zheng; Ailing Chen; Youpeng Xu; C.-Y. Xu (Water Resources Management, 2013)

Association of interleukin-1 receptor-associated kinase (IRAK1) gene polymorphisms (rs3027898, rs1059702) with systemic lupus erythematosus in a Chinese Han population - Yu Zhai; Ke Xu; Rui-Xue Leng; Han Cen; Wei Wang; Yan Zhu; Mo Zhou; Chen-Chen Feng; Dong-Qing Ye (Inflammation Research, 2013)

Recombinant High Density Lipoprotein Nanoparticles for Target-Specific Delivery of siRNA - Mengjie Rui; Hailing Tang; Yan Li; Xiaohui Wei; Yuhong Xu (Pharmaceutical Research, 2013)

Pelagibacterium nitratireducens sp.nov., A Marine Alphaproteobacterium Isolated from the East China Sea - Qipei Li; Yongle Xu; Keshao Liu; Lanlan Cai; Yingnan Fu; Jia Sun; Rui Zhang (Current Microbiology, 2013)

Upregulation of CBLL1 in rat brain cortex after lipopolysaccharide treated - Maohong Cao; Heyi Zheng; Xiang Tan; Wei Xu; Ying Rui; Lei Li; Xiaofei Liu; Guangfei Xu; Gang Cui; Jian Xu; Jianhua Cao; Kaifu Ke; et al. (Journal of Molecular Histology, 2013)

WHAMM is required for meiotic spindle migration and asymmetric cytokinesis in mouse oocytes - Xin Huang; Lu Ding; Rui Pan; Peng-Fei Ma; Pan-Pan Cheng; Chun-Hui Zhang; Yu-Ting Shen; Lin Xu; Yu Liu; Xiao-Qin He; Zhong-Quan Qi; Hai-Long Wang (Histochemistry and Cell Biology, 2013)

Genomewide analysis of the chitinase gene family in Populus trichocarpa - CONG JIANG; RUI FANG HUANG; JIA LIANG SONG; MIN REN HUANG; LI AN XU (Journal of Genetics, 2013)

Antidepressant-like effect of flaxseed secoisolariciresinol diglycoside in ovariectomized mice subjected to unpredictable chronic stress - Xing Ma; Rui Wang; Xin Zhao; Chong Zhang; Jiao Sun; Jianxin Li; Lu Zhang; Tuo Shao; Lina Ruan; Liang Chen; Ying Xu; Jianchun Pan (Metabolic Brain Disease, 2013)

The protective effect of silymarin on the carbon tetrachloride (CCl4)-induced liver injury in common carp (Cyprinus carpio) - Rui Jia; Liping Cao; Jinliang Du; Pao Xu; Galina Jeney; Guojun Yin (In Vitro Cellular & Developmental Biology - Animal, 2013)

Multi-scale spatial determinants of dissolved oxygen and nutrients in Qiantang River, China - Shiliang Su; Rui Xiao; Xiangyang Xu; Zhonghao Zhang; Xiaoya Mi; Jiaping Wu (Regional Environmental Change, 2013)

The roles of ADIPOQ genetic variations in cancer risk: evidence from published studies - Yeqiong Xu; Bangshun He; Yuqin Pan; Ling Gu; Zhenlin Nie; Liping Chen; Rui Li; Tianyi Gao; Shukui Wang (Molecular Biology Reports, 2013)

Expression profiles of Th17 pathway related genes in human systemic lupus erythematosus - Hai-Feng Pan; Rui-Xue Leng; Chen-Chen Feng; Xiang-Pei Li; Gui-Mei Chen; Bao-Zhu Li; Wang-Dong Xu; Song Guo Zheng; Dong-Qing Ye (Molecular Biology Reports, 2013)

Novel association of a PROC variant with ischemic stroke in a Chinese Han population - Xuan Lu; Liang Tang; Kang Xu; Jie Ma; Tao Guo; Heng Mei; Rui Yang; Jianming Yu; Qingyun Wang; Yan Yang; Xiaorong Jian; Yu Hu (Human Genetics, 2013)

Effects of Sub-soil Drip Fertigation on Sugarcane in Field Conditions - Gui-Fen Chen; Qi-Zhan Tang; Yang-Rui Li; Yu-Yi Huang; Bin Liu; Lin Xu; Hai-Rong Huang (Sugar Tech, 2012)

Exogenous hydrogen sulfide attenuates diabetic myocardial injury through cardiac mitochondrial protection - Xin Zhong; Leihong Wang; Yuwen Wang; Shiyun Dong; Xiaoning Leng; Jing Jia; Yajun Zhao; Hulun Li; Xinying Zhang; Changqing Xu; Guangdong Yang; Lingyun Wu; et al. (Molecular and Cellular Biochemistry, 2012)

Postconditioning with vagal stimulation attenuates local and systemic inflammatory responses to myocardial ischemia reperfusion injury in rats - Qiang Wang; Yi Cheng; Fu-Shan Xue; Yu-Jing Yuan; Jun Xiong; Rui-Ping Li; Xu Liao; Jian-Hua Liu (Inflammation Research, 2012)

Association of interleukin 23 receptor gene polymorphisms (rs10489629, rs7517847) with rheumatoid arthritis in European population: a meta-analysis - Yu Zhai; Ke Xu; Fen Huang; Hui Peng; Chen-Chen Feng; Kao-Kao Zhu; Rui-Xue Leng; Hai-Feng Pan; Dong-Qing Ye (Molecular Biology Reports, 2012)

Isolation and characterization of fifteen novel microsatellite loci in golden mandarin fish (Siniperca scherzeri) Steindachne - Min Yang; Xu-Fang Liang; ChangXu Tian; Yasmeen Gul; YaQi Dou; Liang Cao; Rui Yu (Conservation Genetics Resources, 2012)

Warming and grazing increase mineralization of organic P in an alpine meadow ecosystem of Qinghai-Tibet Plateau, China - Yichao Rui; Yanfen Wang; Chengrong Chen; Xiaoqi Zhou; Shiping Wang; Zhihong Xu; Jichuang Duan; Xiaoming Kang; Shunbao Lu; Caiyun Luo (Plant and Soil, 2012)

Increased expression of calcium-sensing receptors in atherosclerosis confers hypersensitivity to acute myocardial infarction in rats - Jin Guo; Hong-zhu Li; Lu-chuan Wang; Wei-hua Zhang; Guang-wei Li; Wen-jing Xing; Rui Wang; Chang-qing Xu (Molecular and Cellular Biochemistry, 2012)

Synthesis and studies on antidepressant activity of 2′,4′,6′-trihydroxychalcone derivatives - Xin Sui; Ying-Chun Quan; Yue Chang; Rui-Peng Zhang; Yin-Feng Xu; Li-Ping Guan (Medicinal Chemistry Research, 2012)

Characterization of a spliced variant of human IRF-3 promoter and its regulation by the transcription factor Sp1 - Wei Ren; Liang-Hua Zhu; Hua-Guo Xu; Rui Jin; Guo-Ping Zhou (Molecular Biology Reports, 2012)

Synthesis of 2-R1-2-(4-(2-fluoroethoxy)benzamido)acetate as potential PET imaging agents - Yong He; Jingli Xu; Hang Liu; Man Feng; Xiao Wang; Rui Ding; Chuanmin Qi; Yurong Chen; Fang Li; Zhao-Hui Zhu; Yong-Hong Dang; Ming Wang; et al. (Medicinal Chemistry Research, 2012)

In vitro and in vivo hepatoprotective and antioxidant effects of Astragalus polysaccharides against carbon tetrachloride-induced hepatocyte damage in common carp (Cyprinus carpio) - Rui Jia; Liping Cao; Pao Xu; Galina Jeney; Guojun Yin (Fish Physiology and Biochemistry, 2012)

Gene expression profile of campylobacter jejuni-induced GBS in bama miniature pigs - Feng Xue; Dexin Zeng; Fei Xu; Rui Zhang; Yang Chen; Yuefei Yang; Xiaobo Wang; Zhenzhong Li; Xiaorong Zhang; Yuan Jiang (Cell and Tissue Research, 2012)

Synthesis of benzopyrano[4,3-b](N-arylsulfonyl)indoles and benzopyrano[3,4-b](N-arylsulfonyl)indoles via intramolecular palladium-catalyzed aryl–aryl coupling reaction - Ling-ling Fan; Zhi-ping Che; Rui Zhang; Xiang Yu; Xiao-yan Zhi; Hui Xu (Molecular Diversity, 2012)

siRNAs target sites selection of ezrin and the influence of RNA interference on ezrin expression and biological characters of osteosarcoma cells - XiFu Shang; YaoFei Wang; QiChun Zhao; KeRong Wu; Xu Li; XiaoFeng Ji; Rui He; WenZhi Zhang (Molecular and Cellular Biochemistry, 2012)

Erbin inhibits TGF-β1-induced EMT in renal tubular epithelial cells through an ERK-dependent pathway - Qiaodan Zhou; Rui Zeng; Chuou Xu; Lili Liu; Lin Chen; Pei Kou; Guangchang Pei; Shoujun Bai; Yamin Zhang; Caixia Li; Song Rong; Min Han; et al. (Journal of Molecular Medicine, 2012)

Preparation and bioevaluation of 99mTc nitrido radiopharmaceuticals with pyrazolo[1,5-a]pyrimidine as tumor imaging agents - Rui Ding; Yong He; Jingli Xu; Hang Liu; Xiao Wang; Man Feng; Chuanmin Qi; Junbo Zhang; Cheng Peng (Medicinal Chemistry Research, 2012)

Oceaniovalibus guishaninsula gen. nov., sp. nov., A Marine Bacterium of the Family Rhodobacteraceae - Keshao Liu; Rui Zong; Qipei Li; Yingnan Fu; Yongle Xu; Yanan Wang; Nianzhi Jiao (Current Microbiology, 2012)

Natural Heritage value of Xinjiang Tianshan and global comparative analysis - Xiaoliang Xu; Zhaoping Yang; Adayi Saiken; Shao Rui; Xinyu Liu (Journal of Mountain Science, 2012)

In silico identification of potential drug targets in swine pathogen Haemophilus parasuis - Zhuofei Xu; Lifang Ma; Huanchun Chen; Rui Zhou (Genes & Genomics, 2012)

Involvement of calcium-sensing receptor in oxLDL-induced MMP-2 production in vascular smooth muscle cells via PI3K/Akt pathway - Hong-Xia Li; Fan-Juan Kong; Shu-Zhi Bai; Wen He; Wen-Jing Xing; Yu-Hui Xi; Guang-Wei Li; Jin Guo; Hong-Zhu Li; Ling-Yun Wu; Rui Wang; Guang-Dong Yang; et al. (Molecular and Cellular Biochemistry, 2012)

A New Piezochromic Fluorescence and Aggregation-Induced Emission Compound Containing Tetraphenylethylene and Triphenylamine Moieties with Morphology-alterable Property - Xie Zhou; Hai-yin Li; Zhen-guo Chi; Bing-jia Xu; Xi-qi Zhang; Yi Zhang; Si-wei Liu; Jia-rui Xu (Journal of Fluorescence, 2012)

The genetic analysis of the flp locus of Actinobacillus pleuropneumoniae - Tingting Li; Zhuofei Xu; Tengfei Zhang; Lu Li; Huanchun Chen; Rui Zhou (Archives of Microbiology, 2012)

Transcriptional control of human CD2AP expression: the role of Sp1 and Sp3 - Hua-Guo Xu; Wei Ren; Li Zou; Yi Wang; Rui Jin; Guo-Ping Zhou (Molecular Biology Reports, 2012)

The short-term cover crops increase soil labile organic carbon in southeastern Australia - Xiaoqi Zhou; Chengrong Chen; Shunbao Lu; Yichao Rui; Hanwen Wu; Zhihong Xu (Biology and Fertility of Soils, 2012)

Type 17 T-helper cells might be a promising therapeutic target for osteoporosis - Feng-Lai Yuan; Xia Li; Wei-Guo Lu; Yi-Qing Zhao; Cheng-Wan Li; Jian-Ping Li; Jun-Ming Sun; Rui-Sheng Xu (Molecular Biology Reports, 2012)

The Mechanism of the Molecular Interaction between Cerium (III) and Ribulose-1,5-Bisphosphate Carboxylase/Oxygenase (Rubisco) - Chao Liu; Fa-shui Hong; Ye Tao; Tao Liu; Ya-ning Xie; Jian-hua Xu; Zhong-rui Li (Biological Trace Element Research, 2011)

Characterization of a novel isoform of the human ORMDL3 gene - Rui Jin; Wen-Xiao Yuan; Hua-Guo Xu; Wei Ren; Li-Li Zhuang; Guo-Ping Zhou (Cell and Tissue Research, 2011)

The characterization of two novel IRF-3 transcripts starting from intron 2 of the wild type of IRF-3 - Wei Ren; Hua-Guo Xu; Chao Lu; Rui Jin; Li Zou; Yi Wang; Guo-Ping Zhou (Molecular Biology Reports, 2011)

Warming and grazing affect soil labile carbon and nitrogen pools differently in an alpine meadow of the Qinghai–Tibet Plateau in China - Yichao Rui; Shiping Wang; Zhihong Xu; Yanfen Wang; Chengrong Chen; Xiaoqi Zhou; Xiaoming Kang; Shunbao Lu; Yigang Hu; Qiaoyan Lin; Caiyun Luo (Journal of Soils and Sediments, 2011)

Synthesis and Characterization of Triphenylethylene Derivatives with Aggregation-Induced Emission Characteristics - Xiao-Fang Li; Zhen-Guo Chi; Bing-Jia Xu; Hai-Yin Li; Xi-Qi Zhang; Wei Zhou; Yi Zhang; Si-Wei Liu; Jia-Rui Xu (Journal of Fluorescence, 2011)

Organochlorine pesticides in the soil of a karst cave in Guilin, China - Yinghui Wang; Songjun Guo; Rui Xue; Shihua Qi; Yiyin Xu; Baoming Xue; Daoxian Yuan (Environmental Monitoring and Assessment, 2011)

Calculations of rock matrix modulus based on a linear regression relation - Xi-Lei He; Zhen-Hua He; Rui-Liang Wang; Xu-Ben Wang; Lian Jiang (Applied Geophysics, 2011)

Expression of a novel gene FAM43B repressing cell proliferation is regulated by DNA methylation in hepatocellular carcinoma cell lines - Xiao Xu; Rui-Fang Liu; Bing-Bing Wan; Wen-Ming Xing; Jian Huang; Ze-Guang Han (Molecular and Cellular Biochemistry, 2011)

Aerosol size distributions in urban Jinan: Seasonal characteristics and variations between weekdays and weekends in a heavily polluted atmosphere - Pengju Xu; Wenxing Wang; Lingxiao Yang; Qingzhu Zhang; Rui Gao; Xinfeng Wang; Wei Nie; Xiaomei Gao (Environmental Monitoring and Assessment, 2011)

A study on the effects of the surrounding faults on water loss in the Zoige Wetland, China - Mei Li; Rui Xu; Wendian Huang; Hailong Sun; Lin Luo (Journal of Mountain Science, 2011)

Proteomic analysis of seed germination under salt stress in soybeans - Xiao-yan Xu; Rui Fan; Rui Zheng; Chun-mei Li; De-yue Yu (Journal of Zhejiang University-SCIENCE B, 2011)

Construction of the yeast whole-cell Rhizopus oryzae lipase biocatalyst with high activity - Mei-ling Chen; Qin Guo; Rui-zhi Wang; Juan Xu; Chen-wei Zhou; Hui Ruan; Guo-qing He (Journal of Zhejiang University-SCIENCE B, 2011)

Symbiotic nitrogen fixation and soil N availability under legume crops in an arid environment - Xiaoqi Zhou; Xian Liu; Yichao Rui; Chengrong Chen; Hanwen Wu; Zhihong Xu (Journal of Soils and Sediments, 2011)

Risk assessment of polycyclic aromatic hydrocarbons in aquatic ecosystems - Bing Wu; Rui Zhang; Shu-Pei Cheng; Timothy Ford; Ai-Min Li; Xu-Xiang Zhang (Ecotoxicology, 2011)

Risk of high-grade bleeding in patients with cancer treated with bevacizumab: a meta-analysis of randomized controlled trials - Xiao Feng Hang; Wen Sheng Xu; Jun Xue Wang; Lei Wang; Hai Guang Xin; Rui Qi Zhang; Wu Ni (European Journal of Clinical Pharmacology, 2011)

Molecular and serological diversity in Apple chlorotic leaf spot virus from sand pear (Pyrus pyrifolia) in China - Yansu Song; Ni Hong; Liping Wang; Hongju Hu; Rui Tian; Wenxing Xu; Fang Ding; Guoping Wang (European Journal of Plant Pathology, 2011)

COD removal from expanded granular sludge bed effluent using a moving bed biofilm reactor and their microbial community analysis - Bo Fu; Xiaoyi Liao; Rui Liang; Lili Ding; Ke Xu; Hongqiang Ren (World Journal of Microbiology and Biotechnology, 2011)

Estimate of eddy energy generation/dissipation rate in the world ocean from altimetry data - Chi Xu; Xiao-Dong Shang; Rui Xin Huang (Ocean Dynamics, 2011)

Analysis on the interaction between IL-1F7 gene and environmental factors on patients with ankylosing spondylitis: a case-only study - Rui Ge; Faming Pan; Fangfang Liao; Guo Xia; Yang Mei; Beibei Shen; Tianchen Zhang; Jing Gao; Li Zhang; Zhenhua Duan; Shengqian Xu; Jianhua Xu (Molecular Biology Reports, 2011)

Artesunate inhibits growth and induces apoptosis in human osteosarcoma HOS cell line in vitro and in vivo - Qiang Xu; Zhao-xu Li; Hui-qin Peng; Zheng-wang Sun; Rui-lin Cheng; Zhao-ming Ye; Wei-xu Li (Journal of Zhejiang University-SCIENCE B, 2011)

Direct repression of the human IRF-3 promoter by E2F1 - Hua-Guo Xu; Wei Ren; Li Zou; Yi Wang; Rui Jin; Guo-Ping Zhou (Immunogenetics, 2011)

Multiple amino acid variations in the nonstructural proteins of swine Japanese encephalitis virus alter its virulence in mice - Rui Wu; Yongxiang Tian; Junhua Deng; Keli Yang; Wangwang Liang; Rui Guo; Zhengying Duan; Zewen Liu; Danna Zhou; Diping Xu (Archives of Virology, 2011)

Molecular cloning, characterization and expression analysis of adenylosuccinate lyase gene in grass carp (Ctenopharyngodon idella) - Tian Yuan; Ji-Rui Gu; Wen-Bo Gu; Jiang Wu; Shao-Rong Ge; Heng Xu (Molecular Biology Reports, 2011)

Targeting interleukin-21 in rheumatoid arthritis - Feng-Lai Yuan; Wei Hu; Wei-Guo Lu; Xia Li; Jian-Ping Li; Rui-Sheng Xu; Cheng-Wan Li; Fei-Hu Chen; Cheng Jin (Molecular Biology Reports, 2011)

Human Prion Protein Mutants with Deleted and Inserted Octarepeats Undergo Different Pathways to Trigger Cell Apoptosis - Kun Xu; Xin Wang; Qi Shi; Cao Chen; Chan Tian; Xiao-Li Li; Rui-Min Zhou; Yong-Lie Chu; Xiao-Ping Dong (Journal of Molecular Neuroscience, 2011)

Synthesis and Properties of Diphenylcarbazole Triphenylethylene Derivatives with Aggregation-Induced Emission, Blue Light Emission and High Thermal Stability - Bing-jia Xu; Zhen-guo Chi; Xiao-fang Li; Hai-yin Li; Wei Zhou; Xi-qi Zhang; Cheng-cheng Wang; Yi Zhang; Si-wei Liu; Jia-rui Xu (Journal of Fluorescence, 2011)

Comparison of Responsive Behaviors of Two Cinnamic Acid Derivatives Containing Carbazolyl Triphenylethylene - Xi-qi Zhang; Zhen-guo Chi; Bing-jia Xu; Hai-yin Li; Wei Zhou; Xiao-fang Li; Yi Zhang; Si-wei Liu; Jia-rui Xu (Journal of Fluorescence, 2011)

RETRACTED ARTICLE: Cytotoxic activities of tubeimoside-2 on human hepatoma HepG2 cells by induction of G2/M phase arrest and apoptosis in a p53-dependent manner - Ying-Yong Zhao; Xu Chao; Yongmin Zhang; Li-Jun Sun; Hong Zhang; Rui-Chao Lin; Xuefeng Shen; Wen-Ji Sun (Apoptosis, 2010)

Inhibition of acid-sensing ion channels in articular chondrocytes by amiloride attenuates articular cartilage destruction in rats with adjuvant arthritis - Feng-Lai Yuan; Fei-Hu Chen; Wei-Guo Lu; Xia Li; Jian-ping Li; Cheng-Wan Li; Rui-Sheng Xu; Fan-Rong Wu; Wei Hu; Teng-Yue Zhang (Inflammation Research, 2010)

The functional expression of calcium-sensing receptors in BRL cells and related signal transduction pathway responsible for intracellular calcium elevation - Wenjing Xing; Guangwei Li; Yuhui Xi; Jin Guo; Hongzhu Li; Hongxia Li; Weihua Zhang; Li Zhang; Lingyun Wu; Rui Wang; Changqing Xu (Molecular and Cellular Biochemistry, 2010)

Identification of the VP92R gene from infectious spleen and kidney necrosis virus - Xiaopeng Xu; Qingxia Lu; Rui Wang; Ting Lin; Shaoping Weng; Ling Lu; Zhongsheng Li; Xiaoqiang Yu; Junliang Tang; Jianguo He (Virus Genes, 2010)

The functional expression of calcium-sensing receptor in the differentiated THP-1 cells - Yu-hui Xi; Hong-zhu Li; Wei-hua Zhang; Li-na Wang; Li Zhang; Yan Lin; Shu-zhi Bai; Hong-xia Li; Ling-yun Wu; Rui Wang; Chang-qing Xu (Molecular and Cellular Biochemistry, 2010)

Isolation and characterization of a gene encoding a polyethylene glycol-induced cysteine protease in common wheat - Qing-Wei Zang; Cai-Xiang Wang; Xu-Yan Li; Zhi-Ai Guo; Rui-Lian Jing; Jun Zhao; Xiao-Ping Chang (Journal of Biosciences, 2010)

Seasonal variation analysis of atmospheric CH4, N2O and CO2 in Tianjin offshore area - ShaoFei Kong; Bing Lu; Bin Han; ZhiPeng Bai; Zhun Xu; Yan You; LiangMao Jin; XiaoYang Guo; Rui Wang (Science China Earth Sciences, 2010)

Testicular toxicity induced by dietary cadmium in cocks and ameliorative effect by selenium - Jin-Long Li; Rui Gao; Shu Li; Jin-Tao Wang; Zhao-Xin Tang; Shi-Wen Xu (BioMetals, 2010)

Combined application of NPK on yield quality of sugarcane applied through SSDI - Lin Xu; Hai-Rong Huang; Li-Tao Yang; Yang-Rui Li (Sugar Tech, 2010)

Isolation, Functional Characterization, and Expression Pattern of a Vacuolar Na+/H+ Antiporter Gene TrNHX1 from Trifolium repens L. - Rui Tang; Cui Li; Kai Xu; Yanhua Du; Tao Xia (Plant Molecular Biology Reporter, 2010)

Photocatalytic degradation of organic dyes by Er3+:YAlO3/TiO2 composite under solar light - Jun Wang; Yingpeng Xie; Zhaohong Zhang; Jia Li; Chengwu Li; Liquan Zhang; Zhiqiang Xing; Rui Xu; Xiangdong Zhang (Environmental Chemistry Letters, 2010)

Microbial community structure and diversity in a native forest wood-decomposed hollow-stump ecosystem - Bao-Yu Tian; Qin-Geng Huang; Yan Xu; Chun-Xiang Wang; Rui-Rui Lv; Jian-Zhong Huang (World Journal of Microbiology and Biotechnology, 2010)

Scutellarin exerts its anti-hypertrophic effects via suppressing the Ca2+-mediated calcineurin and CaMKII signaling pathways - Zhen-Wei Pan; Ying Zhang; Dong-Hua Mei; Rui Zhang; Jing-Hao Wang; Xiang-Ying Zhang; Chang-Qing Xu; Yan-Jie Lu; Bao-Feng Yang (Naunyn-Schmiedeberg's Archives of Pharmacology, 2010)

No significant association between Fc receptor-like 3 gene polymorphisms and human leukocyte antigen-B27 positive ankylosing spondylitis in Han Chinese population - Guo Xia; Faming Pan; Fangfang Liao; Xiaowu Tang; Rui Ge; Yang Mei; Heping Pan; Shengqian Xu; Jianhua Xu (Molecular Biology Reports, 2010)

Isolation and Analysis of Rice Rf1-Orthologus PPR Genes Co-segregating with Rf3 in Maize - Xiang-Bo Xu; Zhan-Xian Liu; Deng-Feng Zhang; Ying Liu; Wei-Bin Song; Jian-Sheng Li; Jing-Rui Dai (Plant Molecular Biology Reporter, 2009)

Involvement of the ornithine decarboxylase/polyamine system in precondition-induced cardioprotection through an interaction with PKC in rat hearts - Ya-Jun Zhao; Wei-Hua Zhang; Chang-Qing Xu; Hong-Zhu Li; Li-Na Wang; Hong Li; Yi-Hua Sun; Yan Lin; Li-Ping Han; Li Zhang; Yie Tian; Rui Wang; et al. (Molecular and Cellular Biochemistry, 2009)

Effects of rice cropping intensity on soil nitrogen mineralization rate and potential in buried ancient paddy soils from the Neolithic Age in China’s Yangtze River Delta - Jia Lu; Zhengyi Hu; Zhihong Xu; Zhihong Cao; Shunyao Zhuang; Linzhang Yang; Xiangui Lin; Yuanhua Dong; Rui Yin; Jinlong Ding; Yunfei Zheng (Journal of Soils and Sediments, 2009)

The Influence of Cosolvent on the Complexation of HP-β-cyclodextrins with Oleanolic Acid and Ursolic Acid - Rui Li; Peng Quan; Dong-Fei Liu; Fang-Di Wei; Qing Zhang; Qun-Wei Xu (AAPS PharmSciTech, 2009)

Inhibitory effect of reinioside C on monocyte–endothelial cell adhesion induced by oxidized low-density lipoprotein via inhibiting NADPH oxidase/ROS/NF-κB pathway - Yong-Ping Bai; Chang-ping Hu; Mei-Fang Chen; Kang-Ping Xu; Gui-Shan Tan; Rui-Zhen Shi; Yuan-Jian Li; Guo-Gang Zhang (Naunyn-Schmiedeberg's Archives of Pharmacology, 2009)

Manganese-induced changes of the biochemical characteristics of the recombinant wild-type and mutant PrPs - Xiao-Li Li; Chen-Fang Dong; Gui-Rong Wang; Rui-Min Zhou; Qi Shi; Chan Tian; Chen Gao; Guo-Yong Mei; Cao Chen; Kun Xu; Jun Han; Xiao-Ping Dong (Medical Microbiology and Immunology, 2009)

Function and regulation of TRP family channels in C. elegans - Rui Xiao; X. Z. Shawn Xu (Pflügers Archiv - European Journal of Physiology, 2009)

Infectivity and propagation of attenuated infectious bursal disease virus in the chicken B-lymphocyte cell line DT40 - Jun Luo; Gai-Ping Zhang; Jian-Ming Fan; Man Teng; Lei-Ming You; Ling Zhou; Rui-Guang Deng; Xuan-Nian Wang; Yan-Yan Yang; Li Wang; Guang-Xu Xing; Na Cheng (Archives of Virology, 2009)

Genesis and stability of the Zhoujiawan landslide, Three Gorges, China - Wen-jie Xu; Rui-lin Hu; Zhong-qi Yue; Ru-jiao Tan (Bulletin of Engineering Geology and the Environment, 2009)

Expression of thyrotropin-releasing hormone receptors in rat testis and their role in isolated Leydig cells - Yong Zhao; Wu-Gang Hou; Hua-Ping Zhu; Jie Zhao; Rui-An Wang; Ruo-Jun Xu; Yuan-Qiang Zhang (Cell and Tissue Research, 2008)

Cloning and characterization of phosphorus starvation inducible Brassica napus PURPLE ACID PHOSPHATASE 12 gene family, and imprinting of a recently evolved MITE-minisatellite twin structure - Kun Lu; You-Rong Chai; Kai Zhang; Rui Wang; Li Chen; Bo Lei; Jun Lu; Xin-Fu Xu; Jia-Na Li (Theoretical and Applied Genetics, 2008)

Deglycosylation altered the gating properties of rNav1.3: glycosylation/deglycosylation homeostasis probably complicates the functional regulation of voltage-gated sodium channel - Qing Xu; Hui-Wen Cheng; Hui-Qiong He; Zhi-Rui Liu; Ming He; Hong-Tian Yang; Zhi-Lei Zhou; Yong-Hua Ji (Neuroscience Bulletin, 2008)

Vesicular stomatitis virus matrix protein gene enhances the antitumor effects of radiation via induction of apoptosis - Xiao-Bo Du; Jin-Yi Lang; Jian-Rong XU; You Lu; Yan-Jun Wen; Ju-Mei Zhao; Peng Diao; Zhi-Ping Yuan; Bin Yao; Ling-Yu Fan; Guo-Qing Wang; Li Liu; et al. (Apoptosis, 2008)

Genome sequence and characterization of a new virus infecting Mikania micrantha H.B.K. - Rui-Long Wang; Ling-Wen Ding; Qiao-Yang Sun; Jing Li; Zeng-Fu Xu; Shao-Lin Peng (Archives of Virology, 2008)

The research of air pollution based on spectral features in leaf surface of Ficus microcarpa in Guangzhou, China - Jie Wang; Ruisong Xu; Yueliang Ma; Li Miao; Rui Cai; Yu Chen (Environmental Monitoring and Assessment, 2008)

Neuropeptide Y promotes TGF-β1 production in RAW264.7 cells by activating PI3K pathway via Y1 receptor - Jiang-Rui Zhou; Zheng Xu; Chun-Lei Jiang (Neuroscience Bulletin, 2008)

Degradation of Hazardous Dyes in Wastewater using Nanometer Mixed Crystal TiO2 Powders under Visible Light Irradiation - Jun Wang; Ronghe Li; Zhaohong Zhang; Wei Sun; Xiaofang Wang; Rui Xu; Zhiqiang Xing; Xiangdong Zhang (Water, Air, & Soil Pollution, 2008)

Molecular cloning and characterization of two novel cellulase genes from the mollusc Ampullaria crossean - Rui Guo; Ming Ding; Si-Liang Zhang; Gen-jun Xu; Fu-kun Zhao (Journal of Comparative Physiology B, 2008)

Origin of new Brassica types from a single intergeneric hybrid between B. rapa and Orychophragmus violaceus by rapid chromosome evolution and introgression - Chuan-Yuan Xu; Rui-Hong Wan-Yan; Zai-Yun Li (Journal of Genetics, 2007)

Isolation and molecular characterization of the Triticum aestivum L. ethylene-responsive factor 1 (TaERF1) that increases multiple stress tolerance - Zhao-Shi Xu; Lan-Qin Xia; Ming Chen; Xian-Guo Cheng; Rui-Yue Zhang; Lian-Cheng Li; Yun-Xiang Zhao; Yan Lu; Zhi-Yong Ni; Li Liu; Zhi-Gang Qiu; You-Zhi Ma (Plant Molecular Biology, 2007)

Modified Paclitaxel-loaded Nanoparticles for Inhibition of Hyperplasia in a Rabbit Arterial Balloon Injury Model - Lin Mei; Hongfan Sun; Xu Jin; Dunwan Zhu; Rui Sun; Minfang Zhang; Cunxian Song (Pharmaceutical Research, 2007)

Functional response of the predator Scolothrips takahashii to hawthorn spider mite, Tetranychus viennensis: effect of age and temperature - Li Ding-Xu; Tian Juan; Shen Zuo-Rui (BioControl, 2007)

Prohibitin suppresses renal interstitial fibroblasts proliferation and phenotypic change induced by transforming growth factor-β1 - Wei Guo; Hong Xu; Jing Chen; Yong Yang; Jia Wei Jin; Rui Fu; Hai Mei Liu; Xi Liang Zha; Zhi Gang Zhang; Wen Yan Huang (Molecular and Cellular Biochemistry, 2007)

Inhibition of Japanese Encephalitis Virus NS1 Protein Expression in Cell by Small Interfering RNAs - Xueqin Liu; Shengbo Cao; Rui Zhou; Gaoyuan Xu; Shaobo Xiao; Ying Yang; Minxuan Sun; Yaoming Li; Huanchun Chen (Virus Genes, 2006)

A general procedure for the enantioselective synthesis of the minor tobacco alkaloids nornicotine, anabasine, and anatabine - Joshua T. Ayers; Rui Xu; Linda P. Dwoskin; Peter A. Crooks (The AAPS Journal, 2005)

Biophysical studies of a ruthenium(II) polypyridyl complex binding to DNA and RNA prove that nucleic acid structure has significant effects on binding behaviors - Hong Xu; Yi Liang; Peng Zhang; Fen Du; Bing-Rui Zhou; Jun Wu; Jian-Hong Liu; Zhi-Gang Liu; Liang-Nian Ji (JBIC Journal of Biological Inorganic Chemistry, 2005)

Newly Detected Specific Hydrogenation of the Conjugated Double Bond of Unsaturated Alkaloid Lactones by Aspergillus sp. - Hong Guan; Song You; Li Yang; Xu Wang; Rui Ni (Biotechnology Letters, 2005)

Activation of the gene promoter of barley β-1,3-glucanase isoenzyme GIII is salicylic acid (SA)-dependent in transgenic rice plants - Yun-Feng Li; Rui Zhu; Peilin Xu (Journal of Plant Research, 2005)

Introduction of unsaturation into theN-n-alkyl chain of the nicotinic receptor antagonists, NONI and NDNI: Effect on affinity and selectivity - Sangeetha P. Sumithran; Peter A. Crooks; Rui Xu; Jun Zhu; Agripina G. Deaciuc; Lincoln H. Wilkins; Linda P. Dwoskin (The AAPS Journal, 2005)

Study on construction of cDNA libraries from rat normal liver and regeneration liver with smart technique - Lin Jun-Tang; Wang Cong-Rui; Jogenananda Pramanik; Zhang Hui-Yong; Feng Hui-Gen; Yang Bao-Sheng; L. I. Yu-Chang; Xu Cun-Shuan (Indian Journal of Clinical Biochemistry, 2004)

A Chimeric Ecdysone Receptor Facilitates Methoxyfenozide-Dependent Restoration of Male Fertility in ms45 Maize - Erica Unger; A. Mark Cigan; Mary Trimnell; Rui-ji Xu; Tim Kendall; Brad Roth; Marc Albertsen (Transgenic Research, 2002)

Volatile Compounds in Anal Gland of Siberian Weasels (Mustela sibirica) and Steppe Polecats (M. eversmanni) - Jian-Xu Zhang; Lixing Sun; Zhi-Bin Zhang; Zu-Wang Wang; Yi Chen; Rui Wang (Journal of Chemical Ecology, 2002)

Selection and orientation of adjacent genes influences DAM-mediated male sterility in transformed maize - Erica Unger; Steve Betz; Rui-ji Xu; A. Mark Cigan (Transgenic Research, 2001)

New progress of research on water cycle in atmosphere in China - Wang Guo; Jia Shao-feng; Yu Gui-rui; Xu Juan; Wang Jin-xia; Wang Qiu-feng; Ge Quan-sheng; Huang Ji-kun; Xia Jun; Li Li-fnjuan; Jin De-sheng; Dong Suo-cheng; et al. (Journal of Geographical Sciences, 2001)